Constraints from C-O-Sr isotopes on the origin of carbonate minerals in coal-bearing sequences from the Dong Open-pit Mine, Ningwu coal field, Shanxi, China - Shaobo Di; Shifeng Dai; Baruch Spiro; Antonio Delgado; David French; Ian Graham; Jingjing Liu; Shaowei Zhang (Journal of Asian Earth Sciences, 2026)

Testing the general phytoplankton biomarker-based pCO2 proxy across the last 350,000 years - Olivia A. Graham; Caitlyn R. Witkowski; Kate Littler; Richard D. Pancost; Johannes J. Viljoen; B. David A. Naafs (Organic Geochemistry, 2026)

Paleoshorelines on the West Florida Shelf as indicators of past sea levels - Catalina Rubiano; Cheryl J. Hapke; David F. Naar; Alastair G.C. Graham (Continental Shelf Research, 2026)

Albatross and petrel overlap with pelagic longline fisheries in the Eastern Pacific Ocean - Daniel P. Crear; Thomas A. Clay; Ana P.B. Carneiro; Johannes H. Fischer; Igor Debski; David J. Anderson; Jill A. Awkerman; Alastair M.M. Baylis; Elizabeth A. Bell; Letizia Campioni; Paulo Catry; Tyler Clavelle; et al. (Fisheries Research, 2026)

First record of piscivory in ghost pipefishes (Teleostei, Solenostomidae) revealed by micro‐computed tomography - Graham Short; Kerryn Parkinson; Thomas J Peachey; Richard Smith; David Harasti (Journal of Fish Biology, 2026)
Ghost pipefishes (Solenostomidae) have been regarded as specialist crustacean feeders since the 1960s, an inference resting on two primary dietary accounts. We report the first documented evidence of piscivory in the family based on micro‐computed tomography (micro‐CT) examination of voucher specimens of Solenostomus snuffleupagus and S. cyanopterus . Two head‐first teleost prey, both identified as gobiids, were recovered from the holotype of S. snuffleupagus , and additional ichthyic remains were recovered from an S. cyanopterus specimen collected in 1952, indicating a solenostomid diet broader than previously recognized.

North American crayfish: A quest for the biggest catch - Caitlin C. Bloomer; Susan B. Adams; Zanethia C. Barnett; Zackary A. Graham; Emmy M. Delekta; David M. Hayes; Zachary J. Loughman; Hugh MacIntosh; M. Worth Pugh; Karen Reed; Nathaniel F. Shoobs; Christopher A. Taylor; et al. (Ecology, 2026)

Metal resistant bacterial diversity and abundance in four United Kingdom and Indian rivers with different levels of metal and fecal pollution - Sonia Gupta; Panagiota Adamou; David W. Graham; T.R. Sreekrishnan; Shaikh Ziauddin Ahammad (Environmental Pollution, 2026)

Comparing loss-on-ignition, acid decarbonation and combustion elemental analysis for measuring organic carbon concentrations – recommendations for best practice - Robert B. Sparkes; Stuart A. Rae; Lucy McMahon; Hannah L. Mossman; David McKendry; Clare E. Dean; Graham Tinsley; Frances Fowden; Connor J. Grisdale; Hafiza Begum; Holly Hope; Charlotte McEnhill; et al. (Organic Geochemistry, 2026)

Effect of dissolved versus total zinc levels on bacterial zinc-dependent meropenem co-resistance in River Tyne sediments - Catherine L. Hands; Sonia Gupta; Anke Neumann; Charles W. Knapp; S.Z. Ahammad; Jason Snape; David W. Graham (Environmental Pollution, 2026)

The synergistic recovery of aluminum, lithium and gallium from fly ash using physical enrichment followed by an alkali fusion-organic acid leaching method - Chen Li; Chuncai Zhou; David French; Ian T. Graham; Zixuan Wang; Yunfei Li; Feng Wang; Da Li; Guijian Liu (Minerals Engineering, 2026)

In-situ constraints on the occurrence and mineralization of critical elements in Late Triassic coals from the Sichuan Basin, China - Rongjie Wang; Shifeng Dai; Victor P. Nechaev; Sergey Y. Budnitskiy; David French; Ian T. Graham; Xiaoyun Yan; Zhuangzhuang Bao; Junling Lu (Fuel, 2026)

Fire frequency differentially affects carbon pools and pyrogenic organic matter in a South African montane grassland - Victor Johannes Trouw; Olli Hyvärinen; Nicola Findlay; Heidi-Jayne Hawkins; Katja Heister; Walter David Cornelis Schenkeveld; Joris Petrus Gerardus Marinus Cromsigt; Graham Kerley; Mariska Beest te (Plant and Soil, 2026)
Aims Grasslands are globally important for biodiversity and ecosystem services, including carbon storage, and have coevolved with disturbances such as fire. However, the effects of fire on soil carbon storage in southern African grasslands remain poorly understood. We investigated how fire frequency (annual, biennial, quinquennial, and infrequent) influences the distribution of soil organic carbon (SOC) pools in a 40-year burning experiment in a South African montane grassland. Methods Surface soils (0–15 cm) were sampled and separated into free particulate (fPOC), occluded particulate (oPOC), and mineral-associated organic carbon (MAOC) using density fractionation. Pyrogenic organic matter (PyOM) was quantified within each pool across fire treatments. Results Most SOC was mineral-associated, with 88.2% stored as MAOC and 10.1% as particulate organic carbon (free and occluded). Higher fire frequency increased SOC contents, particularly in subsurface soil (5–15 cm), where fPOC and MAOC showed the strongest responses. PyOM increased with depth across all treatments. Annual and biennial fires were less effective at increasing PyOM than infrequent fires, although this pattern depended on the temperature range used in thermogravimetric analysis. Conclusions This study advances our understanding of SOC dynamics in fire-adapted montane grasslands in South Africa by showing that frequent fire can lead to higher fPOC and MAOC pools in subsurface soil. This suggests an important role of fire for the soil carbon storage potential of these grasslands, both through the formation of more stable carbon in pools that are better protected against decomposition and through the contribution of recalcitrant pyrogenic organic material.

Novel rock luminescence dating of snow petrel stomach-oil deposits from East Antarctica - Rachel K. Smedley; David Small; Erin L. McClymont; Michael J. Bentley; Dominic A. Hodgson; Alice Graham (Quaternary Geochronology, 2026)

Neoproterozoic-Early Ordovician sedimentation on the eastern margin of Laurentia: A detrital zircon provenance perspective on the Dalradian Supergroup, Scotland and Ireland - Elias J. Rugen; Rob Strachan; David Chew; Jessica Molesworth; James Lee; Pieter Vermeesch; Dirk Frei; Andrew Morton; Zoe Whittaker; Craig Storey; Marina Seraine; Christopher L. Kirkland; et al. (Earth-Science Reviews, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Habitat and spatial trends of U.K. wintering waterbird populations over 50 years - Blaise Martay; Philipp H. Boersch‐Supan; James W. Pearce‐Higgins; Graham E. Austin; Niall H. K. Burton; David Noble; Kirsi Peck; Simon R. Wotton; Teresa M. Frost (Conservation Biology, 2026)
The United Kingdom is an important wintering ground for millions of waterbirds. Most U.K. wintering waterbird populations increased between 1970 and the mid‐1990s, but declined thereafter. We examined U.K. population indices in 46 wintering waterbird species in two 25‐year periods, 1970–1994 and 1995–2019, to identify which waterbird groups were vulnerable to declines. We modeled abundance to examine whether spatial patterns in population change were consistent with changes in habitat quality, climate, or phenology. We used the resulting model outputs to test whether there were patterns in these relationships across all monitored wintering waterbirds and within groups based on ecology, migratory strategy, and breeding location. Waterbird populations in the United Kingdom increased from 1970 to 1994, particularly in estuaries, but then showed mixed trends from 1995 to 2019: geese and swan populations increased, and waders declined. Wader declines were least apparent, although still declining, in estuaries and most apparent in reservoirs. Increased breeding season temperatures were linked to population increases for most species in both periods, although there was no beneficial impact of climate warming for migrants from 1995 to 2019. We found no evidence that apparent declines were due to phenological changes. These results highlight the need for more research into why U.K. wintering waterbird trends have become more negative over the past 25 years.

Solenostomus snuffleupagus sp. nov., a hairy ghost pipefish (Teleostei: Solenostomidae) from the Southwest Pacific, with an integrative comparison to S. paegnius - Graham Short; David Harasti (Journal of Fish Biology, 2026)
A new species of ghost pipefish, Solenostomus snuffleupagus sp. nov., is described from the Coral Sea based on specimens (18–34 mm SL) collected from coral reef habitats in Queensland, Australia. The species is diagnosed by the following combination of characters: abundant elongate integumentary filaments imparting a conspicuously shaggy appearance; 36 total vertebrae (vs. 32–34 in all congeners); compact body form with a short, deep pretrunk (11%–14% SL); sexually dimorphic supraoccipital crests (moderately elevated in females, strongly developed in males); and two modified anchor‐like ossicles spanning the pterygiophores in both soft dorsal and anal fins. Micro‐CT imaging reveals distinctive pretrunk ossicle configuration characterized by deep angular interspaces and absence of a ventral ossicle series. Mitochondrial COI sequences indicate an uncorrected p‐distance of 22.0% from the superficially similar S. paegnius , a species with which it has long been confused in museum collections and citizen science databases. Field observations document consistent association with dense filamentous red macroalgae, with body coloration closely matching host substrate. The species is currently known from the southwest Pacific, including northeastern Australia (Coral Sea), Papua New Guinea, New Caledonia, Fiji and Tonga, representing a southwestern Pacific distribution.

Strategic deep tillage of deep sand soils impacts the sorption and biological availability of trifluralin - Tom J. Edwards; Stephen L. Davies; Ron J. Yates; Michael T. Rose; Benedict Arthur; John G. Howieson; Graham O’Hara; Emma J. Steel; David JM Hall (Soil and Tillage Research, 2026)

The influence of terrestrial plants on the enrichment of critical metals in coal - Lei Zhao; Qiang Wei; David French; James C. Hower; Ian T. Graham; Gregory C. Smith (Earth-Science Reviews, 2026)

Canada’s climate lobby: networks of fossil dominance and social-ecological advocacy - Nicolas Graham; David Chen; Jean Philippe Sapinski; William K. Carroll (Climatic Change, 2026)

Mechanisms of Strong Hearts, Healthy Communities-2.0 Effects on Weight: A Mediation Analysis - Chad D. Rethorst; Margaret Demment; Meredith L. Graham; Seungyeon Ha; Alexandra L. MacMillan Uribe; Brian K. Lo; Jacob Szeszulski; Phrashiah Githinji; David Strogatz; Sara C. Folta; Miriam E. Nelson; Rebecca A. Seguin-Fowler (Journal of Nutrition Education and Behavior, 2026)

Multiple Mechanisms Required to Predict Grass Community Composition - Jane A. Catford; Laura J. Graham; Harry E. R. Shepherd; Cindy E. Hauser; Nicola T. Munro; Brendan A. Wintle; John G. Donohue; David Tilman; Adam T. Clark (Ecology Letters, 2026)
Accurate prediction of community assembly is a central goal in ecology but is challenging because assembly is governed by numerous mechanisms. Few theoretical models explicitly incorporate or test multiple mechanisms at once. We empirically tested the predictive performance of a plant community assembly model built using all possible combinations of four ‘mechanisms’ (soil resource competition, dispersal and colonisation, spatiotemporal niche differentiation, population growth rates) and 11 underlying ‘attributes’ based on measured traits (e.g., fecundity, phenology). The full model accurately predicted out‐of‐sample biomass observations of five grasses sown in mixture along a soil nitrogen gradient (overall R 2 = 0.65). Alternative model variants, parameterised using subsets of the mechanisms and their nested attributes, still retained high explanatory power if the model included at least three of the four mechanisms. Our results suggest that plant community composition is determined by simultaneous effects of multiple mechanisms, and simpler theories have much lower predictive abilities.

Using herd frailty estimates from survival models in a mortality-based syndromic surveillance system - Jaden M. Carlson; T. Brendan Murphy; Luke O’Grady; Jonas Brock; Maria P. Guelbenzu-Gonzalo; David A. Graham; Guy McGrath; Jamie A. Tratalos; Rafael de Andrade Moral; Niamh Mimnagh; Niamh L. Field; John F. Mee; et al. (Preventive Veterinary Medicine, 2026)

Small methane emissions from pasture observed with eddy covariance and flux-gradient methods: are they real or artefacts? - Johannes Laubach; Aaron M. Wall; John E. Hunt; David I. Campbell; Jordan P. Goodrich; Scott L. Graham; Louis A. Schipper (Agricultural and Forest Meteorology, 2026)

Are Insect Populations Inherently More Variable? A Multi‐Taxa Approach to Characterising Interannual Fluctuations in Insect Time Series - Graham A. Montgomery; Eliza M. Grames; Jake M. Jacobsen; Ethan X. Kahn; Amanda Leyel; Mia C. Rosati; Qiyuan Wu; Chris S. Elphick; David Wagner; Morgan W. Tingley (Ecology Letters, 2026)
The determinants of population variability across taxa, time, and space are not fully understood, particularly for insects, a group with recent reports of widespread abundance declines. We collated data from unpublished and published sources to calculate indices of interannual population variability for over 4500 unique insect time series, comprising data from nearly 1500 species. We evaluate whether insects exhibit greater population variability than other types of animals. Our results demonstrate that insects as a group indeed exhibit much greater population variability than birds, mammals, or fish, but that within Insecta, included orders show similar levels of population variability. We also find that population variability in insects is greater at higher latitudes, for species with smaller body sizes and for shorter, older time series and that it varies between biomes. Overall, our findings can inform the interpretation and prediction of insect population trends, fluctuations and extinction risk in an era of insect decline.

Eastern Tethyan region periodic ecological collapse and recovery from Upper Triassic to Lower Jurassic - Rongjie Wang; Shifeng Dai; James C. Hower; David French; Ian T. Graham; John Dodson; Cortland F. Eble; Jingjing Liu; Zhengfu Zhao (Global and Planetary Change, 2026)

Potassium isotopic variability in coals induced by magmatic and submarine exhalative hydrothermal activity - Shuai Kang; Zhihan Ji; Weiqiang Li; Jingjing Liu; Qian Wang; Na Wang; David French; Ian T. Graham; Victor P. Nechaev; James C. Hower; Jintian Zheng; Mengda Yao; et al. (Geochimica et Cosmochimica Acta, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Black Array of Broadband Absolute Radiometers Earth Radiation Imager: Science Requirements, Instrument Design, and Concept of Operations - Odele Coddington; Cameron Straatsma; Ginger Drake; Kush Tyagi; Michelle Stephens; Chris Yung; Nathan Tomlin; John Lehman; Chip Bollendonk; Paris Buedel; Katherine Catani; Beth Cervelli; et al. (Advances in Atmospheric Sciences, 2026)
The Black Array of Broadband Absolute Radiometers Earth Radiation Imager (BABAR-ERI) is a small, adaptable nadir-pointed pushbroom imager to measure Earth-leaving broadband radiance from 0.3 µm to 100 µm with higher information content than is currently measured by reducing radiometric uncertainty and enabling cloud-resolving spatial resolution. The three-instrument BABAR-ERI suite fits a 12U CubeSat form factor and contains co-registered science telescope channels for measuring shortwave (0.3 µm to 4.5 µm band) and total radiance (0.3 µm to 100 µm band), dual-channel on-board radiance stability monitors, and a visible-wavelength camera. Novel, 1 × 32 element, electrical-substitution radiometer pixels image the shortwave and total radiance in 1 km × 1 km co-registered ground footprints; longwave radiance (4.5 µm to 100 µm band) is derived from subtraction of the shortwave and total radiance. The dual-channel onboard stability monitors are radiance standard detectors, and their measurements, acquired concurrently with the science telescopes and at much different duty cycles for the dual channels, will be used to track and correct the degradation of the science channels. The single-channel, mid-visible camera facilitates geolocation pointing knowledge and provides scene context information and sub-pixel variability to facilitate measurement stability studies and enable process-level science studies at high spatial resolution. The detectors for the science channels and stability monitors are absolute, ambient-temperature, micro-fabricated, electrical-substitution radiometers with near-perfect optical absorptance across the measurement range from vertically aligned carbon nanotubes. The BABAR-ERI science channels will be characterized over the full measurement range and for variable Earth scenes and deep space temperatures during extensive ground calibrations.

Aspects of Germanium and Nickel accumulation in low-ash coal: Examples from the Blue Gem coal, eastern Kentucky, USA - James C. Hower; Susan M. Rimmer; Darrell N. Taulbee; Debora Berti; Robert B. Finkelman; David French; Ian T. Graham; Harold H. Schobert; Lei Zhao; Shifeng Dai (International Journal of Coal Geology, 2026)

Perceived effectiveness of 25 interventions and policies designed to reduce meat consumption - David McBey; Graciela Martinez Sanchez; Graham Horgan; Jennie I. Macdiarmid; Benjamin J.J. McCormick (Food Quality and Preference, 2026)

Craniofacial photography for detection of positional obstructive sleep apnoea - Kate Sutherland; John Wheatley; Kristina Kairaitis; Brendon J. Yee; Gary Cohen; Kerri Melehan; Stephen Lambert; Philip de Chazal; Peter A. Cistulli; Peter Cistulli; Philip de Chazal; Nina Sarkissian; et al. (Sleep and Biological Rhythms, 2026)
Supine-dependent OSA is a well-recognised OSA phenotype and may relate to craniofacial structure. Our aim was to assess whether craniofacial photos are able to identify positional OSA, specifically supine-isolated OSA, in comparison to non-positional OSA. Frontal and profile craniofacial photographs of participants were acquired according to a standardised protocol. Photographs were analysed and compared between non-positional and supine-isolated OSA groups. A total of 156 OSA patients were included (54.5% supine-isolated OSA, 45.5% with non-positional OSA). The supine-isolated group had a longer upper face height and greater upper-to-lower face height ratio, smaller face width, reduced face width-to-height ratio, and smaller mandibular width, length, and size of the mandibular base. Differences in facial measurements were no longer significant after adjustment for body size and OSA severity. Our study demonstrates that supine-isolated OSA can be identified using facial photography. Larger studies in groups matched for BMI and OSA severity are needed to confirm whether this technique may also capture other features related to supine-isolated OSA (i.e., differences in underlying skeletal structure).

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Removal of antimicrobial resistance determinants from wastewater: Role of capacity overloading and treatment technology in wastewater treatment plants - Vikas Sonkar; Arun Kashyap; Rebeca Pallares-Vega; Sai Sugitha Sasidharan; Sangeetha Chandrakalabai Jambu; Nikash Naorem; David W. Graham; Jan-Ulrich Kreft; Shashidhar Thatikonda (Journal of Environmental Management, 2025)

Cool transient lithospheric thermal conditions driven by subduction recorded by Neoarchean diamonds from Knee Lake, northwestern Superior Craton - Andrea Pezzera; Fabrizio Nestola; Thomas Stachel; Richard A. Stern; Herman Grütter; David Graham Pearson (Mineralogy and Petrology, 2025)

Species Richness Gradients Vary Across Phylogenetic Scales - Antonin Machac; Allen Hurlbert; Juliano Sarmento Cabral; Felipe O. Cerezer; Cristian S. Dambros; Susanne Fritz; Catherine H. Graham; Oskar Hagen; Florian Hartig; Shan Huang; Mikael Pontarp; David Storch (Global Ecology and Biogeography, 2025)
Aim To determine how species richness gradients—commonly considered universal—vary across the phylogenetic hierarchy of birds and mammals, and to uncover how clade age and size predetermine the gradients. Location Global. Time Period Last 120 million years. Taxa Studied Birds and mammals (~15,000 species). Methods We used large‐scale phylogenies of birds and mammals and captured the species richness gradient for each of their monophyletic clades. Gradient strength was quantified with respect to latitude, environmental productivity and temperature using multiple measures (raw slopes, log transformation, log–log transformation, and correlations). To distinguish statistical from biological effects, we compared the observed gradients to those generated by null models that randomly reassigned species to clades while preserving the phylogeny and species distributions. Results Species richness gradients show considerable variation. Small and young clades exhibited inconsistent gradients—including reverse or flat gradients—while older and larger clades converged on steep, consistent gradients. Even moderately large clades (~500 species) commonly displayed reverse gradients. Null models replicated this trend but only partially, implying that biological effects also drive gradient variation. These phylogenetic trends were sensitive to the choice of gradient measure: raw slopes frequently inflated the strength of this trend and the apparent differences among clades, while log and log–log transformations revealed only moderate trends. Main Conclusions Species richness gradients are not universal, nor are they phylogenetic scale‐invariant. Instead, they follow systematic trends across the phylogenetic hierarchy. Young, small clades often bear signatures of their region of origin and historical dispersal, whereas older, larger clades converge on similar gradients. Recognising the variation and the phylogenetic trends within it elucidates the formation of biodiversity patterns. We offer guidelines for choosing gradient measures, arguing that multiple metrics, combined with careful use of null models, are necessary for a nuanced understanding of how, and why, global biodiversity patterns diverge from the presumed universal gradients.

Changing Interactions Between Trace Gas Fluxes, Belowground Chemistry, and Plant Traits Across an Arctic Thermokarst Landscape - Sean Fettrow; Verity Salmon; Joanne Childs; Benjamin Sulman; David Graham; Colleen M. Iversen; Elizabeth Herndon (Global Change Biology, 2025)
Arctic permafrost soils are increasingly subject to thermokarst that is, abrupt ground subsidence caused by thaw. Wetlands can form within these depressions, leading to changes in organic matter decomposition and gas fluxes (CO 2 , CH 4 , N 2 O, NH 3 ). Thermokarst wetlands tend to be dominated by graminoids, while surrounding upland tussock tundra tends to be dominated by mixed communities of shrubs and graminoids. To investigate how thermokarst alters the land‐atmosphere exchange of C and N gases in Arctic tundra, we analyzed soil, porewater, above‐ and belowground biomass, and measured gas fluxes across dominant plant functional types (PFTs) within a lowland thermokarst wetland and adjacent upland tussock tundra. Both locations were overall sinks of CO 2 , sources of CH 4 , and sources of both N 2 O and NH 3 . We found that thermokarst wetlands emitted enough CH 4 to generate a positive radiative forcing in CO 2 equivalents (+1.2 μmol m −2 s −1 CO 2 ‐eq), counteracting the high CO 2 uptake. In contrast, the upland tussock tundra had a net negative radiative forcing (−1.2 μmol m −2 s −1 CO 2 ‐eq). Differences in gas flux and soil chemistry between upland and lowland are primarily driven by flooded conditions present in thermokarst wetland. Additionally, root biomass from graminoids across both lowlands and uplands significantly correlated with CH 4 fluxes, supporting previous observations of plant‐mediated transport of CH 4 . Graminoid cover was correlated with increases in low molecular weight dissolved organic carbon, possibly associated with root exudates that fuel methanogenesis. Forb cover in the upland tussock tundra was significantly correlated with nine soil chemical variables, indicating that forbs may influence local soil chemistry or conversely, that soil chemistry controls where forbs grow. Overall, our findings indicate the variability in gas fluxes in the upland tussock tundra is partially controlled by PFT cover, while thermokarst wetlands emit enough CH 4 to counteract CO 2 uptake, with implications for carbon budget changes in Arctic systems.

Open problems in ageing science: a roadmap for biogerontology - Angelo Talay; Aleksey V. Belikov; Paul Ka Po To; Hamid H. Alfatemi; Uri Alon; Joris Deelen; Collin Y. Ewald; David Gems; Vera Gorbunova; Jan Gruber; Sara Hägg; John Hemming; et al. (GeroScience, 2025)

Human health risk assessment of toxic metal(loid)s in soils and crops around a Pb Zn mine, Central Iran: Implications of human bioaccessibility and bioavailability to crops - Giti Forghani Tehrani; David A. Rubinos; Afshin Qishlaqi; Margaret C. Graham (Journal of Geochemical Exploration, 2025)

Abundances of elements in global coals - Shifeng Dai; James C. Hower; Robert B. Finkelman; Marina P. Ketris; Yakov E. Yudovich; Yutang Zhang; Jingjing Liu; Changqiu Zhao; Na Xu; Ian T. Graham; David French; Yu Liu; et al. (International Journal of Coal Geology, 2025)

In-situ iron isotope analysis of pyrite from coals: Insights into iron isotope fractionation from dissimilatory iron reduction (DIR) and redox reactions - Mengda Yao; Shifeng Dai; David French; Ian T. Graham; Zhengfu Zhao; Yutang Zhang; Yang Liang; Shuai Kang; Jintian Zheng; Shaowei Zhang (Geochimica et Cosmochimica Acta, 2025)

Can lithium dominantly occur in kaolinite with a high degree of crystallinity in the Carboniferous No. 11 coal from the Xinliangyou mine, Huozhou mining district, southern Shanxi Province, China? - Yan Wang; Shifeng Dai; Yu Liu; David French; Ian Graham; Ning Wang; Jiawei Feng; Niande Shang; Jintian Zheng; Mengda Yao (Chemical Geology, 2025)

Genealogical Analysis of Replicate Flower Colour Hybrid Zones in Antirrhinum - Arka Pal; Daria Shipilina; Alan Le Moan; Adrian J. McNairn; Jennifer K. Grenier; Marek Kucka; Graham Coop; Yingguang Frank Chan; Nicholas H. Barton; David L. Field; Sean Stankowski (Molecular Ecology, 2025)
A major goal of speciation research is identifying loci that underpin barriers to gene flow. Population genomics takes a ‘bottom‐up’ approach, scanning the genome for molecular signatures of processes that drive or maintain divergence. However, interpreting the ‘genomic landscape’ of speciation is complicated, because genome scans conflate multiple processes, most of which are not informative about gene flow. However, studying replicated population contrasts, including multiple incidences of secondary contact, can strengthen inferences. In this paper, we use linked‐read sequencing (haplotagging), F ST scans and genealogical methods to characterise the genomic landscape associated with replicate hybrid zone formation. We studied two flower colour varieties of the common snapdragon, Antirrhinum majus subspecies majus , that form secondary hybrid zones in multiple independent valleys in the Pyrenees. Consistent with past work, we found very low differentiation at one well‐studied zone (Planoles). However, at a second zone (Avellanet), we found stronger differentiation and greater heterogeneity, which we argue is due to differences in the amount of introgression following secondary contact. Topology weighting of genealogical trees identified loci where haplotype diversity was associated with the two snapdragon varieties. Two of the strongest associations were at previously identified flower colour loci: Flavia , that affects yellow pigmentation, and Rosea/Eluta , two linked loci that affect magenta pigmentation. Preliminary analysis of coalescence times provides additional evidence for selective sweeps at these loci and barriers to gene flow. Our study highlights the impact of demographic history on the differentiation landscape, emphasising the need to distinguish between historical divergence and recent introgression.

DNA barcode assessment of Xanthium section Xanthium cockle burrs in Australia - David Gopurenko; Xiaocheng Zhu; R. M. S. P. Rathnayake; Hanwen Wu; Bruce A. Auld; James Hereward; Heather Smith; Stephen B. Johnson; Karen A. Kirkby; Graham W. Charles (Plant Systematics and Evolution, 2025)
Xanthium cockle burrs are invasive weeds in many countries, affecting local ecosystems and agriculture. All Xanthium in Australia are naturalised weeds from multiple overseas sources, but their taxonomic identities are contentious. In particular, species identities of four burr varieties or “complexes” under Xanthium section Xanthium in Australia are unclear. These complexes, commonly referred to as “Noogoora”, “Californian”, “Hunter”, and “South American” burr, are regarded as either varieties of a single species ( Xanthium strumarium ) or four separate species in the section. To genetically determine the species identities of these complexes in Australia, we compared their chloroplast DNA barcodes to reference sequences of vouchered Xanthium species reported by Tomasello (2018). We barcoded 173 plants from 26 sites consisting of single complex burrs and 175 plants from sites containing mixed burr complexes. Single complex sites contained either of two DNA barcode clades. One clade consisting of Noogoora and Californian burrs matched reference sequences of X. chinense . The second clade consisting of Hunter and South American burrs matched X. orientale . Genetic exchange between these two species in Australia was partially evident at some sites containing sympatric complexes or putative hybrids. Reference X. strumarium sequences were unmatched to the DNA barcodes of specimens sampled in Australia, and subsequently, we advise against future claims to a historical presence of this species in Australia. Our findings are significant for taxonomic treatment of Xanthium species in Australia and for consideration of source-specific biological controls of these weeds.

Origin and preservation of Li and Se–Mo–U in Carboniferous-Permian coals from the Jincheng Coalfield, Qinshui basin, Shanxi Province, China - Mengda Yao; Ian T. Graham; Shifeng Dai; David French; Shaowei Zhang; Jintian Zheng; Shuai Kang; Niande Shang; Doudou Li (Applied Geochemistry, 2025)

Progress and gaps in antimicrobial resistance research within One Health sectors in China: a systematic analysis - Cai Chen; Shu-Le Li; Jue Liu; Sabiha Y. Essack; Yi Luo; Mui-Choo Jong; Xiang-Yu Dai; Yao-Yang Xu; Lise Korsten; David W. Graham; Yong-Guan Zhu (Science China Life Sciences, 2025)

Origin of composite fibrous carbonate veins in Middle Jurassic ultra-low-ash coal, Ordos Basin, China: Insights on the interaction between organic carbon and inorganic carbonates after peat burial - Jintian Zheng; Shifeng Dai; Victor P. Nechaev; David French; Ian T. Graham; Na Wang; Pan Yang; Shuai Kang; Mengda Yao; Yang Liang (Applied Geochemistry, 2025)

The University of Oklahoma Inpatient Spine Protocol: optimizing surgical outcomes through standardized perioperative care - David Barkyoumb; William C. Kaiser; Lonnie Smith; Lance M. Villeneuve; Graham Mulvaney; Chao Li; Christopher S. Graffeo; Andrew M. Bauer; Hakeem J. Shakir; Karl Balsara; M. Burhan Janjua; John F. Burke; et al. (GeroScience, 2025)

Decision-making and ecosystem service dimensions of managed dyke realignment in the complex coastal landscapes of the Bay of Fundy - Lara Cornejo; Elson Ian Nyl Ebreo Galang; Kate Sherren; Jeremy Lundholm; Danika van Proosdij; Will Balser; Elena Bennett; Tony M. Bowron; Kirsten Ellis; Jonathan Fowler; Jennifer Graham; Patrick James; et al. (Ocean & Coastal Management, 2025)

Petrogenesis and evolution of Miocene-Quaternary continental basalts at Harrat Ash Shaam (Al Harrah), NW Saudi Arabia - Shelby Bowden; Tanya Furman; David W. Graham; Mansour Alhumimidi; Willis Hames; Ali Assiri; Mazen Alyousif; Ramzi Almutairi; Hamad Alqahtani; Abdurahman Bin Rogaib; Abdulaziz Bin Rushood; Khaled AlYousef; et al. (Lithos, 2025)

Quantification of In Situ Ulnar Nerve Strain and Constraint Tension in the Forearm - Mark Carl Miller; Patrick J. Schimoler; Harsh Shah; Alexander Kharlamov; R. David Graham; Carol Armstrong; Andrew Wroblewski; Yue Yin; Peter Tang (Annals of Biomedical Engineering, 2025)

The use of data for health and welfare management of farmed salmons in Norway, Scotland, and Ireland - Xiao Zhou; Annette S. Boerlage; Britt Bang Jensen; Kristine Gismervik; Victor H.S. Oliveira; Ian Hutchinson; Alison Burrell; David A. Graham; Charlotte Doidge; Jasmeet Kaler; Gerdien van Schaik; Michael Siegrist; et al. (Preventive Veterinary Medicine, 2025)

Near surface lithium isotopic fractionation and lithium enrichment in coal-hosted Li-rich clays from the South China Block - Rongjie Wang; Shifeng Dai; David French; Ian T. Graham; Victor P. Nechaev; Robert B. Finkelman (International Journal of Coal Geology, 2025)

A phytol εp-based core-top calibration to reconstruct past changes in atmospheric CO2 - Olivia A. Graham; Caitlyn R. Witkowski; Mark A. Stevenson; Francien Peterse; B. David A. Naafs (Geochimica et Cosmochimica Acta, 2025)

Impact of indigenous vs. cultivated microalgae strains on biomass accumulation, microbial community composition, and nutrient removal in algae-based dairy wastewater treatment - KhinKhin Phyu; Suli Zhi; David W. Graham; Yuang Cao; Xiaoyu Xu; Jiahua Liu; Han Wang; Keqiang Zhang (Bioresource Technology, 2025)

Towards an ecological metaphor for regenerative circular economies - Filippos K. Zisopoulos; Brian D. Fath; Bruno Meirelles de Oliveira; Susana Toboso-Chavero; Hugo D'Assenza-David; Vitor Miranda de Souza; Hao Huang; Şerban Scrieciu; O. Grant Clark; Dominik Noll; Simron Singh; Alexandros Stefanakis; et al. (Ecological Economics, 2025)

Role of earthworms and their excretion products in reducing antimicrobial resistance and putative pathogens during vermicomposting - Ning Liu; David W. Graham; Yi Zhao; Xiao-Ru Yang; Gang Li; Yong-Guan Zhu (Chemical Engineering Journal, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Extreme enriched-mantle (EM) compositions recorded by the Sr-Nd-Hf isotopes of global cratonic lamproites - Soumendu Sarkar; Hayden Dalton; Andrea Giuliani; David Phillips; D. Graham Pearson; Geoff M. Nowell; Jon D. Woodhead; Janet Hergt; Roland Maas; A. Lynton Jaques; N.V. Chalapathi Rao; Yaakov Weiss; et al. (Geochimica et Cosmochimica Acta, 2025)

Conservation genetics of Stylophorum diphyllum (Papaveraceae): investigating the genetic diversity and differentiation of peripheral and core populations across the range - Linda A. Lait; Brendan A. Graham; David A. Galbraith; Theresa M. Burg; J. L. McCune (Conservation Genetics, 2025)

How much seagrass does a dugong need? Metabolic rate of live wild dugongs, Dugong dugon , determined through indirect calorimetry (oxygen consumption) - Janet M. Lanyon; Helen L. Sneath; Trevor Long; Wendy H. Blanshard; Graham A. J. Worthy; David T. Booth (Marine Mammal Science, 2025)
Deterioration of seagrass beds worldwide has raised concern about the future of dugongs because almost all aspects of their life history depend on availability of seagrass. Understanding their energy metabolism and consequently how much seagrass they need will inform protective conservation strategies for dugongs. This study determined resting metabolic rate (RMR) in five wild‐caught adult dugongs by measuring oxygen consumption (O 2 ). Measurement conditions met assumptions for RMR, except that dugongs were not postabsorptive, thus a postprandial (pp) allometric equation for herbivorous mammals of similar size was used to predict an expected RMR pp for dugongs of known mass. O 2 was measured for 30 min in a metabolic tank after brief habituation. Dugongs' RMR pp was approximately half that predicted for their body mass but was higher than for manatees. Based on dugongs' RMR pp and considering plant caloric and water content, the daily minimum intake of fresh weight seagrass was 40–65 kg Halophila ovalis , or 20–40 kg Halodule spp. Greater seagrass intake would be required for growing and reproducing dugongs. Slow growth and protracted reproductive rates of dugongs are likely related to limitations in seagrass energy and nutrients. To ensure viability of this vulnerable species, it is critically important to conserve extensive healthy seagrass beds.

Latitudinal gradients in herbivorous and detritivorous reef fish productivity - Sterling B. Tebbett; Helen F. Yan; Scott Bennett; Graham J. Edgar; Scott D. Ling; Rick D. Stuart-Smith; David R. Bellwood (Reviews in Fish Biology and Fisheries, 2025)

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Designing a monitoring plan for microbial water quality and waterborne antimicrobial resistance in the Akaki catchment, Ethiopia - Alemseged Tamiru Haile; Mulugeta Kibret; Mihret Mersha Haileselassie; Kominist Asmamaw Anley; Tilaye Worku Bekele; Jemila Mohammed Kassa; Kirubel Demissie; David Werner; David Graham; Javier Mateo-Sagasta (Environmental Monitoring and Assessment, 2025)

Exposed and Vulnerable: Sources and Health Implications of Chemical Exposures in Neonatal, Pediatric, and Cardiac Intensive Care Units - Jordan R. Kuiper; Melania Bembea; J. William Gaynor; David Graham; Eric M. Graham; Kurunthachalam Kannan; Nikki G. Posnack; Allen D. Everett; Jessie P. Buckley (Current Environmental Health Reports, 2025)

Managing wilding pines in the Cape Floristic Region, South Africa: Progress and prospects - Grant Martin; Kim Canavan; Gerald Chikowore; Richard Bugan; Willem De Lange; Ben du Toit; Graham Harding; Ronald Heath; Martin Hill; Brett P. Hurley; Philip Ivey; Debbie Muir; et al. (South African Journal of Botany, 2025)

Control of N-nitrosamine impurities in drug products: Progressing the current CPCA framework and supporting the derivation of robust compound specific acceptable intakes - David J. Ponting; Andreas Czich; Susan P. Felter; Susanne Glowienke; James S. Harvey; Raphael Nudelman; Joerg Schlingemann; Stephanie Simon; Graham F. Smith; Andrew Teasdale; Robert Thomas (Regulatory Toxicology and Pharmacology, 2025)

Multi-stage hydrothermal activity affecting the early Jurassic K7 coal seam from the Gaosheng coal Mine, Sichuan Basin, southwest China: Evidence from whole-rock geochemistry and C-O-Sr isotopes in authigenic carbonates - Rongjie Wang; Shifeng Dai; Baruch F. Spiro; Victor P. Nechaev; David French; Ian T. Graham; Mingxuan Zhou; Jingjing Liu; Shaobo Di; Xiao Tian (Journal of Asian Earth Sciences, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

An mTOR inhibitor discovery system using drug-sensitized yeast - Anna K. Breen; Sarah Thomas; David Beckett; Matthew Agsalud; Graham Gingras; Judd Williams; Brian M. Wasko (GeroScience, 2025)
Inhibition of the target of rapamycin (TOR/mTOR) protein kinase by the drug rapamycin extends lifespan and health span across diverse species. However, rapamycin has potential off-target and side effects that warrant the discovery of additional TOR inhibitors. TOR was initially discovered in Saccharomyces cerevisiae (yeast) which contains two TOR paralogs, TOR1 and TOR2 . Yeast lacking functional Tor1 are viable but are hypersensitive to growth inhibition by TORC1 inhibitors, which is a property of yeast that can be exploited to identify TOR inhibitors. Additionally, yeast lacking FK506-sensitive proline rotamase ( FPR1 ) or containing a tor1-1 allele (a mutation in the Fpr1-rapamycin binding domain of Tor1) are robustly and selectively resistant to rapamycin and analogs that allosterically inhibit TOR activity via an FPR1 -dependent mechanism. To facilitate the identification of TOR inhibitors, we generated a panel of yeast strains with mutations in TOR pathway genes combined with the removal of 12 additional genes involved in drug efflux. This creates a drug-sensitive strain background that can sensitively and effectively identify TOR inhibitors. In a wild-type yeast strain background, 25 µM of Torin1 and 100 µM of GSK2126458 (omipalisib) are necessary to observe TOR1 -dependent growth inhibition by these known TOR inhibitors. In contrast, 100 nM Torin1 and 500 nM GSK2126458 (omipalisib) are sufficient to identify TOR1- dependent growth inhibition in the drug-sensitized background. This represents a 200-fold and 250-fold increase in detection sensitivity for Torin1 and GSK2126458, respectively. Additionally, for the TOR inhibitor AZD8055, the drug-sensitive system resolves that the compound results in TOR1- dependent growth sensitivity at 100 µM, whereas no growth inhibition is observed in a wild-type yeast strain background. Our platform also identifies the caffeine analog aminophylline as a TOR1 -dependent growth inhibitor via selective tor1 growth sensitivity. We also tested nebivolol, isoliquiritigenin, canagliflozin, withaferin A, ganoderic acid A, and taurine and found no evidence for TOR inhibition using our yeast growth-based model. Our results demonstrate that this system is highly effective at identifying compounds that inhibit the TOR pathway. It offers a rapid, cost-efficient, and sensitive tool for drug discovery, with the potential to expedite the identification of new TOR inhibitors that could serve as geroprotective and/or anti-cancer agents.

The Pb, Sr and Nd isotopic composition of the upper continental crust: An Australian perspective - Candan U. Desem; Jon Woodhead; Patrice de Caritat; Roland Maas; David C. Champion; Anthony Dosseto; Ashlea Wainwright; Graham Carr (Chemical Geology, 2025)

Analyzing Archive Transit Multibeam Data for Nodule Occurrences - Mark E. Mussett; David F. Naar; David W. Caress; Tracey A. Conrad; Alastair G. C. Graham; Max Kaufmann; Marcia Maia (Journal of Marine Science and Engineering, 2024)
We show that analyzing archived and future multibeam backscatter and bathymetry data, in tandem with regional environmental parameters, can help to identify polymetallic nodule fields in the world’s oceans. Extensive archived multibeam transit data through remote areas of the world’s oceans are available for data mining. New multibeam data will be made available through the Seabed 2030 Project. Uniformity of along- and across-track backscatter, backscatter intensity, angular response, water depth, nearby ground-truth data, local slope, sedimentation rate, and seafloor age provide thresholds for discriminating areas that are permissive to nodule presence. A case study of this methodology is presented, using archived multibeam data from a remote section of the South Pacific along the Foundation Seamounts between the Selkirk paleomicroplate and East Pacific Rise, that were collected during the 1997 Foundation–Hotline expedition on R/V Atalante. The 12 kHz Simrad EM12D multibeam data and the other forementioned data strongly suggest that a previously unknown nodule occurrence exists along the expedition transit. We also compare the utility of three different backscatter products to demonstrate that scans of printed backscatter maps can be a useful substitute for digital backscatter mosaics calculated using primary multibeam data files. We show that this expeditious analysis of legacy multibeam data could characterize benthic habitat types efficiently in remote deep-ocean areas, prior to more time-consuming and expensive video and sample acquisition surveys. Additionally, utilizing software other than specialty sonar processing programs during this research allows an exploration of how multibeam data products could be interrogated by a broader range of scientists and data users. Future mapping, video, and sampling cruises in this area would test our prediction and investigate how far it might extend to the north and south.

Evaluating the effectiveness & costs of strategies post-eradication to monitor for freedom from BVDV infection in Ireland - Jonas Brock; Maria Guelbenzu-Gonzalo; Martin Lange; Jamie A. Tratalos; Damien Barrett; Liz Lane; Simon J. More; David A. Graham; Hans-Hermann Thulke (Agricultural Systems, 2024)

Unifying Coral Reef States Through Space and Time Reveals a Changing Ecosystem - Simon J. Brandl; Jérémy Carlot; Rick D. Stuart‐Smith; Sally A. Keith; Nicholas A. J. Graham; Graham J. Edgar; Jérémy Wicquart; Shaun K. Wilson; Rucha Karkarey; Mary K. Donovan; Jesus E. Arias‐Gonzalez; Rohan Arthur; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological state shifts that alter the structure and function of entire ecosystems are a concerning consequence of human impact. Yet, when, where and why discrete ecological states emerge remains difficult to predict and monitor, especially in high‐diversity systems. We sought to quantify state shifts and their drivers through space and time in the most ecologically complex marine ecosystem: tropical coral reefs. Location Worldwide. Time Period 1987–2019. Major Taxa Studied Coral reef communities. Methods Using a global dataset of 3375 coral reef surveys, along with 13 time series datasets ranging between 1987 and 2019, we applied a novel double‐dichotomy approach to classify coral reefs into four simplified and discrete states based on the relative contributions of corals versus algae to benthic cover and small‐bodied versus large‐bodied fishes to fish standing stock. We then examined state shifts considering a range of spatial predictors and tested whether states have shifted directionally over time, and the nature of the most common transitions. Results We show that geographic, environmental and anthropogenic context fundamentally shapes coral reef states at the local scale, which explains disparities among case studies, and stakes out critical baseline expectations for regional management efforts. We also reveal clear multi‐decadal state shifts on coral reefs: over time, systems dominated by reef‐building corals and small‐bodied, planktivorous fishes tend to have been replaced with reefs characterised by algae and larger‐bodied fishes. Main Conclusions Our results suggest a previously unrecognised transition from systems that harness external subsidies through small‐bodied consumers associated with structurally complex live corals, to herbivore‐dominated systems with stronger bottom‐up dynamics. Overall, the partitioning of complex reef ecosystems into a small suite of discrete ecological states suggests that spatial context‐dependency, shifting baselines and changes in reef functioning are crucial considerations for coral reef management in the 21st century.

Revisiting sustainable resources in the combustion products of alumina-rich coal: Critical metal (Li, Ga, Nb, and REY) potential of ash from the Togtoh Power Plant, Inner Mongolia, China - Yanmin Zheng; Lei Zhao; David French; Ian Graham; Qiang Wei; Shifeng Dai; Lili Feng (Science of The Total Environment, 2024)

Practical non-stationary extreme value analysis of peaks over threshold using the generalised Pareto distribution: Estimating uncertainties in return values - Stan Tendijck; David Randell; Graham Feld; Philip Jonathan (Ocean Engineering, 2024)

Fungal membrane determinants affecting sensitivity to antifungal cyclic lipopeptides from Bacillus spp. - Charlotte Bakker; Hailey R. Graham; Irina Popescu; Melody Li; David R. McMullin; Tyler J. Avis (Fungal Biology, 2024)

Streamflow timing and magnitude during snow drought depend on snow drought type and regional hydroclimate - John Hammond; Annie Putman; Theodore Barnhart; Graham Sexstone; Gregory McCabe; David Wolock; Aaron Heldmyer; Stephanie Kampf (Hydrological Sciences Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Microplastic-induced hepatic adverse effects evaluated in advanced quadruple cell human primary models following three weeks of repeated exposure - Asha Guraka; Graham Souch; Richard Duff; David Brown; Wolfgang Moritz; Ali Kermanizadeh (Chemosphere, 2024)

Individual variability and consistency of post-exercise energy and macronutrient intake, appetite sensations, and food reward in healthy adults - Léna Pélissier; Céline Lambert; David J. Stensel; Duane Beraud; Graham Finlayson; Bruno Pereira; Yves Boirie; Martine Duclos; Laurie Isacco; David Thivel (Appetite, 2024)

Reward for fat and sweet dimensions of food are altered by an acute bout of running in healthy young men - Yoshiki Yamada; Ayano Hiratsu; David Thivel; Kristine Beaulieu; Graham Finlayson; Chihiro Nagayama; Kayoko Kamemoto; Sirikul Siripiyavatana; Yusei Tataka; Miki Sakazaki; Masashi Miyashita (Appetite, 2024)

Transformation of organic to inorganic nitrogen in NH4+-illite-bearing and Ga-Al-REE-rich bituminous coals: Evidence from nitrogen isotopes and functionalities - Qian Wang; Shifeng Dai; Victor P. Nechaev; David French; Ian Graham; Lei Zhao; Shaowei Zhang; Yang Liang; James C. Hower (Chemical Geology, 2024)

Identifying leverage points for sustainable nutrient policy integration in Canada - Sibeal McCourt; David Kanter; Graham K. MacDonald (Ambio, 2024)

Southern Flounder: Major Milestones and Remaining Knowledge Gaps in Their Biology, Ecology, and Fishery Management - Stephen R. Midway; Frederick S. Scharf; Michael A. Dance; Nancy J. Brown-Peterson; Joseph C. Ballenger; Nicolette S. Beeken; Russell J. Borski; Tanya L. Darden; Kenneth A. Erickson; Troy M. Farmer; Ashley Fincannon; John Godwin; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Detection of mpox virus in wastewater provides forewarning of clinical cases in Canadian cities - Edgard M. Mejia; Nikho A. Hizon; Codey E. Dueck; Ravinder Lidder; Jade Daigle; Quinn Wonitowy; Nestor G. Medina; Umar P. Mohammed; Graham W. Cox; David Safronetz; Mable Hagan; Jim Strong; et al. (Science of The Total Environment, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Masculine voice is associated with better mucosal immune defense in adolescent and adult males - Carolyn R. Hodges-Simeon; Graham Albert; Timothy McHale; Steven J.C. Gaulin; Michael Gurven; Nick Landry; Jessica K. Hlay; Nicole Merullo; David A. Puts; Steven A. Arnocky (Evolution and Human Behavior, 2024)

Is hyperaccumulation a viable hypothesis for organic associations of minor elements in coals? - James C. Hower; Maheteme Gebremedhin; Demetrio P. Zourarakis; Robert B. Finkelman; David French; Ian T. Graham; Harold H. Schobert; Lei Zhao; Shifeng Dai (Earth-Science Reviews, 2024)

Antimicrobial resistance in rural rivers: Comparative study of the Coquet (Northumberland) and Eden (Cumbria) River catchments - Katie Robins; Greg O'Donnell; Anke Neumann; Wiebke Schmidt; Alwyn Hart; David W. Graham (Science of The Total Environment, 2024)

A multi-methods, multi-actor exploration of the benefits and barriers to milk recording on Irish farms using the COM-B model - Alison MG Burrell; Lorraine Balaine; Seán Clifford; Michelle McGrath; David A. Graham; Finola McCoy; Emma Dillon; Áine Regan (Preventive Veterinary Medicine, 2024)

Lamb meat colour is minimally affected under reduced oxygen concentration in modified atmosphere packaging - Maddison T. Corlett; David W. Pethick; Khama R. Kelman; Robin H. Jacob; Liselotte Pannier; Ihab Habib; Graham E. Gardner (Food Packaging and Shelf Life, 2024)

Effects of dairy farming management practices on carbon balances in New Zealand’s grazed grasslands: Synthesis from 68 site-years - Aaron M. Wall; Johannes Laubach; David I. Campbell; Jordan P. Goodrich; Scott L. Graham; John E. Hunt; Paul L. Mudge; David Whitehead; Louis A. Schipper (Agriculture, Ecosystems & Environment, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Methane emissions from animal agriculture: Micrometeorological solutions for challenging measurement situations - Johannes Laubach; Thomas K. Flesch; Christof Ammann; Mei Bai; Zhiling Gao; Lutz Merbold; David I. Campbell; Jordan P. Goodrich; Scott L. Graham; John E. Hunt; Aaron M. Wall; Louis A. Schipper (Agricultural and Forest Meteorology, 2024)

Post-exercise energy replacement might lead to reduced subsequent energy intake in women with constitutional thinness: Exploratory results from the NUTRILEAN project - Audrey Boscaro; Mélina Bailly; Bruno Pereira; Duane Beraud; Frédéric Costes; Valérie Julian; Martine Duclos; Graham Finlayson; David Thivel; Yves Boirie; Julien Verney (Appetite, 2024)

Differences in neuroinflammation in people who started antiretroviral treatment during primary versus chronic HIV infection: an 18kDa Translocator protein (TSPO) positron emission tomography (PET) study - Jasmini Alagaratnam; John P. Thornhill; Zhen Fan; Jaime H. Vera; Jonathan Underwood; Rebecca Hall; Graham Searle; David Owen; Paul Edison; Sarah Fidler; Alan Winston (Journal of NeuroVirology, 2024)
Persistent inflammation is described in people with HIV (PWH) on antiretroviral treatment (ART). Early ART initiation is associated with reduced inflammation. We aimed to evaluate neuroinflammation, using translocator protein (TSPO) [ 11 C]PBR28 PET neuroimaging in PWH who initiated ART during acute HIV (aPWH) versus chronic HIV infection (cPWH) versus a control population. This was a cross-sectional, observational study. All participants underwent [ 11 C]PBR28 PET-CT neuroimaging. Using a two-tissue compartment model, total volume of distribution (V T ) and distribution volume ratios (DVR) using cortical grey matter as a pseudo-reference region at 20 regions of interest (ROIs) were calculated. Differences in V T and DVR were compared between groups using the Kruskall-Wallis test. Seventeen neuro-asymptomatic male PWH on ART (9 aPWH, 8 cPWH) and 8 male control participants (CPs) were included. Median (interquartile range, IQR) age was 40 (30, 46), 44 (41, 47) and 21 (20, 25) years in aPWH, cPWH and CPs, respectively. Median (IQR) CD4 (cells/µL) and CD4:CD8 were 687 (652, 1014) and 1.37 (1.24, 1.42), and 700 (500, 720) and 0.67 (0.64, 0.82) in aPWH and cPWH, respectively. Overall, no significant difference in V T and DVR were observed between the three groups at any ROIs. cPWH demonstrated a trend towards higher mean V T compared with aPWH and CPs at most ROIs. No significant differences in neuroinflammation, using [ 11 C]PBR28 binding as a proxy, were identified between cPWH, aPWH and CPs. A trend towards lower absolute [ 11 C]PBR28 binding was seen amongst aPWH and CPs, suggesting early ART may mitigate neuroinflammation.

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

Detrital U Pb zircon geochronology, zircon Lu Hf and Sr Nd isotopic signatures of the Lopingian volcanic-ash-derived Nb-Zr-REY-Ga mineralized horizons from eastern Yunnan, SW China - Ning Wang; Shifeng Dai; Victor P. Nechaev; David French; Ian T. Graham; Xiaolin Song; Igor Yu. Chekryzhov; Irina A. Tarasenko; Sergey Y. Budnitskiy (Lithos, 2024)

Diamond sources of the Juína region, Amazonian craton: textural and mineral chemical characteristics of Kimberley-type pyroclastic kimberlites - Izaac Cabral-Neto; Excelso Ruberti; David Graham Pearson; Yan Luo; Rogério G. Azzone; Francisco V. Silveira; Vidyã V. Almeida (Mineralogy and Petrology, 2024)

Rarity mediates species‐specific responses of tropical reef fishes to protection - Loïc Sanchez; Nicolas Loiseau; Graham J. Edgar; Cyril Hautecoeur; Fabien Leprieur; Stéphanie Manel; Matthew McLean; Rick D. Stuart‐Smith; Laure Velez; David Mouillot (Ecology Letters, 2024)
Marine protected areas (MPAs) are the most widely applied tool for marine biodiversity conservation, yet many gaps remain in our understanding of their species‐specific effects, partly because the socio‐environmental context and spatial autocorrelation may blur and bias perceived conservation outcomes. Based on a large data set of nearly 3000 marine fish surveys spanning all tropical regions of the world, we build spatially explicit models for 658 fish species to estimate species‐specific responses to protection while controlling for the environmental, habitat and socio‐economic contexts experienced across their geographic ranges. We show that the species responses are highly variable, with ~40% of fishes not benefitting from protection. When investigating how traits influence species' responses, we find that rare top‐predators and small herbivores benefit the most from MPAs while mid‐trophic level species benefit to a lesser extent, and rare large herbivores experience adverse effects, indicating potential trophic cascades.

ELSSIE: A compact stereo spectral imager for planetary surface morphology and composition - Scott L. Murchie; Frank P. Seelos; Bethany L. Ehlmann; John D. Boldt; Lawrence E. Brown; Jacob M. Greenberg; Karl A. Hibbitts; W. Jeffrey Lees; David M. Linko; Joseph J. Linden; Graham P. Murphy; Jorge I. Núñez; et al. (Planetary and Space Science, 2024)

Quaternary ammonium salt coated air filter for bioaerosol removal from building indoor air - Huixin Jiang; Kai Li; David E. Graham; Attelia Hollander; Mariappan P. Paranthaman; M. Muneeshwaran; Xiaoli Liu; Merlin Theodore; Tolga Aytug; Keju An; Kashif Nawaz (Building and Environment, 2024)

Towards global traceability for sustainable cephalopod seafood - Ian G. Gleadall; Hassan Moustahfid; Warwick H. H. Sauer; Lahsen Ababouch; Alexander I. Arkhipkin; Jilali Bensbai; Isa Elegbede; Abdelmalek Faraj; Pedro Ferreiro-Velasco; Roberto González-Gómez; Carmen González-Vallés; Unai Markaida; et al. (Marine Biology, 2024)

Prediction of solar energetic events impacting space weather conditions - Manolis K. Georgoulis; Stephanie L. Yardley; Jordan A. Guerra; Sophie A. Murray; Azim Ahmadzadeh; Anastasios Anastasiadis; Rafal Angryk; Berkay Aydin; Dipankar Banerjee; Graham Barnes; Alessandro Bemporad; Federico Benvenuto; et al. (Advances in Space Research, 2024)

New supporting data to guide the use of evident toxicity in acute oral toxicity studies (OECD TG 420) - Fiona Sewell; Ian Ragan; Graham Horgan; David Andrew; Thomas Holmes; Irene Manou; Boris P. Müller; Tim Rowan; Barbara G. Schmitt; Marco Corvaro (Regulatory Toxicology and Pharmacology, 2024)

Fate and transport modelling for evaluating antibiotic resistance in aquatic environments: Current knowledge and research priorities - Mahesh Jampani; Javier Mateo-Sagasta; Aparna Chandrasekar; Despo Fatta-Kassinos; David W. Graham; Ritu Gothwal; Arshnee Moodley; Vishnumurthy Mohan Chadag; David Wiberg; Simon Langan (Journal of Hazardous Materials, 2024)

Too much too soon? Risk factors for fear behaviour in foster kittens prior to adoption - Courtney Graham; David L. Pearl; Lee Niel (Applied Animal Behaviour Science, 2024)

The energy content of meals with a similar macronutrient distribution may have a greater impact on appetite sensations than food preferences in adolescents with obesity: A secondary analysis - Halim Moore; Julie Siroux; Bruno Pereira; Maud Miguet; Alicia Fillon; Celine Dionnet; Valérie Julian; Martine Duclos; Yves Boirie; Graham Finlayson; Laurie Isacco; David Thivel (Appetite, 2023)

Characterisation of typical enteropathogenic Escherichia coli (tEPEC) lineages and novel bfpA variants detected in Australian fruit bats (Pteropus poliocephalus) - Fiona McDougall; David Gordon; Roy Robins-Browne; Vicki Bennett-Wood; Wayne S.J. Boardman; Petra L. Graham; Michelle Power (Science of The Total Environment, 2023)

Early Eocene Arctic volcanism from carbonate-metasomatized mantle - James M. D. Day; D. Graham Pearson; Bruce A. Kjarsgaard; Abigail K. Barker; Geoff M. Nowell; Nancy Joyce; David Lowry; Chiranjeeb Sarkar; Christopher Harrison (Contributions to Mineralogy and Petrology, 2023)
Melilitite, nephelinite, basanite, and alkali basalt, along with phonolite differentiates, form the Freemans Cove Complex (FCC) in the south-eastern extremity of Bathurst Island (Nunavut, Canada). New 40 Ar/ 39 Ar chronology indicates their emplacement between ~ 56 and ~ 54 million years ago within a localized extensional structure. Melilitites and nephelinites, along with phonolite differentiates, likely relate to the beginning and end phases of extension, whereas alkali basalts were emplaced during a main extensional episode at ~ 55 Ma. The melilitites, nephelinites, and alkali basalts show no strong evidence for significant assimilation of crust, in contrast to some phonolites. Partial melting occurred within both the garnet- and spinel-facies mantle and sampled sources with He, O, Nd, Hf, and Os isotope characteristics indicative of peridotite with two distinct components. The first, expressed in higher degree partial melts, represents a relatively depleted component (“A”; 3 He/ 4 He ~ 8 R A , ε Nd i ~ + 3 ε Hf i ~ + 7, γ Os i ~ 0). The second was an enriched component (“B” 3 He/ 4 He < 3 R A , ε Nd i < – 1 ε Hf i < + 3, γ Os i > + 70) sampled by the lowest degree partial melts and represents carbonate-metasomatized peridotite. Magmatism in the FCC shows that rifting extended from the Labrador Sea to Bathurst Island and reached a zenith at ~ 55 Ma, during the Eurekan orogeny. The incompatible trace-element abundances and isotopic signatures of FCC rocks indicate melt generation occurred at the base of relatively thin lithosphere at the margin of a thick craton, with no mantle plume influence. FCC melt compositions are distinct from other continental rift magmatic provinces worldwide, and their metasomatized mantle source was plausibly formed synchronously with emplacement of Cretaceous kimberlites. The FCC illustrates that the range of isotopic compositions preserved in continental rift magmas are likely to be dominated by temporal changes in the extent of partial melting, as well as by the timing and degree of metasomatism recorded in the underlying continental lithosphere.

Effects of management objectives and rules on marine conservation outcomes - Natalie C. Ban; Emily S. Darling; Georgina G. Gurney; Whitney Friedman; Stacy D. Jupiter; W. Peni Lestari; Irfan Yulianto; Sinta Pardede; Sukma A. R. Tarigan; Puji Prihatiningsih; Sangeeta Mangubhai; Waisea Naisilisili; et al. (Conservation Biology, 2023)
Understanding the relative effectiveness and enabling conditions of different area‐based management tools is essential for supporting efforts that achieve positive biodiversity outcomes as area‐based conservation coverage increases to meet newly set international targets. We used data from a coastal social–ecological monitoring program in 6 Indo‐Pacific countries to analyze whether social, ecological, and economic objectives and specific management rules (temporal closures, fishing gear‐specific, species‐specific restrictions) were associated with coral reef fish biomass above sustainable yield levels across different types of area‐based management tools (i.e., comparing those designated as marine protected areas [MPAs] with other types of area‐based management). All categories of objectives, multiple combinations of rules, and all types of area‐based management had some sites that were able to sustain high levels of reef fish biomass—a key measure for coral reef functioning—compared with reference sites with no area‐based management. Yet, the same management types also had sites with low biomass. As governments advance their commitments to the Kunming–Montreal Global Biodiversity Framework and the target to conserve 30% of the planet's land and oceans by 2030, we found that although different types of management can be effective, most of the managed areas in our study regions did not meet criteria for effectiveness. These findings underscore the importance of strong management and governance of managed areas and the need to measure the ecological impact of area‐based management rather than counting areas because of their designation.

Response of wastewater-based epidemiology predictor for the second wave of COVID-19 in Ahmedabad, India: A long-term data Perspective - Manish Kumar; Madhvi Joshi; Guangming Jiang; Rintaro Yamada; Ryo Honda; Vaibhav Srivastava; Jürgen Mahlknecht; Damia Barcelo; Sabarathinam Chidambram; Anwar Khursheed; David W Graham; Ritusmita Goswami; et al. (Environmental Pollution, 2023)

Green and gold kiwifruit powders consumed for 28 days by healthy individuals with occasional constipation are safe and well-tolerated: A randomized controlled trial - Erin D. Lewis; David C. Crowley; Rupal Trivedi; Thomas Wolever; Mary Ann Buggia; Emma Graham; Starin McKeen; Jennifer Gu; Doug Rosendale; Malkanthi Evans (Bioactive Carbohydrates and Dietary Fibre, 2023)

Why humans kill animals and why we cannot avoid it - Benjamin L. Allen; Christopher Bobier; Stuart Dawson; Peter J.S. Fleming; Jordan Hampton; David Jachowski; Graham I.H. Kerley; John D.C. Linnell; Kelly Marnewick; Liaan Minnie; Mike Muthersbaugh; M. Justin O'Riain; et al. (Science of The Total Environment, 2023)

Future climate change-related decreases in food quality may affect juvenile Chinook salmon growth and survival - Jessica Garzke; Ian Forster; Caroline Graham; David Costalago; Brian P.V. Hunt (Marine Environmental Research, 2023)

Geochemical and mineralogical evidence for the formation of siderite in Late Permian coal-bearing strata from western Guizhou, SW China - Minglian Shen; Shifeng Dai; David French; Ian T. Graham; Baruch F. Spiro; Na Wang; Xiao Tian (Chemical Geology, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

An innovative passive sampling approach for the detection of cyanobacterial gene targets in freshwater sources - David J. Redden; Toni Stanhope; Lindsay E. Anderson; Jessica Campbell; Wendy H. Krkošek; Graham A. Gagnon (Science of The Total Environment, 2023)

Origin of chamosite and berthierine: Implications for volcanic-ash-derived Nb-Zr-REY-Ga mineralization in the Lopingian sequences from eastern Yunnan, SW China - Ning Wang; David French; Shifeng Dai; Ian T. Graham; Lei Zhao; Xiaolin Song; Jintian Zheng; Yan Gao; Yan Wang (Journal of Asian Earth Sciences, 2023)

Co-designing a multi-criteria approach to ranking hazards to and from Australia’s emerging offshore blue economy - Mischa P. Turschwell; Christopher J. Brown; Myriam Lacharité; Jess Melbourne-Thomas; Keith R. Hayes; Rodrigo H. Bustamante; Jeffrey M. Dambacher; Karen Evans; Pedro Fidelman; Darla Hatton MacDonald; Ingrid Van Putten; Graham Wood; et al. (Environmental Science & Policy, 2023)

Carbon isotope composition of basalts from Loihi Seamount: Primordial or recycled carbon in the Hawaiian mantle plume? - David W. Graham; Peter J. Michael; Thi B. Truong (Earth and Planetary Science Letters, 2023)

Canada and ocean climate adaptation: tracking law and policy responses, charting future directions - David L. VanderZwaag; Sara L. Seck; Laura Graham; Jonathon Frontain; Kieran Simpson (Frontiers in Marine Science, 2023)
This research article provides a law and policy summary of climate change adaptation initiatives in Canada at the ocean-climate nexus. Three levels of governance are examined (national, provincial, and Indigenous) with a focus on the Atlantic region. The research method was the review of relevant and newly amended laws, regulations and policy statements, and related commentaries. The roles of the federal government are first described with key developments including the launch of a Climate Adaptation Platform in 2012 to share adaptation experiences and information and release of a National Adaptation Strategy and accompanying Adaptation Action Plan in November 2022. Federal adaptation efforts in the areas of fisheries, aquaculture and shipping are also reviewed along with progress in establishing marine protected areas (MPAs) and other effective area-based conservation measures. Provincial adaptation initiatives are next summarized with a focus on the four Atlantic provinces. Those provinces have established a regional hub, CLIMAtlantic, to provide climate information and advance climate-related research and training. Each province has developed a climate action plan which includes climate adaptation priorities. Indigenous-led climate engagement and adaptation initiatives are finally described including the publication in 2019 of a National Inuit Climate Change Strategy , regional initiatives of the Atlantic Policy Congress of First Nations Chiefs Secretariat, and the development of climate adaptation plans by select First Nation communities in the Atlantic region. The paper concludes by discussing future law and policy directions to make Canada more “climate ready.” Adoption of climate adaptation strategies for governmental departments and agencies with ocean and coastal responsibilities should be a priority. Incorporating climate change adaptation responsibilities through legislative and regulatory changes also needs to be considered, for example, by amending Canada’s Oceans Act to recognize the role of oceans in climate adaptations and mitigation, to authorize the designation of MPAs as climate refuges and to require adaptive and dynamic MPA management plans through strict monitoring and timely review provisions. Indigenous peoples must be effectively included in all climate adaptation discussions and planning.

Sea temperature influences accumulation of tetrodotoxin in British bivalve shellfish - Monika Dhanji-Rapkova; Mickael Teixeira Alves; Joaquin A. Triñanes; Jaime Martinez-Urtaza; David Haverson; Kirsty Bradley; Craig Baker-Austin; Jim F. Huggett; Graham Stewart; Jennifer M. Ritchie; Andrew D. Turner (Science of The Total Environment, 2023)

Hydrothermally-altered coal from the Daqingshan Coalfield, Inner Mongolia, northern China: Evidence from stable isotopes of C within organic matter and C-O-Sr in associated carbonates - Qian Wang; Shifeng Dai; David French; Baruch Spiro; Ian Graham; Jingjing Liu (International Journal of Coal Geology, 2023)

Absence of low-δ18O magmas despite widespread assimilation of altered crust in a large magmatic and hydrothermal province - Shane M. Rooyakkers; Isabelle Chambefort; Kevin Faure; Colin J.N. Wilson; Simon J. Barker; Nick Mortimer; Hannah C. Elms; Juliana Troch; Bruce L.A. Charlier; Graham S. Leonard; David Farsky (Geochimica et Cosmochimica Acta, 2023)

Non-asbestiform elongate mineral particles and mesothelioma risk: Human and experimental evidence - Julie E. Goodman; Michael J. Becich; David M. Bernstein; Bruce W. Case; Jeffrey H. Mandel; Andre E. Nel; Robert Nolan; Nnaemeka U. Odo; Steven R. Smith; Emanuela Taioli; Graham Gibbs (Environmental Research, 2023)

Forester and Logger Response to Emerald Ash Borer in Massachusetts and Vermont: A Secondary Disturbance - Marla Markowski-Lindsay; Paul Catanzaro; Amanda Robillard; Brett J Butler; David A Orwig; Anthony W D’Amato; Jonathan R Thompson; Danelle M Laflower; Meghan Graham MacLean; Malcolm Itter (Journal of Forestry, 2023)
Forester and logger responses to the invasive emerald ash borer (EAB) could substantially affect regions across the United States. We analyzed forester and logger responses to EAB in Massachusetts and Vermont, exploring characteristics associated with purposeful targeting of substantial ash properties; managing forests differently because of EAB; and regeneration goals. One-third of respondents increased timber sales on ash properties, motivated by ecological, not economic, impacts of EAB. Nearly 60% said EAB changed their management activity in stands with ash; changes influenced by the ecological impact of EAB and not economic factors. Those influenced by EAB’s ecological impact to choose properties with substantial ash were more likely to have increased harvest area size, sawtimber removal, and harvest intensity. Loggers were more likely than foresters to remove small-diameter ash and low-grade trees. Both rated regenerating economically valuable species well adapted to the site as their highest essential priority.

The phytotoxicity of soil-applied herbicides is enhanced in the first-year post strategic deep tillage - Tom J. Edwards; Stephen L. Davies; Ron J. Yates; Mick Rose; John G. Howieson; Graham O’Hara; Emma J. Steel; David JM Hall (Soil and Tillage Research, 2023)

Exploring resistomes and microbiomes in pilot-scale microalgae-bacteria wastewater treatment systems for use in low-resource settings - Julián O. Ovis-Sánchez; Victor D. Perera-Pérez; Germán Buitrón; Marcos Quintela-Baluja; David W. Graham; Rosario Morales-Espinosa; Julián Carrillo-Reyes (Science of The Total Environment, 2023)

Entry fees enhance marine protected area management and outcomes - Chris Brown; Gabby N. Ahmadia; Dominic A. Andradi-Brown; Nur Arafeh-Dalmau; Christina A. Buelow; Max D. Campbell; Graham J. Edgar; Jonas Geldmann; David Gill; Rick D. Stuart-Smith (Biological Conservation, 2023)

Mineralogy and enrichment of critical elements (Li and Nb-Ta-Zr-Hf-Ga) in the Pennsylvanian coals from the Antaibao Surface Mine, Shanxi Province, China: derivation of pyroclastics and sediment-source regions - Shaobo Di; Shifeng Dai; Victor P. Nechaev; David French; Ian T. Graham; Lei Zhao; Robert B. Finkelman; Hongdong Wang; Shaowei Zhang; Yongjie Hou (International Journal of Coal Geology, 2023)

Environmental Investigation and Surveillance for Legionella in Aotearoa New Zealand, 2000–2020 - Frances F. Graham; David J. G. Harte; Michael G. Baker (Current Microbiology, 2023)
The reported rate of legionellosis is increasing in Aotearoa New Zealand (NZ) with most cases community-acquired, sporadic (non-outbreak) and without an identifiable source. This analysis used two datasets to describe the environmental sources that contribute to Legionella in NZ, based on linkages with outbreaks and sporadic clinical cases, and analysis of environmental testing data. These findings highlight the need for enhanced environmental investigation of clinical cases and outbreaks. There is also a need for systematic surveillance testing of high-risk source environments to support more rigorous controls to prevent legionellosis.

Failure of an attempt to eradicate southern sting nematode (Ibipora lolii) from the Brisbane Cricket Ground (the Gabba) - Graham R Stirling; Wayne O’Neill; Jennifer Cobon; Tim Shuey; David Sandurski (Australasian Plant Pathology, 2023)

Agulhas leakage extension and its influences on South Atlantic surface water hydrography during the Pleistocene - B. Nirmal; K. Mohan; Aradhna Tripati; Beth A. Christensen; P. Graham Mortyn; David De Vleeschouwer; M. Prakasam; K. Saravanan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Reduced model for female endocrine dynamics: Validation and functional variations - Erica J. Graham; Noémie Elhadad; David Albers (Mathematical Biosciences, 2023)

Zinc on the edge—isotopic and geophysical evidence that cratonic edges control world-class shale-hosted zinc-lead deposits - David L. Huston; David C. Champion; Karol Czarnota; Jingming Duan; Matthew Hutchens; Suzanne Paradis; Mark Hoggard; Bryant Ware; George M. Gibson; Michael P. Doublier; Karen Kelley; Anne McCafferty; et al. (Mineralium Deposita, 2023)
The North Australian Zinc Belt is the largest zinc-lead province in the world, containing three of the ten largest known individual deposits (HYC, Hilton-George Fisher, and Mount Isa). The Northern Cordillera in North America is the second largest zinc-lead province, containing a further two of the world’s top ten deposits (Red Dog and Howards Pass). Despite this world-class endowment, exploration in both mineral provinces during the past 2 decades has not been particularly successful, yielding only two significant discoveries (Teena, Australia, and Boundary, Canada). One of the most important aspects of exploration is to choose mineral provinces and districts within geological belts that have the greatest potential for discovery. Here, we present results from these two zinc belts that highlight previously unused datasets for area selection and targeting. Lead isotope mapping using analyses of mineralized material has identified gradients in μ ( 238 U/ 204 Pb) that coincide closely with many major deposits. Locations of these deposits also coincide with a gradient in the depth of the lithosphere-asthenosphere boundary determined from calibrated surface wave tomography models converted to temperature. Furthermore, gradients in upward-continued gravity anomalies and a step in Moho depth correspond to a pre-existing major crustal boundary in both zinc belts. A spatial association of deposits with a linear mid- to lower-crustal resistivity anomaly from magnetotelluric data is also observed in the North Australian Zinc Belt. The change from thicker to thinner lithosphere is interpreted to localize prospective basins for zinc-lead mineralization and to control the gradient in lead isotope and geophysical data. These data, when combined with data indicative of paleoenvironment and changes in plate motion at the time of mineralization, provide new exploration criteria that can be used to identify prospective mineralized basins and define the most favorable parts of these basins.

Estimation of associated values from conditional extreme value models - Ross Towe; David Randell; Jennifer Kensler; Graham Feld; Philip Jonathan (Ocean Engineering, 2023)

Local reports of climate change impacts in Sierra Nevada, Spain: sociodemographic and geographical patterns - David García-del-Amo; Peter Graham Mortyn; Victoria Reyes-García (Regional Environmental Change, 2023)
While we know that climate change is having different impacts on various ecosystems and regions of the world, we know less how the perception of such impacts varies within a population. In this study, we examine patterns of individual variation in climate change impacts reports using data from a sample ( n = 238) drawn from 33 mountainous municipalities of Sierra Nevada, Spain. Sierra Nevada inhabitants report multiple climate change impacts, being the most frequently reported changes in snowfall and snow cover, abundance of terrestrial fauna, freshwater availability, and extreme temperatures. Reports of climate change impacts vary according to informants’ sociodemographic characteristics and geographical location. People with life-long bonds with the environment and higher connection and dependence upon ecosystem services report more climate change impacts than other informants, as do people with lower level of schooling. We also found that reports of climate change impacts vary according to geographic areas, which reinforces the idea that climate change generates differentiated impacts even at small geographical scales. Understanding intracultural variation in reports of climate change impacts not only gives an enriched picture of the human dimensions of climate change but might also help design more targeted mitigation and adaptation responses.

Mitigation potential and trade-offs for nitrous oxide emissions and carbon balances of irrigated mixed-species and ryegrass-clover pastures - Johannes Laubach; John E. Hunt; Scott L. Graham; Rowan P. Buxton; Graeme N.D. Rogers; Paul L. Mudge; Jordan P. Goodrich; David Whitehead (Agricultural and Forest Meteorology, 2023)

Sediment gravity flow frequency offshore central California diminished significantly following the Last Glacial Maximum - Stephen C. Dobbs; Charles K. Paull; Eve M. Lundsten; Roberto Gwiazda; David W. Caress; Mary McGann; Marianne M. Coholich; Maureen A. L. Walton; Nora M. Nieminski; Tim McHargue; Stephan A. Graham (Frontiers in Marine Science, 2023)
A high-resolution multibeam survey from a portion of the San Simeon Channel (offshore Morro Bay, California) captured a zone of recurring troughs and ridges adjacent to prominent submarine meander bends. Through an integrated study using surveying data, sediment core analysis, radiocarbon dating, and stable isotope measurements, we hypothesize that turbidity current event frequency was higher during the late Pleistocene than at present conditions. We speculate that the rise in sea-level following the Last Glacial Maximum sequestered sedimentation largely to the shelf during the Holocene. This work suggests that the occurrence of sediment gravity flows in this region, particularly away from any submarine channels, is appreciably lower than at times of continental shelf subaerial exposure.

Dietary- but not exercise-induced acute iso-energetic deficit result in short-term appetitive compensatory responses in adolescents with obesity - Alicia Fillon; Léna Pélissier; Kristine Beaulieu; Keyne Charlot; Julie Siroux; Sarah Bagot; Mélina Bailly; Audrey Boscaro; Graham Finlayson; Yves Boirie; Martine Duclos; Laurie Isacco; et al. (Appetite, 2023)

Evaluating major anthropogenic VOC emission sources in densely populated Vietnamese cities. - Pamela A. Dominutti; James R. Hopkins; Marvin Shaw; Graham P. Mills; Hoang Anh Le; Duong Huu Huy; Grant L. Forster; Sekou Keita; To Thi Hien; David E. Oram (Environmental Pollution, 2023)

Using Protection Motivation Theory to Predict Intentions for Breast Cancer Risk Management: Intervention Mechanisms from a Randomized Controlled Trial - Claire C. Conley; Karen J. Wernli; Sarah Knerr; Tengfei Li; Kathleen Leppig; Kelly Ehrlich; David Farrell; Hongyuan Gao; Erin J. A. Bowles; Amanda L. Graham; George Luta; Jinani Jayasekera; et al. (Journal of Cancer Education, 2023)
The purpose of this study is to evaluate the direct and indirect effects of a web-based, Protection Motivation Theory (PMT)–informed breast cancer education and decision support tool on intentions for risk-reducing medication and breast MRI among high-risk women. Women with ≥ 1.67% 5-year breast cancer risk ( N = 995) were randomized to (1) control or (2) the PMT-informed intervention. Six weeks post-intervention, 924 (93% retention) self-reported PMT constructs and behavioral intentions. Bootstrapped mediations evaluated the direct effect of the intervention on behavioral intentions and the mediating role of PMT constructs. There was no direct intervention effect on intentions for risk-reducing medication or MRI ( p ’s ≥ 0.12). There were significant indirect effects on risk-reducing medication intentions via perceived risk, self-efficacy, and response efficacy, and on MRI intentions via perceived risk and response efficacy ( p ’s ≤ 0.04). The PMT-informed intervention effected behavioral intentions via perceived breast cancer risk, self-efficacy, and response efficacy. Future research should extend these findings from intentions to behavior. ClinicalTrials.gov Identifier: NCT03029286 (date of registration: January 24, 2017).

Physiological response of channel (Ictalurus punctatus) and hybrid (I. punctatus x I. furcatus) catfish following Bolbophorus damnificus infection - Mackenzie A. Gunn; Matt J. Griffin; Brian D. Ott; T. Graham Rosser; Lester H. Khoo; David J. Wise; Peter J. Allen (Aquaculture, 2023)

Explaining the resistomes in a megacity's water supply catchment: Roles of microbial assembly-dominant taxa, niched environments and pathogenic bacteria - Dong Wu; Jue Zhao; Yinglong Su; Mengjie Yang; Jan Dolfing; David W. Graham; Kai Yang; Bing Xie (Water Research, 2023)

Heavy metal and antibiotic resistance in four Indian and UK rivers with different levels and types of water pollution - Sonia Gupta; David W. Graham; T.R. Sreekrishnan; Shaikh Ziauddin Ahammad (Science of The Total Environment, 2023)

Exploring the impacts of physicochemical characteristics and heavy metals fractions on bacterial communities in four rivers - Sonia Gupta; David W. Graham; T.R. Sreekrishnan; Shaikh Ziauddin Ahammad (Journal of Environmental Management, 2023)

Provenance changes for mineral matter in the latest Permian coals from western Guizhou, southwestern China, relative to tectonic and volcanic activity in the Emeishan Large Igneous Province and Paleo-Tethys region - Minglian Shen; Shifeng Dai; Victor P. Nechaev; David French; Ian T. Graham; Shande Liu; Igor Yu. Chekryzhov; Irina A. Tarasenko; Shaowei Zhang (Gondwana Research, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

The movement ecology of fishes - Steven J. Cooke; Jordanna N. Bergman; William M. Twardek; Morgan L. Piczak; Grace A. Casselberry; Keegan Lutek; Lotte S. Dahlmo; Kim Birnie‐Gauvin; Lucas P. Griffin; Jacob W. Brownscombe; Graham D. Raby; Emily M. Standen; et al. (Journal of Fish Biology, 2022)
Movement of fishes in the aquatic realm is fundamental to their ecology and survival. Movement can be driven by a variety of biological, physiological and environmental factors occurring across all spatial and temporal scales. The intrinsic capacity of movement to impact fish individually ( e.g. , foraging) with potential knock‐on effects throughout the ecosystem ( e.g. , food web dynamics) has garnered considerable interest in the field of movement ecology. The advancement of technology in recent decades, in combination with ever‐growing threats to freshwater and marine systems, has further spurred empirical research and theoretical considerations. Given the rapid expansion within the field of movement ecology and its significant role in informing management and conservation efforts, a contemporary and multidisciplinary review about the various components influencing movement is outstanding. Using an established conceptual framework for movement ecology as a guide ( i.e. , Nathan et al. , 2008: 19052), we synthesized the environmental and individual factors that affect the movement of fishes. Specifically, internal ( e.g. , energy acquisition, endocrinology, and homeostasis) and external (biotic and abiotic) environmental elements are discussed, as well as the different processes that influence individual‐level (or population) decisions, such as navigation cues, motion capacity, propagation characteristics and group behaviours. In addition to environmental drivers and individual movement factors, we also explored how associated strategies help survival by optimizing physiological and other biological states. Next, we identified how movement ecology is increasingly being incorporated into management and conservation by highlighting the inherent benefits that spatio‐temporal fish behaviour imbues into policy, regulatory, and remediation planning. Finally, we considered the future of movement ecology by evaluating ongoing technological innovations and both the challenges and opportunities that these advancements create for scientists and managers. As aquatic ecosystems continue to face alarming climate (and other human‐driven) issues that impact animal movements, the comprehensive and multidisciplinary assessment of movement ecology will be instrumental in developing plans to guide research and promote sustainability measures for aquatic resources.

Mainstreaming forecast based action into national disaster risk management systems: experience from drought risk management in Kenya - Emmah Mwangi; Olivia Taylor; Martin C. Todd; Emma Visman; Dom Kniveton; Mary Kilavi; William Ndegwa; George Otieno; Shamton Waruru; John Mwangi; Maurine Ambani; Halima Abdillahi; et al. (Climate and Development, 2022)

Riverine bacterioplankton and phytoplankton assembly along an environmental gradient induced by urbanization - Alain Isabwe; Jun R. Yang; Yongming Wang; David M. Wilkinson; Emily B. Graham; Huihuang Chen; Jun Yang (Limnology and Oceanography, 2022)
Longitudinal environmental heterogeneity and directionality of the water movement are key features that may exert contrasting forces on riverine plankton assembly. Directionality strengthens dispersal‐driven assembly, but this can be masked by urbanization‐induced environmental heterogeneity along the river continuum. In the light of this contrast, we aimed at delineating the relative importance of assembly processes generating distribution patterns of bacterioplankton and phytoplankton communities in a river draining an urbanizing watershed in Southeast China. We applied variation partitioning analysis, neutral community model, and quantitative process estimate on molecular and morphological plankton data obtained over the years 2012–2016. Despite a relatively short distance between sampling sites (

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Identification of genetic loci in lettuce mediating quantitative resistance to fungal pathogens - Harry Pink; Adam Talbot; Abi Graceson; Juliane Graham; Gill Higgins; Andrew Taylor; Alison C. Jackson; Maria Truco; Richard Michelmore; Chenyi Yao; Frances Gawthrop; David Pink; et al. (Theoretical and Applied Genetics, 2022)
Key message We demonstrate genetic variation for quantitative resistance against important fungal pathogens in lettuce and its wild relatives, map loci conferring resistance and predict key molecular mechanisms using transcriptome profiling. Abstract Lactuca sativa L. (lettuce) is an important leafy vegetable crop grown and consumed globally. Chemicals are routinely used to control major pathogens, including the causal agents of grey mould ( Botrytis cinerea ) and lettuce drop ( Sclerotinia sclerotiorum ) . With increasing prevalence of pathogen resistance to fungicides and environmental concerns, there is an urgent need to identify sources of genetic resistance to B. cinerea and S. sclerotiorum in lettuce. We demonstrated genetic variation for quantitative resistance to B. cinerea and S. sclerotiorum in a set of 97 diverse lettuce and wild relative accessions, and between the parents of lettuce mapping populations. Transcriptome profiling across multiple lettuce accessions enabled us to identify genes with expression correlated with resistance, predicting the importance of post-transcriptional gene regulation in the lettuce defence response. We identified five genetic loci influencing quantitative resistance in a F 6 mapping population derived from a Lactuca serriola (wild relative) × lettuce cross, which each explained 5–10% of the variation. Differential gene expression analysis between the parent lines, and integration of data on correlation of gene expression and resistance in the diversity set, highlighted potential causal genes underlying the quantitative trait loci.

“Killer Joules”: spores of Bipolaris sorokiniana and fusarium species are susceptible to microwave radiation - Toni Petronaitis; Clayton Forknall; Graham Brodie; Steven Simpfendorfer; David Backhouse (Australasian Plant Pathology, 2022)
Cereal production in Australia is severely impacted by diseases such as Fusarium crown rot (caused predominantly by Fusarium pseudograminearum ) and common root rot (caused by Bipolaris sorokiniana ). These diseases are particularly difficult to manage because inoculum can survive at least three years within cereal stubble, or four years in soil in the case of B. sorokiniana . Microwave radiation may be able to reduce or eliminate inoculum within stubble and soil. Several cereal pathogens have been previously shown to be susceptible to microwave radiation, but the energy requirements to achieve a significant decrease in pathogen populations were not defined. Laboratory based microwave dose-response experiments on conidia of B. sorokiniana and macroconidia of F. pseudograminearum and F. cerealis revealed that all three pathogens are susceptible to microwave radiation, with lethal dose (LD) thresholds estimated for each pathogen. Bipolaris sorokiniana conidia required 103.8 Jg − 1 and 236.6 Jg − 1 of microwave radiation energy for LD50 and LD99, respectively, whilst F. pseudograminearum required 78.4 Jg − 1 and 300.8 Jg − 1 and F. cerealis required 95.3 Jg − 1 and 152.7 Jg − 1 for LD50 and LD99, respectively. These results were derived from experiments whereby samples were microwaved for up to 10 s using a domestic 1100 W microwave oven. These timing and energy requirements serve as a starting point to define requirements for further development of microwave radiation treatments under field conditions.

Evaluation of Sublethal Toxicity of Nitrite to a Suite of Aquatic Organisms in Support of the Derivation of a Chronic Environmental Water Quality Benchmark - Josh A. Baker; Graham Matheson; Guy Gilron; David K. DeForest (Archives of Environmental Contamination and Toxicology, 2022)

Cross‐protective efficacy of a live‐attenuated Edwardsiella ictaluri vaccine against heterologous Edwardsiella piscicida isolates in channel and channel × blue catfish hybrids - Adrián López‐Porras; Matt J. Griffin; Cynthia Ware; Bradley M. Richardson; Terrence E. Greenway; Thomas Graham Rosser; Suja Aarattuthodiyi; David J. Wise (Journal of Fish Diseases, 2022)
Edwardsiella piscicida is a growing problem for catfish aquaculture in the southeastern United States, particularly in channel ( Ictalurus punctatus ) x blue ( I. furcatus ) catfish hybrids. Research has shown E. piscicida isolates recovered from farmed catfish in Mississippi form at least five discrete phyletic groups, with no apparent differences in virulence in channel and hybrid catfish. Laboratory trials have shown a live‐attenuated E . ictaluri vaccine (340X2) cross‐protects against at least one E. piscicida isolate (S11–285) in channel and hybrid catfish, although it is unknown if this protection exists for other E. piscicida variants. To this end, channel and hybrid catfish were immunized by immersion with E . ictaluri 340X2. Thirty days later, fish were challenged by intracoelomic injection with representative E. piscicida variants from each phyletic group. Relative percent survival (RPS) for hybrids ranged from 54.7% to 77.8%, while RPS in channels ranged from 80.5% to 100%. A second study investigated whether channel and hybrid catfish exposed to heterologous E. piscicida isolates were similarly protected against wild‐type E . ictaluri . Fish were exposed by bath immersion to representative E. piscicida isolates from each phyletic group. Thirty days post‐immunization, fish were challenged by immersion with wild‐type E . ictaluri isolate S97–773. Regardless of variant, previous exposure to heterologous E. piscicida isolates significantly improved survival following E . ictaluri challenge. These findings suggest the presence of shared and conserved antigens among E. piscicida and E . ictaluri that could be exploited by application of polyvalent or cross‐protective vaccines.

The contribution of macroalgae‐associated fishes to small‐scale tropical reef fisheries - Shaun K. Wilson; Christopher J. Fulton; Nicholas A.J. Graham; Rene A. Abesamis; Charlotte Berkström; Darren J. Coker; Martial Depczynski; Richard D. Evans; Rebecca Fisher; Jordan Goetze; Andrew Hoey; Thomas H. Holmes; et al. (Fish and Fisheries, 2022)
Macroalgae‐dominated reefs are a prominent habitat in tropical seascapes that support a diversity of fishes, including fishery target species. To what extent, then, do macroalgal habitats contribute to small‐scale tropical reef fisheries? To address this question we: (1) Quantified the macroalgae‐associated fish component in catches from 133 small‐scale fisheries, (2) Compared life‐history traits relevant to fishing (e.g. growth, longevity) in macroalgal and coral‐associated fishes, (3) Examined how macroalgae‐associated species can influence catch diversity, trophic level and vulnerability and (4) Explored how tropical fisheries change with the expansion of macroalgal habitats using a case study of fishery‐independent data for Seychelles. Fish that utilised macroalgal habitats comprise 24% of the catch, but very few fished species relied entirely on macroalgal or coral habitats post‐settlement. Macroalgal and coral‐associated fishes had similar life‐history traits, although vulnerability to fishing declined with increasing contribution of macroalgae association to the catch, whilst mean trophic level and diversity peaked when macroalgal‐associated fish accounted for 20%–30% of catches. The Seychelles case study revealed similar total fish biomass on macroalgal and coral reefs, although the biomass of primary target species increased as macroalgae cover expanded. Our findings reinforce that multiple habitat types are needed to support tropical fishery stability and sustainability. Whilst coral habitats have been the focus of tropical fisheries management, we show the potential for macroalgae‐associated fish to support catch size and diversity in ways that reduce vulnerability to overfishing. This is pertinent to seascapes where repeated disturbances are facilitating the replacement of coral reef with macroalgal habitats.

Persistent viral RNA shedding of SARS-CoV-2 is associated with delirium incidence and six-month mortality in hospitalized COVID-19 patients - Ayush Batra; Jeffrey R. Clark; Anthony K. Kang; Sareen Ali; Tulsi R. Patel; Nathan A. Shlobin; Steven C. Hoffman; Patrick H. Lim; Zachary S. Orban; Lavanya Visvabharathy; Edith L. Graham; David P. Sullivan; et al. (GeroScience, 2022)

Moderation of buprenorphine therapy for cocaine dependence efficacy by variation of the Prodynorphin gene - David A. Nielsen; Robrina Walker; David P. Graham; Ellen M. Nielsen; Sara C. Hamon; Maureen Hillhouse; Dikla Shmueli-Blumberg; William B. Lawson; Kathy Shores-Wilson; Beverlyn D. Settles-Reaves; John Rotrosen; Madhukar H. Trivedi; et al. (European Journal of Clinical Pharmacology, 2022)

Physical activity and glioma: a case–control study with follow-up for survival - Zohreh Basiri; Yi Yang; Fiona J. Bruinsma; Anna K. Nowak; Kerrie L. McDonald; Katharine J. Drummond; Mark A. Rosenthal; Eng-Siew Koh; Rosemary Harrup; Elizabeth Hovey; David Joseph; Geza Benke; et al. (Cancer Causes & Control, 2022)
Purpose High-grade disease accounts for ~ 70% of all glioma, and has a high mortality rate. Few modifiable exposures are known to be related to glioma risk or mortality. Methods We examined associations between lifetime physical activity and physical activity at different ages (15–18 years, 19–29 years, 30–39 years, last 10 years) with the risk of glioma diagnosis, using data from a hospital-based family case–control study (495 cases; 371 controls). We followed up cases over a median of 25 months to examine whether physical activity was associated with all-cause mortality. Physical activity and potential confounders were assessed by self-administered questionnaire. We examined associations between physical activity (metabolic equivalent [MET]-h/wk) and glioma risk using unconditional logistic regression and with all-cause mortality in cases using Cox regression. Results We noted a reduced risk of glioma for the highest (≥ 47 MET-h/wk) versus lowest (< 24 METh/wk) category of physical activity for lifetime activity (OR = 0.58, 95% CI: 0.38–0.89) and at 15–18 years (OR = 0.57, 95% CI: 0.39–0.83). We did not observe any association between physical activity and all-cause mortality (HR for lifetime physical activity = 0.91, 95% CI: 0.64–1.29). Conclusion Our findings are consistent with previous research that suggested physical activity during adolescence might be protective against glioma. Engaging in physical activity during adolescence has many health benefits; this health behavior may also offer protection against glioma.

Early-growth results within a Eucalyptus globulus breeding population suggest limited scope for selection focused on CO2 responsiveness - Matthew Theodore Brookhouse; David Bush; Milos Ivkovich; Florian Busch; Graham Douglas Farquhar; Elizabeth Pinkard (Tree Genetics & Genomes, 2022)
Increasing [CO 2 ] may influence commercial crop and timber yield. While selection of genotypes sensitive to elevated [CO 2 ] (e[CO 2 ]) appears possible in agricultural crops, there is limited evidence for genotype-by-CO 2 (G × CO 2 ) interactions in commercial tree species. We examined [CO 2 ] responsiveness in 124 open-pollinated Eucalyptus globulus ssp. globulus ( E. globulus ) families with the aim of assessing whether G × CO 2 interactions are detectable in seedlings for early-age screening. Plants were grown in ambient (a[CO 2 ]; ~ 405 μmol mol −1 ) and e[CO 2 ] (640 μmol mol −1 ) and harvested 25 days after germination. Total, shoot, and root dry weights were determined for each plant. Carbon isotopic discrimination against 13 C (Δ 13 C) was determined at the family level. We observed highly significant ( p < 0.0001) increases in mean total, shoot, and root dry weights. Mixed-model equations were used to estimate the main and interaction effects of the G × CO 2 for each mass trait. The main effects from the mixed-model output ([CO 2 ] and individual-tree effects) were significant for all traits. However, [CO 2 ]-by-individual tree interactions were non-significant for all traits, indicating little G × CO 2 interaction. A secondary aim was to examine the correlation between greenhouse and mature-age growth from breeding trials that use common families conducted under ambient [CO 2 ]. These correlations were non-significant, suggesting early growth is not necessarily indicative of later-age responses. Our results suggest that while early growth of E. globulus is enhanced under e[CO 2 ], genotypes respond relatively uniformly to e[CO 2 ] and little opportunity exists for seedling-based selection at the population level based upon the response of plants during the first weeks of growth.

A Macroinfaunal Ecosystem Engineer May Facilitate Recovery of Benthic Invertebrates and Accompanying Ecosystem Services After an Oil Spill - John W. Fleeger; David S. Johnson; Scott A. Zengel; Irving A. Mendelssohn; Donald R. Deis; Sean A. Graham (Estuaries and Coasts, 2022)

Area‐based management of blue water fisheries: Current knowledge and research needs - Ray Hilborn; Vera N. Agostini; Milani Chaloupka; Serge M. Garcia; Leah R. Gerber; Eric Gilman; Quentin Hanich; Amber Himes‐Cornell; Alistair J. Hobday; David Itano; Michel J. Kaiser; Hilario Murua; et al. (Fish and Fisheries, 2022)
The pelagic fisheries beyond the continental shelves are currently managed with a range of tools largely based on regulating effort or target catch. These tools comprise both static and dynamic area‐based approaches to include gear limitations, closed areas and bycatch limits. There are increasing calls for additional area‐based interventions, particularly expansion of marine protected areas, with many now advocating closing 30% of the oceans to fishing. In this paper, we review the objectives, methods and successes of area‐based management of blue water fisheries across objectives related to food production and environmental, social and economic impacts. We also consider the methods used to evaluate the performance of area‐based regulations and provide a summary of the relative quality of evidence from alternative evaluation approaches. We found that few area‐based approaches have been rigorously evaluated, and that it is often difficult to obtain requisite observational data to define a counterfactual to infer any causal effect for such evaluation. Management agencies have been relatively successful at maintaining important commercial species at or near their target abundance, but success at meeting ecological or social goals is less clear. The high mobility of both target and bycatch species generally reduces the effectiveness of area‐based management, and shifting distributions due to climate change suggest that adaptive rather than static approaches will be preferred. We prioritize research and management actions that would make area‐based management more effective.

Modelling the effects of cold temperature during the reproductive stage on the yield of chickpea (Cicer arietinum L.) - Muhuddin Rajin Anwar; David J. Luckett; Yashvir S. Chauhan; Ryan H. L. Ip; Lancelot Maphosa; Marja Simpson; Annie Warren; Rosy Raman; Mark F. Richards; Georgina Pengilley; Kristy Hobson; Neroli Graham (International Journal of Biometeorology, 2022)
During the reproductive stage, chilling temperatures and frost reduce the yield of chickpea and limit its adaptation. The adverse effects of chilling temperature and frost in terms of the threshold temperatures, impact of cold duration, and genotype-by-environment-by-management interactions are not well quantified. Crop growth models that predict flowering time and yield under diverse climates can identify combinations of cultivars and sowing time to reduce frost risk in target environments. The Agricultural Production Systems Simulator (APSIM-chickpea) model uses daily temperatures to model basic crop growth but does not include penalties for either frost damage or cold temperatures during flowering and podding stages. Regression analysis overcame this limitation of the model for chickpea crops grown at 95 locations in Australia using 70 years of historic data incorporating three cultivars and three sowing times (early, mid, and late). We modified model parameters to include the effect of soil water on thermal time calculations, which significantly improved the prediction of flowering time. Simulated data, and data from field experiments grown in Australia (2013 to 2019), showed robust predictions for flowering time ( n = 29; R 2 = 0.97), and grain yield ( n = 22; R 2 = 0.63–0.70). In addition, we identified threshold cold temperatures that significantly affected predicted yield, and combinations of locations, variety, and sowing time where the overlap between peak cold temperatures and peak flowering was minimal. Our results showed that frost and/or cold temperature–induced yield losses are a major limitation in some unexpected Australian locations, e.g., inland, subtropical latitudes in Queensland. Intermediate sowing maximise yield, as it avoids cold temperature, late heat, and drought stresses potentially limiting yield in early and late sowing respectively.

Progress in protecting air travel from volcanic ash clouds - Larry Mastin; Mike Pavolonis; Samantha Engwell; Rory Clarkson; Claire Witham; Greg Brock; Ian Lisk; Marianne Guffanti; Andrew Tupper; David Schneider; Frances Beckett; Thomas Casadevall; et al. (Bulletin of Volcanology, 2022)

From anecdotes to quantification: advances in characterizing volcanic eruption impacts on the built environment - Natalia Irma Deligne; Susanna F. Jenkins; Elinor S. Meredith; George T. Williams; Graham S. Leonard; Carol Stewart; Thomas M. Wilson; Sébastien Biass; Daniel M. Blake; Russell J. Blong; Costanza Bonadonna; Rodrigo Calderon B.; et al. (Bulletin of Volcanology, 2022)

Large‐scale genome sampling reveals unique immunity and metabolic adaptations in bats - Diana D. Moreno Santillán; Tanya M. Lama; Yocelyn T. Gutierrez Guerrero; Alexis M. Brown; Paul Donat; Huabin Zhao; Stephen J. Rossiter; Laurel R. Yohe; Joshua H. Potter; Emma C. Teeling; Sonja C. Vernes; Kalina T. J. Davies; et al. (Molecular Ecology, 2021)
Comprising more than 1,400 species, bats possess adaptations unique among mammals including powered flight, unexpected longevity, and extraordinary immunity. Some of the molecular mechanisms underlying these unique adaptations includes DNA repair, metabolism and immunity. However, analyses have been limited to a few divergent lineages, reducing the scope of inferences on gene family evolution across the Order Chiroptera. We conducted an exhaustive comparative genomic study of 37 bat species, one generated in this study, encompassing a large number of lineages, with a particular emphasis on multi‐gene family evolution across immune and metabolic genes. In agreement with previous analyses, we found lineage‐specific expansions of the APOBEC3 and MHC‐I gene families, and loss of the proinflammatory PYHIN gene family. We inferred more than 1,000 gene losses unique to bats, including genes involved in the regulation of inflammasome pathways such as epithelial defence receptors, the natural killer gene complex and the interferon‐gamma induced pathway. Gene set enrichment analyses revealed genes lost in bats are involved in defence response against pathogen‐associated molecular patterns and damage‐associated molecular patterns. Gene family evolution and selection analyses indicate bats have evolved fundamental functional differences compared to other mammals in both innate and adaptive immune system, with the potential to enhance antiviral immune response while dampening inflammatory signalling. In addition, metabolic genes have experienced repeated expansions related to convergent shifts to plant‐based diets. Our analyses support the hypothesis that, in tandem with flight, ancestral bats had evolved a unique set of immune adaptations whose functional implications remain to be explored.

Hyperpolarized NMR study of the impact of pyruvate dehydrogenase kinase inhibition on the pyruvate dehydrogenase and TCA flux in type 2 diabetic rat muscle - Jae Mo Park; Sonal Josan; Ralph E. Hurd; James Graham; Peter J. Havel; David Bendahan; Dirk Mayer; Youngran Chung; Daniel M. Spielman; Thomas Jue (Pflügers Archiv - European Journal of Physiology, 2021)

Genetic variability of Edwardsiella piscicida isolates from Mississippi catfish aquaculture with an assessment of virulence in channel and channel × blue hybrid catfish - Adrián López‐Porras; Matt J. Griffin; Abigail R. Armwood; Alvin C. Camus; Geoffrey C. Waldbieser; Cynthia Ware; Bradley Richardson; Terrence E. Greenway; Thomas Graham Rosser; Suja Aarattuthodiyil; David J. Wise (Journal of Fish Diseases, 2021)
The bacterium Edwardsiella piscicida causes significant losses in global aquaculture, particularly channel ( Ictalurus punctatus ) × blue ( I . furcatus ) hybrid catfish cultured in the south‐eastern United States. Emergence of E . piscicida in hybrid catfish is worrisome given current industry trends towards increased hybrid production. The project objectives were to assess intraspecific genetic variability of E . piscicida isolates recovered from diseased channel and hybrid catfish in Mississippi; and determine virulence associations among genetic variants. Repetitive extragenic palindromic sequence‐based PCR (rep‐PCR) using ERIC I and II primers was used to screen 158 E . piscicida diagnostic case isolates. A subsample of 39 E . piscicida isolates, representing predominant rep‐PCR profiles, was further characterized using BOX and (GTG) 5 rep‐PCR primers, virulence gene assessment and multilocus sequence analysis (MLSA) targeting housekeeping genes gyrb , pgi and phoU . The MLSA provided greater resolution than rep‐PCR, revealing 5 discrete phylogroups that correlated similarly with virulence gene profiles. Virulence assessments using E . piscicida representatives from each MLSA group resulted in 14‐day cumulative mortality ranging from 22% to 54% and 63 to 72% in channel and hybrid fingerlings, respectively. Across all phylogroups, mortality was higher in hybrid catfish ( p E . piscicida is an emerging threat to hybrid catfish aquaculture in the south‐eastern United States.

Nitrogen and phosphorus cycling in an ombrotrophic peatland: a benchmark for assessing change - Verity G. Salmon; Deanne J. Brice; Scott Bridgham; Joanne Childs; Jake Graham; Natalie A. Griffiths; Kirsten Hofmockel; Colleen M. Iversen; Terri M. Jicha; Randy K. Kolka; Joel E. Kostka; Avni Malhotra; et al. (Plant and Soil, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

St Helena Marine Water Quality: Background Conditions and Development of Assessment Levels for Coastal Pollutants - Suzanne Jane Painting; Eleanor K. Haigh; Jennifer A. Graham; Simon A. Morley; Leeann Henry; Elizabeth Clingham; Rhys Hobbs; Frances Mynott; Philippe Bersuder; David I. Walker; Tammy Stamford (Frontiers in Marine Science, 2021)
St Helena is an isolated oceanic island located in the tropical South Atlantic, and knowledge of broadscale oceanography and productivity in its surrounding waters is limited. This study used model outputs (2007-2017), remote sensing data (1998-2017) and survey measurements (April 2018 and 2019) to determine background conditions for nutrients, chlorophyll and suspended particulate matter (SPM) in offshore waters and propose standards (thresholds) for assessing inshore water quality based on 50% deviation from seasonal (usually June to November) or annual averages. Seasonal thresholds were proposed for surface nitrate (average 0.18 μM), phosphate (average 0.26 μM), silicate (average 2.60 μM), chlorophyll (average 0.45 μg chl l –1 ), and SPM (average 0.96 mg l –1 ). Associated background values for most surface parameters (phosphate 0.17 μM, silicate 1.57 μM, chlorophyll 0.30 μg chl l –1 ; from model outputs and remote sensing) were slightly higher than offshore observations (April 2019). For nitrate, the average background value (0.12 μM) was lower than the observed average (0.24 μM). At depth (150-500 m), annual background values from model outputs were high (nitrate 26.8 μM, phosphate 1.8 μM, silicate 17.3 μM). Observed water masses at depths >150 m, identified to be of Antarctic and Atlantic origin, were nutrient-rich (e.g., 16 μM for nitrate, April 2019) and oxygen deficient (<4-6 mg l –1 ). A thermocline layer (between ca. 10 and 230 m), characterized by a sub-surface chlorophyll maximum (average 0.3-0.5 μg chl l –1 ) near the bottom of the euphotic zone ( ca. 100 m), is likely to sustain primary and secondary production at St Helena. For assessing inshore levels of chemical contaminants and fecal bacteria estimated from survey measurements, standards were derived from the literature. A preliminary assessment of inshore observations using proposed thresholds from surface offshore waters and relevant literature standards indicated concerns regarding levels of nutrients and fecal bacteria at some locations. More detailed modeling and/or field-based studies are required to investigate seasonal trends and nutrient availability to inshore primary producers and to establish accurate levels of any contaminants of interest or risk to the marine environment.

Effect of seaweed extract application on wine grape yield in Australia - Tony Arioli; Scott W. Mattner; Graham Hepworth; David McClintock; Rachael McClinock (Journal of Applied Phycology, 2021)
Seaweed extracts are agricultural biostimulants that have been shown to increase the productivity of many crops. The aim of this study was to determine the effect of a seaweed extract from the brown algae Durvillaea potatorum and Ascophyllum nodosum as a soil treatment on the yield of wine grapes grown in Australian production and climate conditions. This study used a series of seven field experiments (2012–2017), across five locations, in three Australian states and four cultivars, and analysed data using a linear mixed model approach. The analysis revealed that recurring soil applications of the seaweed extract significantly increased wine grape yield by an average of 14.7% across multiple growing years that experienced climate extremes. Partial budget analysis showed that the use of the seaweed extract increased profits depending on the grape cultivar. This study is the most extensive investigation of its type in Australian viticulture to understand the effect of a soil-applied seaweed extract on wine grape production.

Response and Effect Traits of Coral Reef Fish - Jeneen Hadj-Hammou; David Mouillot; Nicholas A. J. Graham (Frontiers in Marine Science, 2021)
The response-and-effect framework is a trait-based approach that seeks to break down the mechanistic links between ecosystem disturbances, species' traits, and ecosystem processes. We apply this framework to a review of the literature on coral reef fish traits, in order to illustrate the research landscape and structure a path forward for the field. Traits were categorized into five broad groupings: behavioral, life history, morphological, diet, and physiological. Overall, there are fewer studies linking effect traits to ecosystem processes (number of papers on herbivory, n = 14; predation, n = 12; bioerosion, n = 2; nutrient cycling, n = 0) than there are linking response traits to disturbances (climate change, n = 26; fishing, n = 20; pollution, n = 4). Through a network analysis, we show that the size and diet of fish are two of the most common response and effect traits currently used in the literature, central to studies on both ecosystem disturbances and processes. Behavioral and life history traits are more commonly shown to respond to disturbances, while morphological traits tend to be used in capturing ecosystem processes. Pearson correlation coefficients quantifying the strength of the relationships between the most commonly studied process, herbivory, and key effect traits (size, gregariousness, and diel activity) are provided. We find that the most popular cluster of traits used in functional diversity metrics (e.g., functional richness, functional dispersion) is comprised of size, diet, space use/position in the water column, diel activity, gregariousness, and mobility, which encompass three of the broad trait categories. Our assessment of the literature highlights that more research is needed to support an evidence-based selection of traits to understand and predict ecosystem functioning. In synthesizing the literature, we identify research gaps and provide an avenue toward a more robust trait-selection process.

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

A survey of heavy metal contents of rural and urban roadside dusts: comparisons at low, medium and high traffic sites in Central Scotland - Nicholas Cowan; David Blair; Heath Malcolm; Margaret Graham (Environmental Science and Pollution Research, 2021)

Caught in a bottleneck: Habitat loss for woolly mammoths in central North America and the ice‐free corridor during the last deglaciation - Yue Wang; Chris Widga; Russell W. Graham; Jenny L. McGuire; Warren Porter; David Wårlind; John W. Williams (Global Ecology and Biogeography, 2021)
Aim Identifying how climate change, habitat loss, and corridors interact to influence species survival or extinction is critical to understanding macro‐scale biodiversity dynamics under changing environments. In North America, the ice‐free corridor was the only major pathway for northward migration by megafaunal species during the last deglaciation. However, the timing and interplay among the late Quaternary megafaunal extinctions, climate change, habitat structure, and the opening and reforestation of the ice‐free corridor have been unclear. Location North America. Time period 15–10 ka. Major taxa studied Woolly mammoth ( Mammuthus primigenius ). Methods For central North America and the ice‐free corridor between 15 and 10 ka, we used a series of models and continental‐scale datasets to reconstruct habitat characteristics and assess habitat suitability. The models and datasets include biophysical and statistical niche models Niche Mapper and Maxent, downscaled climate simulations from CCSM3 SynTraCE, LPJ‐GUESS simulations of net primary productivity (NPP) and woody cover, and woody cover based upon fossil pollen from Neotoma. Results The ice‐free corridor may have been of limited suitability for traversal by mammoths and other grazers due to persistently low productivity by herbaceous plants and quick reforestation after opening 14 ka. Simultaneously, rapid reforestation and decreased forage productivity may have led to declining habitat suitability in central North America. This was possibly amplified by a positive feedback loop driven by reduced herbivory pressures, as mammoth population decline led to the further loss of open habitat. Main conclusions Declining habitat availability south of the Laurentide Ice Sheet and limited habitat availability in the ice‐free corridor were contributing factors in North American extinctions of woolly mammoths and other large grazers that likely operated synergistically with anthropogenic pressures. The role of habitat loss and attenuated corridor suitability for the woolly mammoth extinction reinforce the critical importance of protected habitat connectivity during changing climates, particularly for large vertebrates.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Temporal variability in size and growth of Atlantic herring in the Gulf of Maine - James R. Becker; Matthew D. Cieri; David A. Libby; Adam St. Gelais; Graham Sherwood; Yong Chen (Journal of Fish Biology, 2020)
Variability in life history traits and structural diversity of commercially exploited fishes in response to stress can impact their population dynamics and sustainability. Using data from a fishery dependent sampling program from 1978 to 2011, we evaluated temporal variability of size and growth of adult Atlantic herring ( Clupea harengus ) in the Gulf of Maine. We then developed and tested the hypotheses on the links of such temporal changes to population density and environmental factors and found decreases in size and growth potential. Generalized additive models found that density dependence was the main driver of such changes over sea surface temperature and salinity. Our results highlight the importance of density dependent processes in regulating growth and population size structure for Atlantic herring in the Gulf of Maine.

Correction to: Rethinking soil water repellency and its management - Katinka X. Ruthrof; Anna J. M. Hopkins; Melissa Danks; Graham O’Hara; Richard Bell; David Henry; Rachel Standish; Mark Tibbett; John Howieson; Treena Burgess; Richard Harper (Plant Ecology, 2020)

Multimodal influences on learning walks in desert ants (Cataglyphis fortis) - Jose Adrian Vega Vermehren; Cornelia Buehlmann; Ana Sofia David Fernandes; Paul Graham (Journal of Comparative Physiology A, 2020)
Ants are excellent navigators using multimodal information for navigation. To accurately localise the nest at the end of a foraging journey, visual cues, wind direction and also olfactory cues need to be learnt. Learning walks are performed at the start of an ant’s foraging career or when the appearance of the nest surrounding has changed. We investigated here whether the structure of such learning walks in the desert ant Cataglyphis fortis takes into account wind direction in conjunction with the learning of new visual information. Ants learnt to travel back and forth between their nest and a feeder, and we then introduced a black cylinder near their nest to induce learning walks in regular foragers. By doing this across days with different wind directions, we were able to probe how ants balance different sensory modalities. We found that (1) the ants’ outwards headings are influenced by the wind direction with their routes deflected such that they will arrive downwind of their target, (2) a novel object along the route induces learning walks in experienced ants and (3) the structure of learning walks is shaped by the wind direction rather than the position of the visual cue.

Accelerated Forced Degradation of Therapeutic Peptides in Levitated Microdroplets - Yangjie Li; Yanyang Hu; David L. Logsdon; Yong Liu; Yuejie Zhao; R. Graham Cooks (Pharmaceutical Research, 2020)

Dynamics of a human‐modified tropical peat swamp forest revealed by repeat lidar surveys - Béatrice Wedeux; Michele Dalponte; Michael Schlund; Stephen Hagen; Mark Cochrane; Laura Graham; Aswin Usup; Andri Thomas; David Coomes (Global Change Biology, 2020)
Tropical peat swamp forests (PSFs) are globally important carbon stores under threat. In Southeast Asia, 35% of peatlands had been drained and converted to plantations by 2010, and much of the remaining forest had been logged, contributing significantly to global carbon emissions. Yet, tropical forests have the capacity to regain biomass quickly and forests on drained peatlands may grow faster in response to soil aeration, so the net effect of humans on forest biomass remains poorly understood. In this study, two lidar surveys (made in 2011 and 2014) are compared to map forest biomass dynamics across 96 km 2 of PSF in Kalimantan, Indonesia. The peatland is now legally protected for conservation, but large expanses were logged under concessions until 1998 and illegal logging continues in accessible portions. It was hypothesized that historically logged areas would be recovering biomass while recently logged areas would be losing biomass. We found that historically logged forests were recovering biomass near old canals and railways used by the concessions. Lidar detected substantial illegal logging activity—579 km of logging canals were located beneath the canopy. Some patches close to these canals have been logged in the 2011–2104 period (i.e. substantial biomass loss) but, on aggregate, these illegally logged regions were also recovering. Unexpectedly, rapid growth was also observed in intact forest that had not been logged and was over a kilometre from the nearest known canal, perhaps in response to greater aeration of surface peat. Comparing these results with flux measurements taken at other nearby sites, we find that carbon sequestration in above‐ground biomass may have offset roughly half the carbon efflux from peat oxidation. This study demonstrates the power of repeat lidar survey to map fine‐scale forest dynamics in remote areas, revealing previously unrecognized impacts of anthropogenic global change.

Macroalgal meadow habitats support fish and fisheries in diverse tropical seascapes - Christopher J. Fulton; Charlotte Berkström; Shaun K. Wilson; Rene A. Abesamis; Michael Bradley; Carolina Åkerlund; Luke T. Barrett; Abner A. Bucol; Dinorah H. Chacin; Karen M. Chong‐Seng; Darren J. Coker; Martial Depczynski; et al. (Fish and Fisheries, 2020)
Canopy‐forming macroalgae can construct extensive meadow habitats in tropical seascapes occupied by fishes that span a diversity of taxa, life‐history stages and ecological roles. Our synthesis assessed whether these tropical macroalgal habitats have unique fish assemblages, provide fish nurseries and support local fisheries. We also applied a meta‐analysis of independent surveys across 23 tropical reef locations in 11 countries to examine how macroalgal canopy condition is related to the abundance of macroalgal‐associated fishes. Over 627 fish species were documented in tropical macroalgal meadows, with 218 of these taxa exhibiting higher local abundance within this habitat (cf. nearby coral reef) during at least one life‐history stage. Major overlap (40%–43%) in local fish species richness among macroalgal and seagrass or coral reef habitats suggest macroalgal meadows may provide an important habitat refuge. Moreover, the prominence of juvenile fishes suggests macroalgal meadows facilitate the triphasic life cycle of many fishes occupying diverse tropical seascapes. Correlations between macroalgal canopy structure and juvenile abundance suggests macroalgal habitat condition can influence levels of replenishment in tropical fish populations, including the majority of macroalgal‐associated fishes that are targeted by commercial, subsistence or recreational fisheries. While many macroalgal‐associated fishery species are of minor commercial value, their local importance for food and livelihood security can be substantial (e.g. up to 60% of landings in Kenyan reef fisheries). Given that macroalgal canopy condition can vary substantially with sea temperature, there is a high likelihood that climate change will impact macroalgal‐associated fish and fisheries.

Mapping sub-field maize yields in Nebraska, USA by combining remote sensing imagery, crop simulation models, and machine learning - Graham R. Jeffries; Timothy S. Griffin; David H. Fleisher; Elena N. Naumova; Magaly Koch; Brian D. Wardlow (Precision Agriculture, 2020)

Horizon scanning for South African biodiversity: A need for social engagement as well as science - Colleen L. Seymour; Lindsey Gillson; Matthew F. Child; Krystal A. Tolley; Jock C. Curie; Jessica M. da Silva; Graham J. Alexander; Pippin Anderson; Colleen T. Downs; Benis N. Egoh; David A. Ehlers Smith; Yvette C. Ehlers Smith; et al. (Ambio, 2020)

Including indigenous and local knowledge in climate research: an assessment of the opinion of Spanish climate change researchers - David García-del-Amo; P. Graham Mortyn; Victoria Reyes-García (Climatic Change, 2020)

Increased attenuation and reverberation are associated with lower maximum frequencies and narrow bandwidth of bird songs in cities - Jennifer N. Phillips; Catherine Rochefort; Sara Lipshutz; Graham E. Derryberry; David Luther; Elizabeth P. Derryberry (Journal of Ornithology, 2020)

Identification and QTL mapping of resistance to Turnip yellows virus (TuYV) in oilseed rape, Brassica napus - Dieter Hackenberg; Elvis Asare-Bediako; Adam Baker; Peter Walley; Carol Jenner; Shannon Greer; Lawrence Bramham; Jacqueline Batley; David Edwards; Regine Delourme; Guy Barker; Graham Teakle; et al. (Theoretical and Applied Genetics, 2020)
Key message Partially dominant resistance to Turnip yellows virus associated with one major QTL was identified in the natural allotetraploid oilseed rape cultivar Yudal. Abstract Turnip yellows virus (TuYV) is transmitted by the peach-potato aphid ( Myzus persicae ) and causes severe yield losses in commercial oilseed rape crops ( Brassica napus ). There is currently only one genetic resource for resistance to TuYV available in brassica, which was identified in the re-synthesised B. napus line ‘R54’. In our study, 27 mostly homozygous B. napus accessions, either doubled-haploid (DH) or inbred lines, representing a diverse subset of the B. napus genepool, were screened for TuYV resistance/susceptibility. Partial resistance to TuYV was identified in the Korean spring oilseed rape, B. napus variety Yudal, whilst the dwarf French winter oilseed rape line Darmor- bzh was susceptible. QTL mapping using the established Darmor- bzh × Yudal DH mapping population (DYDH) revealed one major QTL explaining 36% and 18% of the phenotypic variation in two independent experiments. A DYDH line was crossed to Yudal, and reciprocal backcross (BC 1 ) populations from the F 1 with either the susceptible or resistant parent revealed the dominant inheritance of the TuYV resistance. The QTL on ChrA04 was verified in the segregating BC 1 population. A second minor QTL on ChrC05 was identified in one of the two DYDH experiments, and it was not observed in the BC 1 population. The TuYV resistance QTL in ‘R54’ is within the QTL interval on Chr A04 of Yudal; however, the markers co-segregating with the ‘R54’ resistance are not conserved in Yudal, suggesting an independent origin of the TuYV resistances. This is the first report of the QTL mapping of TuYV resistance in natural B. napus .

Constraints on eruption processes and event masses for the 2016–2017 eruption of Bogoslof volcano, Alaska, through evaluation of IASI satellite SO2 masses and complementary datasets - Taryn Lopez; Lieven Clarisse; Hans Schwaiger; Alexa Van Eaton; Matthew Loewen; David Fee; John Lyons; Kristi Wallace; Cheryl Searcy; Aaron Wech; Matthew Haney; David Schneider; et al. (Bulletin of Volcanology, 2020)

Trends in tuna carbon isotopes suggest global changes in pelagic phytoplankton communities - Anne Lorrain; Heidi Pethybridge; Nicolas Cassar; Aurore Receveur; Valérie Allain; Nathalie Bodin; Laurent Bopp; C. Anela Choy; Leanne Duffy; Brian Fry; Nicolas Goñi; Brittany S. Graham; et al. (Global Change Biology, 2020)
Considerable uncertainty remains over how increasing atmospheric CO 2 and anthropogenic climate changes are affecting open‐ocean marine ecosystems from phytoplankton to top predators. Biological time series data are thus urgently needed for the world's oceans. Here, we use the carbon stable isotope composition of tuna to provide a first insight into the existence of global trends in complex ecosystem dynamics and changes in the oceanic carbon cycle. From 2000 to 2015, considerable declines in δ 13 C values of 0.8‰–2.5‰ were observed across three tuna species sampled globally, with more substantial changes in the Pacific Ocean compared to the Atlantic and Indian Oceans. Tuna recorded not only the Suess effect, that is, fossil fuel‐derived and isotopically light carbon being incorporated into marine ecosystems, but also recorded profound changes at the base of marine food webs. We suggest a global shift in phytoplankton community structure, for example, a reduction in 13 C‐rich phytoplankton such as diatoms, and/or a change in phytoplankton physiology during this period, although this does not rule out other concomitant changes at higher levels in the food webs. Our study establishes tuna δ 13 C values as a candidate essential ocean variable to assess complex ecosystem responses to climate change at regional to global scales and over decadal timescales. Finally, this time series will be invaluable in calibrating and validating global earth system models to project changes in marine biota.

Governing evolution: A socioecological comparison of resistance management for insecticidal transgenic Bt crops among four countries - Yves Carrière; Zachary S. Brown; Sharon J. Downes; Govind Gujar; Graham Epstein; Celso Omoto; Nicholas P. Storer; David Mota-Sanchez; Peter Søgaard Jørgensen; Scott P. Carroll (Ambio, 2020)

Assembly and characterisation of a unique onion diversity set identifies resistance to Fusarium basal rot and improved seedling vigour - Andrew Taylor; Graham R. Teakle; Peter G. Walley; William E. Finch-Savage; Alison C. Jackson; Julie E. Jones; Paul Hand; Brian Thomas; Michael J. Havey; David A. C. Pink; John P. Clarkson (Theoretical and Applied Genetics, 2019)
Key message A unique, global onion diversity set was assembled, genotyped and phenotyped for beneficial traits. Accessions with strong basal rot resistance and increased seedling vigour were identified along with associated markers. Abstract Conserving biodiversity is critical for safeguarding future crop production. Onion ( Allium cepa L.) is a globally important crop with a very large (16 Gb per 1C) genome which has not been sequenced. While onions are self-fertile, they suffer from severe inbreeding depression and as such are highly heterozygous as a result of out-crossing. Bulb formation is driven by daylength, and accessions are adapted to the local photoperiod. Onion seed is often directly sown in the field, and hence seedling establishment is a critical trait for production. Furthermore, onion yield losses regularly occur worldwide due to Fusarium basal rot caused by Fusarium oxysporum f. sp. cepae . A globally relevant onion diversity set, consisting of 10 half-sib families for each of 95 accessions, was assembled and genotyping carried out using 892 SNP markers. A moderate level of heterozygosity (30–35%) was observed, reflecting the outbreeding nature of the crop. Using inferred phylogenies, population structure and principal component analyses, most accessions grouped according to local daylength. A high level of intra-accession diversity was observed, but this was less than inter-accession diversity. Accessions with strong basal rot resistance and increased seedling vigour were identified along with associated markers, confirming the utility of the diversity set for discovering beneficial traits. The onion diversity set and associated trait data therefore provide a valuable resource for future germplasm selection and onion breeding.

Interspecific differences in environmental response blur trait dynamics in classic statistical analyses - Matthew McLean; David Mouillot; Sébastien Villéger; Nicholas A. J. Graham; Arnaud Auber (Marine Biology, 2019)

Rethinking soil water repellency and its management - Katinka X. Ruthrof; Anna J. M. Hopkins; Melissa Danks; Graham O’Hara; Richard Bell; David Henry; Rachel Standish; Mark Tibbett; John Howieson; Treena Burgess; Richard Harper (Plant Ecology, 2019)

Ability of known susceptibility SNPs to predict colorectal cancer risk for persons with and without a family history - Mark A. Jenkins; Aung K. Win; James G. Dowty; Robert J. MacInnis; Enes Makalic; Daniel F. Schmidt; Gillian S. Dite; Mirosl Kapuscinski; Mark Clendenning; Christophe Rosty; Ingrid M. Winship; Jon D. Emery; et al. (Familial Cancer, 2019)

Genomics detects population structure within and between ocean basins in a circumpolar seabird: The white‐chinned petrel - Kalinka Rexer‐Huber; Andrew J. Veale; Paulo Catry; Yves Cherel; Ludovic Dutoit; Yasmin Foster; John C. McEwan; Graham C. Parker; Richard A. Phillips; Peter G. Ryan; Andrew J. Stanworth; Tracey van Stijn; et al. (Molecular Ecology, 2019)
The Southern Ocean represents a continuous stretch of circumpolar marine habitat, but the potential physical and ecological drivers of evolutionary genetic differentiation across this vast ecosystem remain unclear. We tested for genetic structure across the full circumpolar range of the white‐chinned petrel ( Procellaria aequinoctialis ) to unravel the potential drivers of population differentiation and test alternative population differentiation hypotheses. Following range‐wide comprehensive sampling, we applied genomic (genotyping‐by‐sequencing or GBS; 60,709 loci) and standard mitochondrial‐marker approaches (cytochrome b and first domain of control region) to quantify genetic diversity within and among island populations, test for isolation by distance, and quantify the number of genetic clusters using neutral and outlier (non‐neutral) loci. Our results supported the multi‐region hypothesis, with a range of analyses showing clear three‐region genetic population structure, split by ocean basin, within two evolutionary units. The most significant differentiation between these regions confirmed previous work distinguishing New Zealand and nominate subspecies. Although there was little evidence of structure within the island groups of the Indian or Atlantic oceans, a small set of highly‐discriminatory outlier loci could assign petrels to ocean basin and potentially to island group, though the latter needs further verification. Genomic data hold the key to revealing substantial regional genetic structure within wide‐ranging circumpolar species previously assumed to be panmictic.

Trait structure and redundancy determine sensitivity to disturbance in marine fish communities - Matthew McLean; Arnaud Auber; Nicholas A. J. Graham; Peter Houk; Sébastien Villéger; Cyrille Violle; Wilfried Thuiller; Shaun K. Wilson; David Mouillot (Global Change Biology, 2019)
Trait diversity is believed to influence ecosystem dynamics through links between organismal traits and ecosystem processes. Theory predicts that key traits and high trait redundancy—large species richness and abundance supporting the same traits—can buffer communities against environmental disturbances. While experiments and data from simple ecological systems lend support, large‐scale evidence from diverse, natural systems under major disturbance is lacking. Here, using long‐term data from both temperate (English Channel) and tropical (Seychelles Islands) fishes, we show that sensitivity to disturbance depends on communities’ initial trait structure and initial trait redundancy. In both ecosystems, we found that increasing dominance by climatically vulnerable traits (e.g., small, fast‐growing pelagics/corallivores) rendered fish communities more sensitive to environmental change, while communities with higher trait redundancy were more resistant. To our knowledge, this is the first study demonstrating the influence of trait structure and redundancy on community sensitivity over large temporal and spatial scales in natural systems. Our results exemplify a consistent link between biological structure and community sensitivity that may be transferable across ecosystems and taxa and could help anticipate future disturbance impacts on biodiversity and ecosystem functioning.

Toward more robust plant–soil feedback research: Comment - François P. Teste; Paul Kardol; Benjamin L. Turner; David A. Wardle; Graham Zemunik; Michael Renton; Etienne Laliberté (Ecology, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Reproductive characteristics of the fishery important temperate demersal berycid Centroberyx gerrardi indicate greater reproductive output in regions of upwelling - Peter Graham Coulson; Jeffery Vincent Norriss; Gary Jackson; David Victor Fairclough (Fisheries Management and Ecology, 2019)
The reproductive biology of Centroberyx gerrardi (Günther) was investigated across ~2,000 km of its southern Australian distribution, encompassing different jurisdictions and varying environmental features. Greater gonad mass and prevalence of spawning fish, along with lower ratios of lengths at maturity:maximum lengths and ages at maturity:maximum ages, were identified at the western‐most (Capes) and eastern‐most (Great Australian Bight; GAB) regions. Across the study region, spawning peaks in summer/autumn, when water temperatures are warmest. Regional differences in potential “reproductive output,” while not consistent with the eastward decline in mean monthly water temperature, may instead be related to summer upwelling in the Capes and GAB, driving greater oceanic productivity prior to peak spawning, supporting larval survival. In autumn, the prevailing southward and eastward flowing, downwelling Leeuwin Current (LC) strengthens, providing a dispersal mechanism along the west and south Australian coasts, but limiting upwelling effects. Predicted changes in environmental conditions and their potential impacts on C. gerrardi are discussed, in particular how these factors may affect recruitment to stocks and fisheries, requiring a better understanding of source‐sink relationships for this species. As environmental changes occur, management strategies to sustain fish resources must adapt to spatially variable and changing reproductive output and be collaborative across jurisdictions.

Identification and characterization of a novel anti-inflammatory lipid isolated from Mycobacterium vaccae, a soil-derived bacterium with immunoregulatory and stress resilience properties - David G. Smith; Roberta Martinelli; Gurdyal S. Besra; Petr A. Illarionov; Istvan Szatmari; Peter Brazda; Mary A. Allen; Wenqing Xu; Xiang Wang; László Nagy; Robin D. Dowell; Graham A. W. Rook; et al. (Psychopharmacology, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Traditional materials from new sources – conflicts in analytical methods for calcium carbonate - David J. Belton; Graham J. Hickman; Carole C. Perry (Food Additives & Contaminants: Part A, 2019)

Cratons, kimberlites and diamonds: selected papers of the 11th International Kimberlite Conference - Thomas Stachel; D. Graham Pearson; Andrea Giuliani; Casey M. Hetman; Jaroslav (Jarek) Jakubec; Philip E. Janney; Bruce A. Kjarsgaard; Alan F. Kobussen; Jingao Liu; Oded Navon; Roberta Rudnick; David B. Snyder; et al. (Mineralogy and Petrology, 2018)

Mantle composition, age and geotherm beneath the Darby kimberlite field, west central Rae Craton - Garrett A. Harris; D. Graham Pearson; Jingao Liu; Matthew F. Hardman; David B. Snyder; Dave Kelsch (Mineralogy and Petrology, 2018)

Benthic boundary layer macrofauna from the upper slope of the Chatham Rise (SW Pacific) - Stefanie Kaiser; Anne‐Nina Lörz; Graham Bird; Marina Malyutina; David Bowden (Marine Ecology, 2018)
Benthic boundary layer (BBL) communities are a taxonomically and functionally diverse but poorly known component of deep‐sea environments. We investigated macrofaunal assemblages across the upper slope of the Chatham Rise (CR) in the south‐western Pacific in relation to location, depth and sediment variables. Using data from the TAN1116 voyage to the CR in austral spring 2011, we assessed variation in abundance, faunal composition and diversity of three BBL compartments: fully suprabenthic taxa, taxa with suprabenthic affinities and fully epibenthic taxa across taxonomic levels (phylum, class, order, family, genus and species). In total, eight samples were taken using an epibenthic sledge across three areas on the CR (Mernoo Gap, CR North and CR South) and at two depth ranges (400–600 and 900–1,000 m) distributed along a north to south as well as east to west axis, crossing different productivity gradients. In contrast to previous studies from the CR, there was no significant correlation between macrofaunal densities and sediment variables or depth. Species diversity of isopods and tanaidaceans was average to high, compared to other geographic regions, but did not show any significant pattern with location or depth. Most species in these two groups (~82%) were new to science, probably reflecting the paucity of sampling and taxonomic study of these faunal components in New Zealand waters. Our results suggest employing finer‐scale investigations across a range of temporal and spatial scales and at finer taxonomic resolution would greatly further our knowledge and understanding of patterns and processes shaping deep‐sea BBL community structure.

Climate and soils together regulate photosynthetic carbon isotope discrimination within C 3 plants worldwide - William K. Cornwell; Ian J. Wright; Joel Turner; Vincent Maire; Margaret M. Barbour; Lucas A. Cernusak; Todd Dawson; David Ellsworth; Graham D. Farquhar; Howard Griffiths; Claudia Keitel; Alexander Knohl; et al. (Global Ecology and Biogeography, 2018)
Aim Within C 3 plants, photosynthesis is a balance between CO 2 supply from the atmosphere via stomata and demand by enzymes within chloroplasts. This process is dynamic and a complex but crucial aspect of photosynthesis. We sought to understand the spatial pattern in CO 2 supply–demand balance on a global scale, via analysis of stable isotopes of carbon within leaves (Δ 13 C), which provide an integrative record of CO 2 drawdown during photosynthesis. Location Global Time period 1951–2011. Major taxa studied Vascular plants. Methods We assembled a database of leaf carbon isotope ratios containing 3,979 species–site combinations from across the globe, including 3,645 for C 3 species. We examined a wide array of potential climate and soil drivers of variation in Δ 13 C. Results The strongest drivers of carbon isotope discrimination at the global scale included atmospheric pressure, potential evapotranspiration and soil pH, which explained 44% of the variation in Δ 13 C. Addition of eight more climate and soil variables (each explaining small but highly significant amounts of variation) increased the explained variation to 60%. On top of this, the largest plant trait effect was leaf nitrogen per area, which explained 11% of Δ 13 C variation. Main conclusions: By considering variation in Δ 13 C at a considerably larger scale than previously, we were able to identify and quantify key drivers in CO 2 supply–demand balance previously unacknowledged. Of special note is the key role of soil properties, with greater discrimination on low‐pH and high‐silt soils. Unlike other plant traits, which show typically wide variation within sets of coexisting species, the global pattern in carbon stable isotope ratios is much more conservative; there is relatively narrow variation in time‐integrated CO 2 concentrations at the site of carboxylation among plants in a given soil and climate.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Environmental exposure and parental collection does not affect detection or semi-quantitative load assessment of bacteria in nasal swab specimens from children - Nada Townsi; Shannon J. Simpson; Chisha T. Sikazwe; Glenys R. Chidlow; Graham L. Hall; J. Jane Pillow; Andrew C. Wilson; David W. Smith; Ingrid A. Laing (Infectious Diseases, 2018)

A new genus of family Akanthophoreidae and new species of genus Parakanthophoreus Larsen & Araújo-Silva, 2014 (Crustacea: Tanaidacea: Tanaidomorpha) from the North Atlantic - Piotr Jóźwiak; David T. Drumm; Graham J. Bird; Magdalena Błażewicz (Marine Biodiversity, 2018)

Novel full-length major histocompatibility complex class I allele discovery and haplotype definition in pig-tailed macaques - Matthew R. Semler; Roger W. Wiseman; Julie A. Karl; Michael E. Graham; Samantha M. Gieger; David H. O’Connor (Immunogenetics, 2018)

A role for artificial night-time lighting in long-term changes in populations of 100 widespread macro-moths in UK and Ireland: a citizen-science study - John Fawcett Wilson; David Baker; Janet Cheney; Mike Cook; Martin Ellis; Roger Freestone; David Gardner; Graham Geen; Robin Hemming; Don Hodgers; Stephen Howarth; Ade Jupp; et al. (Journal of Insect Conservation, 2018)

Recreational sea fishing in Europe in a global context—Participation rates, fishing effort, expenditure, and implications for monitoring and assessment - Kieran Hyder; Marc Simon Weltersbach; Mike Armstrong; Keno Ferter; Bryony Townhill; Anssi Ahvonen; Robert Arlinghaus; Andrei Baikov; Manuel Bellanger; Janis Birzaks; Trude Borch; Giulia Cambie; et al. (Fish and Fisheries, 2018)
Marine recreational fishing ( MRF ) is a high‐participation activity with large economic value and social benefits globally, and it impacts on some fish stocks. Although reporting MRF catches is a European Union legislative requirement, estimates are only available for some countries. Here, data on numbers of fishers, participation rates, days fished, expenditures, and catches of two widely targeted species were synthesized to provide European estimates of MRF and placed in the global context. Uncertainty assessment was not possible due to incomplete knowledge of error distributions; instead, a semi‐quantitative bias assessment was made. There were an estimated 8.7 million European recreational sea fishers corresponding to a participation rate of 1.6%. An estimated 77.6 million days were fished, and expenditure was €5.9 billion annually. There were higher participation, numbers of fishers, days fished and expenditure in the Atlantic than the Mediterranean, but the Mediterranean estimates were generally less robust. Comparisons with other regions showed that European MRF participation rates and expenditure were in the mid‐range, with higher participation in Oceania and the United States, higher expenditure in the United States, and lower participation and expenditure in South America and Africa. For both northern European sea bass ( Dicentrarchus labrax , Moronidae) and western Baltic cod ( Gadus morhua , Gadidae) stocks, MRF represented 27% of the total removals. This study highlights the importance of MRF and the need for bespoke, regular and statistically sound data collection to underpin European fisheries management. Solutions are proposed for future MRF data collection in Europe and other regions to support sustainable fisheries management.

Phylogenetic scale in ecology and evolution - Catherine H. Graham; David Storch; Antonin Machac (Global Ecology and Biogeography, 2018)
Aim Many important patterns and processes vary across the phylogeny and depend on phylogenetic scale. Nonetheless, phylogenetic scale has never been formally conceptualized, and its potential remains largely unexplored. Here, we formalize the concept of phylogenetic scale, review how phylogenetic scale has been considered across multiple fields and provide practical guidelines for the use of phylogenetic scale to address a range of biological questions. Innovation We summarize how phylogenetic scale has been treated in macroevolution, community ecology, biogeography and macroecology, illustrating how it can inform, and possibly resolve, some of the longstanding controversies in these fields. To promote the concept empirically, we define phylogenetic grain and extent, scale dependence, scaling and the domains of phylogenetic scale. We illustrate how existing phylogenetic data and statistical tools can be used to investigate the effects of scale on a variety of well‐known patterns and processes, including diversification rates, community structure, niche conservatism or species‐abundance distributions. Main conclusions Explicit consideration of phylogenetic scale can provide new and more complete insight into many longstanding questions across multiple fields (macroevolution, community ecology, biogeography and macroecology). Building on the existing resources and isolated efforts across fields, future research centred on phylogenetic scale might enrich our understanding of the processes that together, but over different scales, shape the diversity of life.

Designing connected marine reserves in the face of global warming - Jorge G. Álvarez‐Romero; Adrián Munguía‐Vega; Maria Beger; Maria del Mar Mancha‐Cisneros; Alvin N. Suárez‐Castillo; Georgina G. Gurney; Robert L. Pressey; Leah R. Gerber; Hem Nalini Morzaria‐Luna; Héctor Reyes‐Bonilla; Vanessa M. Adams; Melanie Kolb; et al. (Global Change Biology, 2018)
Marine reserves are widely used to protect species important for conservation and fisheries and to help maintain ecological processes that sustain their populations, including recruitment and dispersal. Achieving these goals requires well‐connected networks of marine reserves that maximize larval connectivity, thus allowing exchanges between populations and recolonization after local disturbances. However, global warming can disrupt connectivity by shortening potential dispersal pathways through changes in larval physiology. These changes can compromise the performance of marine reserve networks, thus requiring adjusting their design to account for ocean warming. To date, empirical approaches to marine prioritization have not considered larval connectivity as affected by global warming. Here, we develop a framework for designing marine reserve networks that integrates graph theory and changes in larval connectivity due to potential reductions in planktonic larval duration ( PLD ) associated with ocean warming, given current socioeconomic constraints. Using the Gulf of California as case study, we assess the benefits and costs of adjusting networks to account for connectivity, with and without ocean warming. We compare reserve networks designed to achieve representation of species and ecosystems with networks designed to also maximize connectivity under current and future ocean‐warming scenarios. Our results indicate that current larval connectivity could be reduced significantly under ocean warming because of shortened PLD s. Given the potential changes in connectivity, we show that our graph‐theoretical approach based on centrality (eigenvector and distance‐weighted fragmentation) of habitat patches can help design better‐connected marine reserve networks for the future with equivalent costs. We found that maintaining dispersal connectivity incidentally through representation‐only reserve design is unlikely, particularly in regions with strong asymmetric patterns of dispersal connectivity. Our results support previous studies suggesting that, given potential reductions in PLD due to ocean warming, future marine reserve networks would require more and/or larger reserves in closer proximity to maintain larval connectivity.

Ecological controls of mammalian diversification vary with phylogenetic scale - Antonin Machac; Catherine H. Graham; David Storch (Global Ecology and Biogeography, 2018)
Aim Diversity dynamics remain controversial. Here, we examine these dynamics, together with the ecological factors governing them, across mammalian clades of different ages and sizes, representing different phylogenetic scales. Specifically, we investigate whether the dynamics are bounded or unbounded, biotically or abiotically regulated, stochastic or ecologically deterministic. Location Worldwide. Time period 150 Myr. Major taxa studied Mammals. Methods Integrating the newest phylogenetic and distributional data by means of several distinct methods, we study the ecology of mammalian diversification within a predictive framework, inspired by classic theory. Specifically, we evaluate the effects of several classes of factors, including climate, topography, geographical area, rates of climatic‐niche evolution, and regional coexistence between related and unrelated species. Next, we determine whether the relative effects of these factors change systematically across clades representing different phylogenetic scales. Results We find that young clades diversify at approximately constant rates, medium‐sized clades show diversification slowdowns, and large clades are mostly saturated, suggesting that diversification dynamics change as clades grow and accumulate species. We further find that diversification slowdowns intensify with the degree of regional coexistence between related species, presumably because increased competition for regional resources suppresses the diversification process. The richness at which clades eventually saturate depends on climate; clades residing in tropical climates saturate at low richness, implying that niches become progressively densely packed towards the tropics. Main conclusions The diversification process is influenced by a variety of ecological factors, whose relative effects change across phylogenetic scales, producing scale‐dependent dynamics. Different segments of the same phylogeny might therefore support seemingly conflicting results (bounded or unbounded, biotically or abiotically regulated, stochastic or ecologically deterministic diversification), which might have contributed to several outstanding controversies in the field. These conflicts can be reconciled, however, when accounting for phylogenetic scale, which might, in turn, produce a more integrated understanding of global diversity dynamics.

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Trends in anecdotal fox sightings in Tasmania accounted for by psychological factors - Clive A. Marks; Malcolm Clark; David Obendorf; Graham P. Hall; Inês Soares; Filipe Pereira (Conservation Biology, 2017)
There has been little evaluation of anecdotal sightings as a means to confirm new incursions of invasive species. This paper explores the potential for equivocal information communicated by the media to account for patterns of anecdotal reports. In 2001, it was widely reported that red foxes ( Vulpes vulpes ) had been deliberately released in the island state of Tasmania (Australia), although this claim was later revealed to be baseless. Regardless, by 2013 a total of 3153 anecdotal fox sightings had been reported by members of the public, which implied their distribution was wide. For each month in 2001–2003, we defined a monthly media index (MMI) of fox‐related media coverage, an index of their relative seasonal abundance (abundance), and a factor denoting claims of fox evidence (claimed evidence) regardless of its evidentiary quality. We fitted a generalized linear model with Poisson error for monthly totals of anecdotal sightings with factors of year and claimed evidence and covariates of MMI, abundance, and hours of darkness. The collective effect of psychological factors (MMI, claimed evidence, and year) relative to biophysical factors (photoperiod and abundance) was highly significant (χ 2 = 122.1, df = 6, p p = 0.15). An annual index of fox media from 2001 to 2010 was strongly associated with the yearly tally of anecdotal sightings ( p = 0.018). The odds ratio of sightings ranked as reliable by the fox eradication program in any year decreased exponentially at a rate of 0.00643 as the total number of sightings increased ( p

Interspecific hybridization causes long‐term phylogenetic discordance between nuclear and mitochondrial genomes in freshwater fishes - Graham P. Wallis; Sophia R. Cameron‐Christie; Hannah L. Kennedy; Gemma Palmer; Tessa R. Sanders; David J. Winter (Molecular Ecology, 2017)
Classification, phylogeography and the testing of evolutionary hypotheses rely on correct estimation of species phylogeny. Early molecular phylogenies often relied on mt DNA alone, which acts as a single linkage group with one history. Over the last decade, the use of multiple nuclear sequences has often revealed conflict among gene trees. This observation can be attributed to hybridization, lineage sorting, paralogy or selection. Here, we use 54 groups of fishes from 48 studies to estimate the degree of concordance between mitochondrial and nuclear gene trees in two ecological grades of fishes: marine and freshwater. We test the hypothesis that freshwater fish phylogenies should, on average, show more discordance because of their higher propensity for hybridization in the past. In keeping with this idea, concordance between mitochondrial and nuclear gene trees (as measured by proportion of components shared) is on average 50% higher in marine fishes. We discuss why this difference almost certainly results from introgression caused by greater historical hybridization among lineages in freshwater groups, and further emphasize the need to use multiple nuclear genes, and identify conflict among them, in estimation of species phylogeny.

White-chinned petrel population estimate, Disappointment Island (Auckland Islands) - Kalinka Rexer-Huber; Graham C. Parker; Paul M. Sagar; David R. Thompson (Polar Biology, 2017)

Improved full-length killer cell immunoglobulin-like receptor transcript discovery in Mauritian cynomolgus macaques - Trent M. Prall; Michael E. Graham; Julie A. Karl; Roger W. Wiseman; Adam J. Ericsen; Muthuswamy Raveendran; R. Alan Harris; Donna M. Muzny; Richard A. Gibbs; Jeffrey Rogers; David H. O’Connor (Immunogenetics, 2017)

Major histocompatibility complex haplotyping and long-amplicon allele discovery in cynomolgus macaques from Chinese breeding facilities - Julie A. Karl; Michael E. Graham; Roger W. Wiseman; Katelyn E. Heimbruch; Samantha M. Gieger; Gaby G. M. Doxiadis; Ronald E. Bontrop; David H. O’Connor (Immunogenetics, 2017)

Deterministic influences exceed dispersal effects on hydrologically‐connected microbiomes - Emily B. Graham; Alex R. Crump; Charles T. Resch; Sarah Fansler; Evan Arntzen; David W. Kennedy; Jim K. Fredrickson; James C. Stegen (Environmental Microbiology, 2017)
Summary Subsurface groundwater‐surface water mixing zones (hyporheic zones) have enhanced biogeochemical activity, but assembly processes governing subsurface microbiomes remain a critical uncertainty in understanding hyporheic biogeochemistry. To address this obstacle, we investigated (a) biogeographical patterns in attached and waterborne microbiomes across three hydrologically‐connected, physicochemically‐distinct zones (inland hyporheic, nearshore hyporheic and river); (b) assembly processes that generated these patterns; (c) groups of organisms that corresponded to deterministic changes in the environment; and (d) correlations between these groups and hyporheic metabolism. All microbiomes remained dissimilar through time, but consistent presence of similar taxa suggested dispersal and/or common selective pressures among zones. Further, we demonstrated a pronounced impact of deterministic assembly in all microbiomes as well as seasonal shifts from heterotrophic to autotrophic microorganisms associated with increases in groundwater discharge. The abundance of one statistical cluster of organisms increased with active biomass and respiration, revealing organisms that may strongly influence hyporheic biogeochemistry. Based on our results, we propose a conceptualization of hyporheic zone metabolism in which increased organic carbon concentrations during surface water intrusion support heterotrophy, which succumbs to autotrophy under groundwater discharge. These results provide new opportunities to enhance microbially‐explicit ecosystem models describing hyporheic zone biogeochemistry and its influence over riverine ecosystem function.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

An assessment of the central disposition of intranasally administered insulin lispro in the cerebrospinal fluid of healthy volunteers and beagle dogs - Stephen Lowe; Emanuele Sher; Graham Wishart; Kimberley Jackson; Eunice Yuen; Claire Brittain; Siew Chinn Fong; David O. Clarke; William H. Landschulz (Drug Delivery and Translational Research, 2017)

The city as a refuge for insect pollinators - Damon M. Hall; Gerardo R. Camilo; Rebecca K. Tonietto; Jeff Ollerton; Karin Ahrné; Mike Arduser; John S. Ascher; Katherine C. R. Baldock; Robert Fowler; Gordon Frankie; Dave Goulson; Bengt Gunnarsson; et al. (Conservation Biology, 2017)
Research on urban insect pollinators is changing views on the biological value and ecological importance of cities. The abundance and diversity of native bee species in urban landscapes that are absent in nearby rural lands evidence the biological value and ecological importance of cities and have implications for biodiversity conservation. Lagging behind this revised image of the city are urban conservation programs that historically have invested in education and outreach rather than programs designed to achieve high‐priority species conservation results. We synthesized research on urban bee species diversity and abundance to determine how urban conservation could be repositioned to better align with new views on the ecological importance of urban landscapes. Due to insect pollinators’ relatively small functional requirements—habitat range, life cycle, and nesting behavior—relative to larger mammals, we argue that pollinators put high‐priority and high‐impact urban conservation within reach. In a rapidly urbanizing world, transforming how environmental managers view the city can improve citizen engagement and contribute to the development of more sustainable urbanization.

Demography and ecology of southern right whales Eubalaena australis wintering at sub-Antarctic Campbell Island, New Zealand - Leigh G. Torres; Will Rayment; Carlos Olavarría; David R. Thompson; Brittany Graham; C. Scott Baker; Nathalie Patenaude; Sarah Jane Bury; Laura Boren; Graham Parker; Emma L. Carroll (Polar Biology, 2017)

Detecting spatial regimes in ecosystems - Shana M. Sundstrom; Tarsha Eason; R. John Nelson; David G. Angeler; Chris Barichievy; Ahjond S. Garmestani; Nicholas A.J. Graham; Dean Granholm; Lance Gunderson; Melinda Knutson; Kirsty L. Nash; Trisha Spanbauer; et al. (Ecology Letters, 2017)
Research on early warning indicators has generally focused on assessing temporal transitions with limited application of these methods to detecting spatial regimes. Traditional spatial boundary detection procedures that result in ecoregion maps are typically based on ecological potential (i.e. potential vegetation), and often fail to account for ongoing changes due to stressors such as land use change and climate change and their effects on plant and animal communities. We use Fisher information, an information theory‐based method, on both terrestrial and aquatic animal data (U.S. Breeding Bird Survey and marine zooplankton) to identify ecological boundaries, and compare our results to traditional early warning indicators, conventional ecoregion maps and multivariate analyses such as nMDS and cluster analysis. We successfully detected spatial regimes and transitions in both terrestrial and aquatic systems using Fisher information. Furthermore, Fisher information provided explicit spatial information about community change that is absent from other multivariate approaches. Our results suggest that defining spatial regimes based on animal communities may better reflect ecological reality than do traditional ecoregion maps, especially in our current era of rapid and unpredictable ecological change.

Developmental Trajectory of Beta Cortical Oscillatory Activity During a Knee Motor Task - Max J. Kurz; Amy L. Proskovec; James E. Gehringer; Katherine M. Becker; David J. Arpin; Elizabeth Heinrichs-Graham; Tony W. Wilson (Brain Topography, 2016)

Effects of experimentally elevated egg cortisol on offspring traits in two species of wild Pacific salmon - Natalie M. Sopinka; Scott G. Hinch; Stephen J. Healy; Graham D. Raby; David A. Patterson (Environmental Biology of Fishes, 2016)

The Microbiota, Immunoregulation, and Mental Health: Implications for Public Health - Christopher A. Lowry; David G. Smith; Philip H. Siebler; Dominic Schmidt; Christopher E. Stamper; James E. Hassell; Paula S. Yamashita; James H. Fox; Stefan O. Reber; Lisa A. Brenner; Andrew J. Hoisington; Teodor T. Postolache; et al. (Current Environmental Health Reports, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Search for an astronomical site in Kenya (SASKYA) using climate reanalyses and high-resolution meteorological model data - Edward Graham; Richard Vaughan; David A. H. Buckley; Koi Tirima (Theoretical and Applied Climatology, 2016)

A framework for understanding climate change impacts on coral reef social–ecological systems - Joshua Eli Cinner; Morgan Stuart Pratchett; Nicholas Anthony James Graham; Vanessa Messmer; Mariana Menezes Prata Bezerra Fuentes; Tracy Ainsworth; Natalie Ban; Line Kolind Bay; Jessica Blythe; Delphine Dissard; Simon Dunn; Louisa Evans; et al. (Regional Environmental Change, 2016)

Can climate projection uncertainty be constrained over Africa using metrics of contemporary performance? - David P. Rowell; Catherine A. Senior; Michael Vellinga; Richard J. Graham (Climatic Change, 2016)

No strong correlations between serum cytokine levels, CMV serostatus and hand-grip strength in older subjects in the Berlin BASE-II cohort - David Goldeck; Graham Pawelec; Kristina Norman; Elisabeth Steinhagen-Thiessen; Lilly Oettinger; Karin Haehnel; Ilja Demuth (Biogerontology, 2016)

Disruption and eradication of P. aeruginosa biofilms using nitric oxide-releasing chitosan oligosaccharides - Katelyn P. Reighard; David B. Hill; Graham A. Dixon; Brittany V. Worley; Mark H. Schoenfisch (Biofouling, 2015)

Dependence of Two-Photon eGFP Bleaching on Femtosecond Pulse Spectral Amplitude and Phase - David J. L. Graham; Shu-Fen Tseng; Jer-Tsong Hsieh; David J. Chen; George Alexandrakis (Journal of Fluorescence, 2015)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Size-assortative mating in simultaneous hermaphrodites: an experimental test and a meta-analysis - Stuart Graham; Elodie Chapuis; Stefania Meconcelli; Nicolas Bonel; Kevin Sartori; Ananda Christophe; Pilar Alda; Patrice David; Tim Janicke (Behavioral Ecology and Sociobiology, 2015)

The macroecology of phylogenetically structured hummingbird–plant networks - Ana M. Martín González; Bo Dalsgaard; David Nogués‐Bravo; Catherine H. Graham; Matthias Schleuning; Pietro K. Maruyama; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Severino Mendes de Azevedo; Andrea C. Baquero; et al. (Global Ecology and Biogeography, 2015)
Aim To investigate the association between hummingbird–plant network structure and species richness, phylogenetic signal on species' interaction pattern, insularity and historical and current climate. Location Fifty‐four communities along a c . 10,000 km latitudinal gradient across the A mericas (39° N –32° S ), ranging from sea level to c . 3700 m a.s.l., located on the mainland and on islands and covering a wide range of climate regimes. Methods We measured the level of specialization and modularity in mutualistic plant–hummingbird interaction networks. Using an ordinary least squares multimodel approach, we examined the influence of species richness, phylogenetic signal, insularity and current and historical climate conditions on network structure (null‐model‐corrected specialization and modularity). Results Phylogenetically related species, especially plants, showed a tendency to interact with a similar array of mutualistic partners. The spatial variation in network structure exhibited a constant association with species phylogeny ( R 2 = 0.18–0.19); however, network structure showed the strongest association with species richness and environmental factors ( R 2 = 0.20–0.44 and R 2 = 0.32–0.45, respectively). Specifically, higher levels of specialization and modularity were associated with species‐rich communities and communities in which closely related hummingbirds visited distinct sets of flowering species. On the mainland, specialization was also associated with warmer temperatures and greater historical temperature stability. Main conclusions Our results confirm the results of previous macroecological studies of interaction networks which have highlighted the importance of species richness and the environment in determining network structure. Additionally, for the first time, we report an association between network structure and species phylogenetic signal at a macroecological scale, indicating that high specialization and modularity are associated with high interspecific competition among closely related hummingbirds, subdividing the floral niche. This suggests a tighter co‐evolutionary association between hummingbirds and their plants than in previously studied plant–bird mutualistic systems.

Impact of age, sex and CMV-infection on peripheral T cell phenotypes: results from the Berlin BASE-II Study - Svetlana Di Benedetto; Evelyna Derhovanessian; Elisabeth Steinhagen-Thiessen; David Goldeck; Ludmila Müller; Graham Pawelec (Biogerontology, 2015)

Quinolinic acid/tryptophan ratios predict neurological disease in SIV-infected macaques and remain elevated in the brain under cART - Julia L. Drewes; Kelly A. Meulendyke; Zhaohao Liao; Kenneth W. Witwer; Lucio Gama; Ceereena Ubaida-Mohien; Ming Li; Francesca M. Notarangelo; Patrick M. Tarwater; Robert Schwarcz; David R. Graham; M. Christine Zink (Journal of NeuroVirology, 2015)

The “nutrient pump:” Iron‐poor sediments fuel low nitrogen‐to‐phosphorus ratios and cyanobacterial blooms in polymictic lakes - Diane M. Orihel; David W. Schindler; Nathaniel C. Ballard; Mark D. Graham; David W. O'Connell; Lindsey R. Wilson; Rolf D. Vinebrooke (Limnology and Oceanography, 2015)
Several lines of evidence from a eutrophic lake show how polymixis enables phosphorus (P) released from anoxic, iron (Fe)‐poor sediments to lower nitrogen‐to‐phosphorus (N : P) ratios and stimulate cyanobacterial blooms. Detailed sediment analyses revealed extensive formation of Fe sulfides, which suppressed porewater Fe levels and prevented sequestration of P in Fe minerals. Experimental additions of Fe significantly decreased the flux of dissolved P from warm, anoxic sediments, increasing N : P ratios in porewater and overlying water. The net midsummer effect of polymixis and P release from Fe‐poor sediments quickly doubled the total P in the euphotic zone during a period of very low external P loading. This internal “nutrient pump” decreased N : P in surface waters and led to a cyanobacterial bloom comprised primarily of diazotrophic Anabaena and Aphanizomenon spp. along with nonheterocystous and potentially toxic Microcystis icthyoblabe and Woronichinia naegelianum . Concentrations of the cyanotoxin, microcystin, in this lake were typically elevated during, or shortly after, episodes of internal P loading. Our study demonstrates an important mechanism underlying the increasing cyanobacterial dominance of weakly stratified eutrophic north temperate lakes, and warns of further increases under a warming climate.

Reply to “Letter to the Editor: Consistency Among Musculoskeletal Models: Caveat Utilitor” - David W. Wagner; Vahagn Stepanyan; James M. Shippen; Matthew S. DeMers; Robin S. Gibbons; Brian J. Andrews; Graham H. Creasey; Gary S. Beaupre (Annals of Biomedical Engineering, 2015)

Minimizing the biodiversity impact of Neotropical oil palm development - James J. Gilroy; Graham W. Prescott; Johann S. Cardenas; Pamela González del Pliego Castañeda; Andrés Sánchez; Luis E. Rojas‐Murcia; Claudia A. Medina Uribe; Torbjørn Haugaasen; David P. Edwards (Global Change Biology, 2015)
Oil palm agriculture is rapidly expanding in the Neotropics, at the expense of a range of natural and seminatural habitats. A key question is how this expansion should be managed to reduce negative impacts on biodiversity. Focusing on the Llanos of Colombia, a mixed grassland–forest system identified as a priority zone for future oil palm development, we survey communities of ants, dung beetles, birds and herpetofauna occurring in oil palm plantations and the other principal form of agriculture in the region – improved cattle pasture – together with those of surrounding natural forests. We show that oil palm plantations have similar or higher species richness across all four taxonomic groups than improved pasture. For dung beetles, species richness in oil palm was equal to that of forest, whereas the other three taxa had highest species richness in forests. Hierarchical modelling of species occupancy probabilities indicated that oil palm plantations supported a higher proportion of species characteristic of forests than did cattle pastures. Across the bird community, occupancy probabilities within oil palm were positively influenced by increasing forest cover in a surrounding 250 m radius, whereas surrounding forest cover did not strongly influence the occurrence of other taxonomic groups in oil palm. Overall, our results suggest that the conversion of existing improved pastures to oil palm has limited negative impacts on biodiversity. As such, existing cattle pastures of the Colombian Llanos could offer a key opportunity to meet governmental targets for oil palm development without incurring significant biodiversity costs. Our results also highlight the value of preserving remnant forests within these agricultural landscapes, protecting high biodiversity and exporting avian ‘spill‐over’ effects into oil palm plantations.

Stoichiometry and temperature sensitivity of methanogenesis and CO 2 production from saturated polygonal tundra in Barrow, Alaska - Taniya Roy Chowdhury; Elizabeth M. Herndon; Tommy J. Phelps; Dwayne A. Elias; Baohua Gu; Liyuan Liang; Stan D. Wullschleger; David E. Graham (Global Change Biology, 2015)
Arctic permafrost ecosystems store ~50% of global belowground carbon (C) that is vulnerable to increased microbial degradation with warmer active layer temperatures and thawing of the near surface permafrost. We used anoxic laboratory incubations to estimate anaerobic CO 2 production and methanogenesis in active layer (organic and mineral soil horizons) and permafrost samples from center, ridge and trough positions of water‐saturated low‐centered polygon in Barrow Environmental Observatory, Barrow AK , USA . Methane ( CH 4 ) and CO 2 production rates and concentrations were determined at −2, +4, or +8 °C for 60 day incubation period. Temporal dynamics of CO 2 production and methanogenesis at −2 °C showed evidence of fundamentally different mechanisms of substrate limitation and inhibited microbial growth at soil water freezing points compared to warmer temperatures. Nonlinear regression better modeled the initial rates and estimates of Q 10 values for CO 2 that showed higher sensitivity in the organic‐rich soils of polygon center and trough than the relatively drier ridge soils. Methanogenesis generally exhibited a lag phase in the mineral soils that was significantly longer at −2 °C in all horizons. Such discontinuity in CH 4 production between −2 °C and the elevated temperatures (+4 and +8 °C) indicated the insufficient representation of methanogenesis on the basis of Q 10 values estimated from both linear and nonlinear models. Production rates for both CH 4 and CO 2 were substantially higher in organic horizons (20% to 40% wt. C) at all temperatures relative to mineral horizons ( CO 2 than the active layer and negligible CH 4 . High concentrations of initial exchangeable Fe( II ) and increasing accumulation rates signified the role of iron as terminal electron acceptors for anaerobic C degradation in the mineral horizons.

Home-range allometry in coral reef fishes: comparison to other vertebrates, methodological issues and management implications - Kirsty L. Nash; Justin Q. Welsh; Nicholas A. J. Graham; David R. Bellwood (Oecologia, 2015)

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

Projected changes in reported campylobacteriosis and cryptosporidiosis rates as a function of climate change: a New Zealand study - Graham McBride; Andrew Tait; David Slaney (Stochastic Environmental Research and Risk Assessment, 2014)

Impact of minocycline on cerebrospinal fluid markers of oxidative stress, neuronal injury, and inflammation in HIV-seropositive individuals with cognitive impairment - Ned Sacktor; Sachiko Miyahara; Scott Evans; Giovanni Schifitto; Bruce Cohen; Norman Haughey; Julia L. Drewes; David Graham; M.Christine Zink; Caroline Anderson; Avindra Nath; Carlos A. Pardo; et al. (Journal of NeuroVirology, 2014)

Combination fluconazole/paroxetine treatment is neuroprotective despite ongoing neuroinflammation and viral replication in an SIV model of HIV neurological disease - Kelly A. Meulendyke; Suzanne E. Queen; Elizabeth L. Engle; Erin N. Shirk; Jiayang Liu; Joseph P. Steiner; Avindra Nath; Patrick M. Tarwater; David R. Graham; Joseph L. Mankowski; M. Christine Zink (Journal of NeuroVirology, 2014)

Identification of putative biomarkers for HIV-associated neurocognitive impairment in the CSF of HIV-infected patients under cART therapy determined by mass spectrometry - Adriana Bora; Ceereena Ubaida Mohien; Raghothama Chaerkady; Linda Chang; Richard Moxley; Ned Sacktor; Norman Haughey; Justin C. McArthur; Robert Cotter; Avindra Nath; David R. Graham (Journal of NeuroVirology, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Aquatic Macrophytes Alter Metabolism and Nutrient Cycling in Lowland Streams - Jonathan M. O’Brien; Joanna L. Lessard; David Plew; S. Elizabeth Graham; Angus R. McIntosh (Ecosystems, 2014)

Discontinuities, cross‐scale patterns, and the organization of ecosystems - Kirsty L. Nash; Craig R. Allen; David G. Angeler; Chris Barichievy; Tarsha Eason; Ahjond S. Garmestani; Nicholas A. J. Graham; Dean Granholm; Melinda Knutson; R. John Nelson; Magnus Nyström; Craig A. Stow; et al. (Ecology, 2014)
Ecological structures and processes occur at specific spatiotemporal scales, and interactions that occur across multiple scales mediate scale‐specific (e.g., individual, community, local, or regional) responses to disturbance. Despite the importance of scale, explicitly incorporating a multi‐scale perspective into research and management actions remains a challenge. The discontinuity hypothesis provides a fertile avenue for addressing this problem by linking measureable proxies to inherent scales of structure within ecosystems. Here we outline the conceptual framework underlying discontinuities and review the evidence supporting the discontinuity hypothesis in ecological systems. Next we explore the utility of this approach for understanding cross‐scale patterns and the organization of ecosystems by describing recent advances for examining nonlinear responses to disturbance and phenomena such as extinctions, invasions, and resilience. To stimulate new research, we present methods for performing discontinuity analysis, detail outstanding knowledge gaps, and discuss potential approaches for addressing these gaps.

How flies respond to honey bee pheromone: the role of the foraging gene on reproductive response to queen mandibular pheromone - Alison L. Camiletti; David N. Awde; Graham J. Thompson (The Science of Nature, 2014)

Muscle strength and its relationship with skeletal muscle mass indices as determined by segmental bio-impedance analysis - Omid Alizadehkhaiyat; David H. Hawkes; Graham J. Kemp; Anthony Howard; Simon P. Frostick (European Journal of Applied Physiology, 2014)

Influence of a wastewater treatment plant on mercury contamination and sediment characteristics in Vidy Bay (Lake Geneva, Switzerland) - Elena Gascon Diez; Andrea Garcia Bravo; Natacha à Porta; Matthieu Masson; Neil D. Graham; Serge Stoll; Yosef Akhtman; David Amouroux; Jean-Luc Loizeau (Aquatic Sciences, 2013)

Can synchronizing feather-based measures of corticosterone and stable isotopes help us better understand habitat–physiology relationships? - Graham D. Fairhurst; Matthias Vögeli; David Serrano; Antonio Delgado; José L. Tella; Gary R. Bortolotti (Oecologia, 2013)

Adenosine Triphosphate Released from HIV-Infected Macrophages Regulates Glutamatergic Tone and Dendritic Spine Density on Neurons - Luis B. Tovar-y-Romo; Dennis L. Kolson; Veera Venkata Ratnam Bandaru; Julia L. Drewes; David R. Graham; Norman J. Haughey (Journal of Neuroimmune Pharmacology, 2013)

Replication and fine mapping of asthma-associated loci in individuals of African ancestry - David B. Kantor; Cameron D. Palmer; Taylor R. Young; Yan Meng; Zofia K. Gajdos; Helen Lyon; Alkes L. Price; Samuela Pollack; Stephanie J. London; Laura R. Loehr; Lewis J. Smith; Rajesh Kumar; et al. (Human Genetics, 2013)

Consistency Among Musculoskeletal Models: Caveat Utilitor - David W. Wagner; Vahagn Stepanyan; James M. Shippen; Matthew S. DeMers; Robin S. Gibbons; Brian J. Andrews; Graham H. Creasey; Gary S. Beaupre (Annals of Biomedical Engineering, 2013)

Cross-scale Habitat Structure Drives Fish Body Size Distributions on Coral Reefs - Kirsty L. Nash; Nicholas A. J. Graham; Shaun K. Wilson; David R. Bellwood (Ecosystems, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Phytochemistry predicts habitat selection by an avian herbivore at multiple spatial scales - Graham G. Frye; John W. Connelly; David D. Musil; Jennifer S. Forbey (Ecology, 2013)
Animal habitat selection is a process that functions at multiple, hierarchically structured spatial scales. Thus multi‐scale analyses should be the basis for inferences about factors driving the habitat selection process. Vertebrate herbivores forage selectively on the basis of phytochemistry, but few studies have investigated the influence of selective foraging (i.e., fine‐scale habitat selection) on habitat selection at larger scales. We tested the hypothesis that phytochemistry is integral to the habitat selection process for vertebrate herbivores. We predicted that habitats selected at three spatial scales would be characterized by higher nutrient concentrations and lower concentrations of plant secondary metabolites (PSMs) than unused habitats. We used the Greater Sage‐Grouse ( Centrocercus urophasianus ), an avian herbivore with a seasonally specialized diet of sagebrush, to test our hypothesis. Sage‐Grouse selected a habitat type (black sagebrush, Artemisia nova ) with lower PSM concentrations than the alternative (Wyoming big sagebrush, A. tridentata wyomingensis ). Within black sagebrush habitat, Sage‐Grouse selected patches and individual plants within those patches that were higher in nutrient concentrations and lower in PSM concentrations than those not used. Our results provide the first evidence for multi‐scale habitat selection by an avian herbivore on the basis of phytochemistry, and they suggest that phytochemistry may be a fundamental driver of habitat selection for vertebrate herbivores.

Driving on ice: impaired driving skills in current methamphetamine users - David Bosanquet; Hamish G. MacDougall; Stephen J. Rogers; Graham A. Starmer; Rebecca McKetin; Alexander Blaszczynski; Iain S. McGregor (Psychopharmacology, 2013)

Comparative mapping in watermelon [Citrullus lanatus (Thunb.) Matsum. et Nakai] - Katherine Sandlin; Jason Prothro; Adam Heesacker; Nelly Khalilian; Rebecca Okashah; Wenwen Xiang; Eleni Bachlava; David G. Caldwell; Chris A. Taylor; Danelle K. Seymour; Victoria White; Eva Chan; et al. (Theoretical and Applied Genetics, 2012)

W olbachia in a major African crop pest increases susceptibility to viral disease rather than protects - Robert I. Graham; David Grzywacz; Wilfred L. Mushobozi; Kenneth Wilson (Ecology Letters, 2012)
W olbachia are common vertically transmitted endosymbiotic bacteria found in S podoptera exempta ), which show that the prevalence and intensity of infection with a nucleopolydrovirus ( SpexNPV ) is positively associated with infection with three strains of W olbachia . We also use laboratory bioassays to demonstrate that infection with one of these strains, a male‐killer, increases host mortality due to SpexNPV by 6–14 times. These findings suggest that rather than protecting their lepidopteran host from viral infection, W olbachia instead make them more susceptible. This finding potentially has implications for the biological control of other insect crop pests.

Erratum to: Microalgal fatty acid composition: implications for biodiesel quality - Graham Robert Stansell; Vincent Myles Gray; Stuart David Sym (Journal of Applied Phycology, 2012)

Microalgal fatty acid composition: implications for biodiesel quality - Graham Robert Stansell; Vincent Myles Gray; Stuart David Sym (Journal of Applied Phycology, 2012)

Oxygen isotope heterogeneity of the mantle beneath the Canary Islands: a discussion of the paper of Gurenko et al. - James M. D. Day; Colin G. Macpherson; David Lowry; D. Graham Pearson (Contributions to Mineralogy and Petrology, 2012)

Early Minocycline Treatment Prevents a Decrease in Striatal Dopamine in an SIV Model of HIV-Associated Neurological Disease - Kelly A. Meulendyke; Mikhail V. Pletnikov; Elizabeth L. Engle; Patrick M. Tarwater; David R. Graham; M. Christine Zink (Journal of Neuroimmune Pharmacology, 2012)

Evaluation of Potential Responses to Invasive Non‐Native Species with Structured Decision Making - SHUANG LIU; TERRY WALSHE; GRAHAM LONG; DAVID COOK (Conservation Biology, 2012)
In managing invasions and colonizations of non‐native species, eradication or control efforts must proceed quickly. There are 2 challenges in taking such quick action. First, managers frequently have to choose among complex and often competing environmental, social, and economic objectives. Second, the effects are highly uncertain. We applied participatory structured decision making (SDM) to develop a response plan for the recent invasion of non‐native myrtle rust ( Uredo rangelii ) in Australia. Structured decision making breaks a complex decision process into 5 steps: identify problems (i.e., decisions to be made), formulate objectives, develop management alternatives, estimate consequences of implementing those alternatives, and select preferred alternatives by evaluating trade‐offs among alternatives. To determine the preferred mid‐ to long‐term alternatives to managing the rust, we conducted 2 participatory workshops and 18 interviews with individuals to elicit stakeholders’ key concerns and convert them into 5 objectives (minimize management cost, minimize economic cost to industry, minimize effects on natural ecosystems and landscape amenities, and minimize environmental effects associated with use of fungicide) and to identify the 5 management alternatives (full eradication, partial eradication, slow spread, live with it [i.e., major effort invested in mitigation of effects], and do nothing). We also developed decision trees to graphically represent the essence of the decision by displaying the relations between uncertainties and decision points. In the short term or before local expansion of myrtle rust, the do‐nothing alternative was not preferred, but an eradication alternative was only recommended if the probability of eradication exceeded about 40%. After the expansion of myrtle rust, the slow‐the‐spread alternative was preferred regardless of which of the short‐term management alternatives was selected at an earlier stage. The participatory SDM approach effectively resulted in informed and transparent response plans that incorporated multiple objectives in decision‐making processes under high uncertainty.

Dissolved extracellular polymeric substances (dEPS) dynamics and bacterial growth during sea ice formation in an ice tank study - Shazia N. Aslam; Graham J. C. Underwood; Hermanni Kaartokallio; Louiza Norman; Riitta Autio; Michael Fischer; Harri Kuosa; Gerhard S. Dieckmann; David N. Thomas (Polar Biology, 2012)

Factors affecting reproduction in rehabilitant female orangutans: young age at first birth and short inter-birth interval - Noko Kuze; David Dellatore; Graham L. Banes; Peter Pratje; Tomoyuki Tajima; Anne E. Russon (Primates, 2012)

Investigation into the Influence of Primary Crystallization Conditions on the Mechanical Properties and Secondary Processing Behaviour of Fluticasone Propionate for Carrier Based Dry Powder Inhaler Formulations - Harshal A. Kubavat; Jagdeep Shur; Graham Ruecroft; David Hipkiss; Robert Price (Pharmaceutical Research, 2012)

A unified model for gold mineralisation in accretionary orogens and implications for regional-scale exploration targeting methods - Jon M. A. Hronsky; David I. Groves; Robert R. Loucks; Graham C. Begg (Mineralium Deposita, 2012)

Reconciling estimates of the contemporary North American carbon balance among terrestrial biosphere models, atmospheric inversions, and a new approach for estimating net ecosystem exchange from inventory‐based data - Daniel J. Hayes; David P. Turner; Graham Stinson; A. David McGuire; Yaxing Wei; Tristram O. West; Linda S. Heath; Bernardus de Jong; Brian G. McConkey; Richard A. Birdsey; Werner A. Kurz; Andrew R. Jacobson; et al. (Global Change Biology, 2012)
We develop an approach for estimating net ecosystem exchange ( NEE ) using inventory‐based information over North America ( NA ) for a recent 7‐year period (ca. 2000–2006). The approach notably retains information on the spatial distribution of NEE , or the vertical exchange between land and atmosphere of all non‐fossil fuel sources and sinks of CO 2 , while accounting for lateral transfers of forest and crop products as well as their eventual emissions. The total NEE estimate of a −327 ± 252 TgC yr −1 sink for NA was driven primarily by CO 2 uptake in the Forest Lands sector (−248 TgC yr −1 ), largely in the Northwest and Southeast regions of the US, and in the Crop Lands sector (−297 TgC yr −1 ), predominantly in the Midwest US states. These sinks are counteracted by the carbon source estimated for the Other Lands sector (+218 TgC yr −1 ), where much of the forest and crop products are assumed to be returned to the atmosphere (through livestock and human consumption). The ecosystems of Mexico are estimated to be a small net source (+18 TgC yr −1 ) due to land use change between 1993 and 2002. We compare these inventory‐based estimates with results from a suite of terrestrial biosphere and atmospheric inversion models, where the mean continental‐scale NEE estimate for each ensemble is −511 TgC yr −1 and −931 TgC yr −1 , respectively. In the modeling approaches, all sectors, including Other Lands, were generally estimated to be a carbon sink, driven in part by assumed CO 2 fertilization and/or lack of consideration of carbon sources from disturbances and product emissions. Additional fluxes not measured by the inventories, although highly uncertain, could add an additional −239 TgC yr −1 to the inventory‐based NA sink estimate, thus suggesting some convergence with the modeling approaches.

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

High site fidelity and low site connectivity in temperate salt marsh fish populations: a stable isotope approach - Benjamin C. Green; David J. Smith; Jonathan Grey; Graham J. C. Underwood (Oecologia, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.

Bovine IFNGR2, IL12RB1, IL12RB2, and IL23R polymorphisms and MAP infection status - Sameer D. Pant; Chris P. Verschoor; Alicia M. Skelding; Flavio S. Schenkel; Qiumei You; Graham A. Biggar; David F. Kelton; Niel A. Karrow (Mammalian Genome, 2011)

Assessment of regional and local biodiversity in tropical and subtropical coastal habitats in the East African Marine Ecoregion - Natalie Barnes; Roger N. Bamber; Graham Bennell; Nils Cornelius; David Glassom; Sophie Conroy-Dalton Henderson; Narriman Jiddawi; Christine N. W. Lee; Adriano Macia; Daudi J. Msangameno; José Paula; Saleh Yahya; et al. (Biodiversity and Conservation, 2011)

Submarine hydrothermal activity and gold-rich mineralization at Brothers Volcano, Kermadec Arc, New Zealand - Cornel E. J. de Ronde; Gary J. Massoth; David A. Butterfield; Bruce W. Christenson; Junichiro Ishibashi; Robert G. Ditchburn; Mark D. Hannington; Robert L. Brathwaite; John E. Lupton; Vadim S. Kamenetsky; Ian J. Graham; Georg F. Zellmer; et al. (Mineralium Deposita, 2011)

North Atlantic climate responses to perturbations in Antarctic Intermediate Water - Jennifer A. Graham; David P. Stevens; Karen J. Heywood; Zhaomin Wang (Climate Dynamics, 2011)

200 years of European temperature variability: insights from and tests of the proxy surrogate reconstruction analog method - Jörg Franke; J. Fidel González-Rouco; David Frank; Nicholas E. Graham (Climate Dynamics, 2011)

Effect of “Pose” cycling on efficiency and pedaling mechanics - Thomas Korff; Graham Fletcher; David Brown; Lee M. Romer (European Journal of Applied Physiology, 2011)

Effects of Customary Marine Closures on Fish Behavior, Spear‐Fishing Success, and Underwater Visual Surveys - DAVID A. FEARY; JOSHUA E. CINNER; NICHOLAS A. J. GRAHAM; FRASER A. JANUCHOWSKI‐HARTLEY (Conservation Biology, 2011)
Customary management systems (i.e., management systems that limit the use of marine resources), such as rotational fisheries closures, can limit harvest of resources. Nevertheless, the explicit goals of customary management are often to influence fish behavior (in particular flight distance, i.e., distance at which an organism begins to flee an approaching threat), rather than fish abundance. We explored whether the flight distance of reef fishes targeted by local artisanal fishers differed between a customary closure and fished reefs. We also examined whether flight distance of these species affected fishing success and accuracy of underwater visual census (UVC) between customary closed areas and areas open to fishing. Several species demonstrated significant differences in flight distance between areas, indicating that fishing activity may increase flight distance. These relatively long flight distances mean that in fished areas most target species may stay out of the range of spear fishers. In addition, mean flight distances for all species both inside and outside the customary‐closure area were substantially smaller than the observation distance of an observer conducting a belt‐transect UVC (mean [SE]= 8.8 m [0.48]). For targeted species that showed little ability to evade spear fishers, customary closures may be a vital management technique. Our results show that customary closures can have a substantial, positive effect on resource availability and that conventional UVC techniques may be insensitive to changes in flight behavior of fishes associated with fishing. We argue that short, periodic openings of customary closures may allow the health of the fish community to be maintained and local fishers to effectively harvest fishes.

Initiation of HAART during acute simian immunodeficiency virus infection rapidly controls virus replication in the CNS by enhancing immune activity and preserving protective immune responses - David R. Graham; Lucio Gama; Suzanne E. Queen; Ming Li; Angela K. Brice; Kathleen M. Kelly; Joseph L. Mankowski; Janice E. Clements; M. Christine Zink (Journal of NeuroVirology, 2011)

Estimation of the Bidomain Conductivity Parameters of Cardiac Tissue From Extracellular Potential Distributions Initiated by Point Stimulation - Leon S. Graham; David Kilpatrick (Annals of Biomedical Engineering, 2010)

Pooled analyses of 13 prospective cohort studies on folate intake and colon cancer - Dong-Hyun Kim; Stephanie A. Smith-Warner; Donna Spiegelman; Shiaw-Shyuan Yaun; Graham A. Colditz; Jo L. Freudenheim; Edward Giovannucci; R. Alexandra Goldbohm; Saxon Graham; Lisa Harnack; Eric J. Jacobs; Michael Leitzmann; et al. (Cancer Causes & Control, 2010)

Future Spruce Budworm Outbreak May Create a Carbon Source in Eastern Canadian Forests - Caren C. Dymond; Eric T. Neilson; Graham Stinson; Kevin Porter; David A. MacLean; David R. Gray; Michel Campagna; Werner A. Kurz (Ecosystems, 2010)

A standardised sampling protocol for robust assessment of reach‐scale fish community diversity in wadeable New Zealand streams - Bruno O David; Mark P Hamer; Kevin J Collier; Mike D Lake; Graham M Surrey; Kate McArthur; Carol Nicholson; Alton Perrie; Matthew Dale (New Zealand Journal of Marine and Freshwater Research, 2010)
The New Zealand fish fauna contains species that are affected not only by river system connectivity, but also by catchment and local‐scale changes in landcover, water quality and habitat quality. Consequently, native fish have potential as multi‐scale bioindicators of human pressure on stream ecosystems, yet no standardised, repeatable and scientifically defensible methods currently exist for effectively quantifying their abundance or diversity in New Zealand stream reaches. Here we report on the testing of a back‐pack electrofishing method, modified from that used by the United States Environmental Protection Agency, on a wide variety of wadeable stream reaches throughout New Zealand. Seventy‐three first‐ to third‐order stream reaches were fished with a single pass over 150–345 m length. Time taken to sample a reach using single‐pass electrofishing ranged from 1–8 h. Species accumulation curves indicated that, irrespective of location, continuous sampling of 150 stream metres is required to accurately describe reach‐scale fish species richness using this approach. Additional species detection beyond 150 m was rare (

Back to nature: ecological genomics of loblolly pine ( Pinus taeda , Pinaceae) - ANDREW J. ECKERT; ANDREW D. BOWER; SANTIAGO C. GONZÁLEZ‐MARTÍNEZ; JILL L. WEGRZYN; GRAHAM COOP; DAVID B. NEALE (Molecular Ecology, 2010)
Genetic variation is often arrayed in latitudinal or altitudinal clines, reflecting either adaptation along environmental gradients, migratory routes, or both. For forest trees, climate is one of the most important drivers of adaptive phenotypic traits. Correlations of single and multilocus genotypes with environmental gradients have been identified for a variety of forest trees. These correlations are interpreted normally as evidence of natural selection. Here, we use a genome‐wide dataset of single nucleotide polymorphisms (SNPs) typed from 1730 loci in 682 loblolly pine ( Pinus taeda L.) trees sampled from 54 local populations covering the full‐range of the species to examine allelic correlations to five multivariate measures of climate. Applications of a Bayesian generalized linear mixed model, where the climate variable was a fixed effect and an estimated variance–covariance matrix controlled random effects due to shared population history, identified several well‐supported SNPs associating to principal components corresponding to geography, temperature, growing degree‐days, precipitation and aridity. Functional annotation of those genes with putative orthologs in Arabidopsis revealed a diverse set of abiotic stress response genes ranging from transmembrane proteins to proteins involved in sugar metabolism. Many of these SNPs also had large allele frequency differences among populations ( F ST = 0.10–0.35). These results illustrate a first step towards a ecosystem perspective of population genomics for non‐model organisms, but also highlight the need for further integration of the methodologies employed in spatial statistics, population genetics and climate modeling during scans for signatures of natural selection from genomic data.

The influence of vegetation type, soil properties and precipitation on the composition of soil mite and microbial communities at the landscape scale - Uffe N. Nielsen; Graham H. R. Osler; Colin D. Campbell; David F. R. P. Burslem; René van der Wal (Journal of Biogeography, 2010)
Aim We used a landscape‐scale study of birch invasion onto heather moorland to determine the consistency of changes in vegetation type and soil properties and in the community composition of five soil organism groups. Our aim was to determine whether the degree to which soil organisms respond to natural changes and/or induced changes (e.g. changes in land‐use type and climate) in habitat is consistent across trophic and taxonomic groups in the context of conservation policies for birch woodland and heather moorland. Location Mainland Scotland. Methods We sampled mesostigmatid mites, oribatid mites, fungi, bacteria and archaea in adjacent patches of birch woodland (dominated by Betula pubescens ) and heather moorland (dominated by Calluna vulgaris ) at 12 sites for which annual rainfall ranged between 713 and 2251 mm. Differences in community composition were visualized using non‐metric multidimensional scaling based on Bray–Curtis dissimilarities. The factors contributing to differences between habitats within sites were explored using general linear models and those among sites using redundancy analysis. Results The communities of all groups differed between habitats within sites, but only the oribatid mites and fungi differed consistently between habitats across sites. Within sites, dissimilarity in fungal communities was positively related to the difference in C. vulgaris cover between habitats, whereas dissimilarities in bacteria and archaea were positively related to differences in soil pH and C:N ratio between habitats, respectively. Main conclusions The influence of vegetation type and soil properties differed between groups of soil organisms, albeit in a predictable manner, across the 12 sites. Organisms directly associated with plants (fungi), and organisms with microhabitat and resource preferences (Oribatida) were strongly responsive to changes in habitat type. The response of organisms not directly associated with plants (bacteria, archaea) depended on differences in soil properties, while organisms with less clear microhabitat and resource preferences (Mesostigmata) were not strongly responsive to either vegetation type or soil properties. These results show that it is possible to predict the impact of habitat change on specific soil organisms depending on their ecology. Moreover, the community composition of all groups was related to variation in precipitation within the study area, which shows that external factors, such as those caused by climate change, can have a direct effect on belowground communities.

Stability in temperate reef communities over a decadal time scale despite concurrent ocean warming - RICK D. STUART‐SMITH; NEVILLE S. BARRETT; DAVID G. STEVENSON; GRAHAM J. EDGAR (Global Change Biology, 2010)
Despite increasing scientific and public concerns on the potential impacts of global ocean warming on marine biodiversity, very few empirical data on community‐level responses to rising water temperatures are available other than for coral reefs. This study describes changes in temperate subtidal reef communities over decadal and regional scales in a location that has undergone considerable warming in recent decades and is forecast to be a ‘hotspot’ for future warming. Plant and animal communities at 136 rocky reef sites around Tasmania (south‐east Australia) were censused between 1992 and 1995, and again in 2006 and 2007. Despite evidence of major ecological changes before the period of study, reef communities appeared to remain relatively stable over the past decade. Multivariate analyses and univariate metrics of biotic communities revealed few changes with time, although some species‐level responses could be interpreted as symptomatic of ocean warming. These included fishes detected in Tasmania only in recent surveys and several species with warmer water affinities that appeared to extend their distributions further south. The most statistically significant changes observed in species abundances, however, were not related to their biogeographical affinities. The majority of species with changing abundance possessed lower to mid‐range abundances rather than being common, raising questions for biodiversity monitoring and management. We suggest that our study encompassed a relatively stable period following more abrupt change, and that community responses to ocean warming may follow nonlinear, step‐like trajectories.

Conservation planning on a budget: a “resource light” method for mapping priorities at a landscape scale? - Karl A. Didier; David Wilkie; Iain Douglas-Hamilton; Laurence Frank; Nicholas Georgiadis; Max Graham; Festus Ihwagi; Anthony King; Alayne Cotterill; Dan Rubenstein; Rosie Woodroffe (Biodiversity and Conservation, 2009)

Cytosolic pH buffering during exercise and recovery in skeletal muscle of patients with McArdle’s disease - Graham J. Kemp; Caterina Tonon; Emil Malucelli; Claudia Testa; Alexandra Liava; David Manners; Enrico Trevisi; Andrea Martinuzzi; Bruno Barbiroli; Raffaele Lodi (European Journal of Applied Physiology, 2009)

Statistical fraud detection in a commercial lobster fishery - Scott D. J. Graham; John Hasseldine; David Paton (New Zealand Journal of Marine and Freshwater Research, 2009)
In this study we introduce the first step towards a statistical model for the reliability of fisheries data. We applied Benford's Law to catch data from the Atlantic Canadian lobster (Homarus americanus) fishery's lobster fishery areas (LFAs) 33 and 34 and compared our results to those using observations from the “grey zone” (a highly regulated lobster fishery shared by Canada and United States) and a fishery with a different regulatory regime (snow crab, Chionoecetes opilio) . Non‐conformity with Benford's Law is often considered as an indicator of human manipulation of accounting data. We found that observations from the grey zone conformed to the distribution predicted by Benford's Law, whereas observations from snow crab and both lobster fishery areas did not conform.

Combining MCMC with ‘sequential’ PKPD modelling - David Lunn; Nicky Best; David Spiegelhalter; Gordon Graham; Beat Neuenschwander (Journal of Pharmacokinetics and Pharmacodynamics, 2009)

Species effects on ecosystem processes are modified by faunal responses to habitat composition - Mark T. Bulling; Martin Solan; Kirstie E. Dyson; Gema Hernandez-Milian; Patricia Luque; Graham J. Pierce; Dave Raffaelli; David M. Paterson; Piran C. L. White (Oecologia, 2008)

Double haploids, markers and QTL analysis in vegetable brassicas - David Pink; Liz Bailey; Sandy McClement; Paul Hand; Evy Mathas; Vicky Buchanan-Wollaston; Dave Astley; Graham King; Graham Teakle (Euphytica, 2008)

Macro‐ to fine‐scale spatial and temporal distributions and dynamics of phytoplankton and their environmental driving forces in a small montane lake in southern California, USA - David A. Caron; Beth Stauffer; Stefanie Moorthi; Amarjeet Singh; Maxim Batalin; Eric A. Graham; Mark Hansen; William J. Kaiser; Jnaneshwar Das; Arvind Pereira; Amit Dhariwal; Bin Zhang; et al. (Limnology and Oceanography, 2008)
A wireless network of buoys, two autonomous robotic boats, and an autonomous tethered vertical profiling system were used to characterize phytoplankton dynamics and spatiotemporal changes in chemical and physical forcing factors in a small montane lake (Lake Fulmor, Idyllwild, California). Three deployments each year were conducted in 2005 and 2006 to examine seasonal changes in the structure of the lake and phytoplankton assemblage, as well as fine‐scale temporal and spatial variations. The buoys yielded fine‐scale temporal patterns of in situ fluorescence and temperature, while the vertical profiling system yielded two‐dimensional, cross‐sectional profiles of several parameters. The autonomous vehicles provided information on fluorescence and corresponding temperature patterns across the surface of the lake. Average, lake‐wide chlorophyll concentrations increased 10‐ fold seasonally, and strong anoxia developed in the hypolimnion during the summer. The latter process dramatically affected vertical chemical gradients in the 5 m water column of the lake. Small‐scale spatial (

INCREASING LITTER SPECIES RICHNESS REDUCES VARIABILITY IN A TERRESTRIAL DECOMPOSER SYSTEM - Aidan M. Keith; René van der Wal; Rob W. Brooker; Graham H. R. Osler; Stephen J. Chapman; David F. R. P. Burslem; David A. Elston (Ecology, 2008)
Debate on the relationship between diversity and stability has been driven by the recognition that species loss may influence ecosystem properties and processes. We conducted a litterbag experiment in the Scottish Highlands, United Kingdom, to examine the effects of altering plant litter diversity on decomposition, microbial biomass, and microfaunal abundance. The design of treatments was fully factorial and included five species from an upland plant community (silver birch, Betula pendula ; Scots' pine, Pinus sylvestris ; heather, Calluna vulgaris ; bilberry, Vaccinium myrtillus ; wavy‐hair grass, Deschampsia flexuosa ); species richness ranged from one to five species. We tested the effects of litter species richness and composition on variable means, whether increasing litter species richness reduced variability in the decomposer system, and whether any richness–variability relationships were maintained over time (196 vs. 564 days). While litter species composition effects controlled variable means, we revealed reductions in variability with increasing litter species richness, even after accounting for differences between litter types. These findings suggest that higher plant species richness per se may result in more stable ecosystem processes (e.g., decomposition) and decomposer communities. Negative richness–variation relationships generally relaxed over time, presumably because properties of litter mixtures became more homogeneous. However, given that plant litter inputs continue to enter the belowground system over time, we conclude that variation in ecosystem properties may be buffered by greater litter species richness.

Missing methane emissions from leaves of terrestrial plants - DAVID J. BEERLING; TOM GARDINER; GRAHAM LEGGETT; ANDY MCLEOD; W. PAUL QUICK (Global Change Biology, 2008)
The controversial claim that attached leaves of terrestrial plants emit CH 4 aerobically remains to be corroborated. Here, we report CH 4 fluxes and CO 2 exchange rates for leaves of the C 4 species Zea mays using a high‐accuracy traceable online analytical system. In contrast to earlier results for Z. mays , our measurements provide no evidence for substantial aerobic CH 4 emissions from photosynthesizing leaves illuminated with photosynthetically active radiation ( λ =400–700 nm), or from dark‐respiring leaves. Preliminary measurements with the same system indicated a similar lack of aerobic CH 4 emissions in the light or dark from leaves of the C 3 species Nicotiana tabacum . These findings are supported by independent high‐precision 13 C‐labeling studies that also failed to confirm substantial aerobic CH 4 emissions from plants. Nevertheless, we are not able to exclude the possibility that CH 4 emissions from plants may be linked to nonenzymatic processes with an action spectrum lying outside the wavelength range for photosynthesis.

Is MSH2 a breast cancer susceptibility gene? - EE Ming Wong; Andrea A. Tesoriero; Gulietta M. Pupo; Margaret R. E. McCredie; Graham G. Giles; John L. Hopper; Graham J. Mann; David E. Goldgar; Melissa C. Southey (Familial Cancer, 2008)

Dispersal of large branchiopod cysts: potential movement by wind from potholes on the Colorado Plateau - Tim B. Graham; David Wirth (Hydrobiologia, 2008)

Host-delivered RNAi: an effective strategy to silence genes in plant parasitic nematodes - David J. Fairbairn; Antonino S. Cavallaro; Margaret Bernard; Janani Mahalinga-Iyer; Michael W. Graham; José R. Botella (Planta, 2007)

Microarray analysis of gene expression of mouse hepatocytes of different ploidy - Pin Lu; Sandrine Prost; Helen Caldwell; Jonathan D. Tugwood; Graham R. Betton; David J. Harrison (Mammalian Genome, 2007)

The reference genetic linkage map for the multinational Brassica rapa genome sequencing project - Su Ryun Choi; Graham R. Teakle; Prikshit Plaha; Jeong Hee Kim; Charlotte J. Allender; Elena Beynon; Zhong Yun Piao; Pilar Soengas; Tae Ho Han; Graham J. King; Guy C. Barker; Paul Hand; et al. (Theoretical and Applied Genetics, 2007)

Responses of Tuatara ( Sphenodon punctatus ) to Removal of Introduced Pacific Rats from Islands - DAVID R. TOWNS; G. RICHARD PARRISH; CLAUDINE L. TYRRELL; GRAHAM T. USSHER; ALISON CREE; DONALD G. NEWMAN; A. (TONY) H. WHITAKER; IAN WESTBROOKE (Conservation Biology, 2007)
Invasive mammalian predators such as rats are now widespread on islands, but hypotheses about their effects have rarely been tested. Circumstantial evidence from New Zealand indicates that, when introduced to islands, Pacific rats (Rattus exulans) have negative effects on endemic plants, invertebrates, birds, and reptiles, including the tuatara (Sphenodon punctatus). We tested the effects of Pacific rats on tuatara by comparing the demographic structure and body condition of tuatara populations on three islands before and after removal of rats and on a fourth island where rats remained. In the presence of rats, juvenile tuatara constituted on average 0–5% of the sample tuatara populations. When Pacific rats were removed after at least 200 years' occupancy, the proportion of juvenile tuatara increased 3.5‐ to 17‐fold and body condition of adult males and females also improved (sometimes dramatically). We predict that, unless Pacific rats are removed from Taranga Island, the tuatara population will collapse because of low population density and the lack of juvenile recruitment. Our results demonstrate that when invasive species exert subtle effects on recruitment and body condition, the effects on populations of long‐lived endemic species may only become apparent long after the invasion.

Does size matter for dispersal distance? - David G. Jenkins; Camille R. Brescacin; Craig V. Duxbury; Jennifer A. Elliott; Jennafer A. Evans; Katherine R. Grablow; Melissa Hillegass; Boyd N. Lyon; Genevieve A. Metzger; Michelle L. Olandese; Diana Pepe; Greg A. Silvers; et al. (Global Ecology and Biogeography, 2007)
Aim The aim of this study is to answer the questions: (1) do small organisms disperse farther than large, or vice versa; and (2) does the observed pattern differ for passive and active dispersers? These questions are central to several themes in biogeography (including microbial biogeography), macroecology, metacommunity ecology and conservation biology. Location The meta‐analysis was conducted using published data collected worldwide. Methods We collected and analysed 795 data values in the peer‐reviewed literature for direct observations of both maximal dispersal distance and mass of the dispersing organisms (e.g. seeds, not trees). Analysed taxa ranged in size from bacteria to whales. We applied macroecology analyses based on null models (using Monte Carlo randomizations) to test patterns relative to specific hypotheses. Results Collected dispersal distance and mass data spanned 9 and 21 orders of magnitude, respectively. Active dispersers dispersed significantly farther ( P P Conclusions Size is important to maximal dispersal distance for active dispersers, but not for passive dispersers. Claims that microbes disperse widely cannot be tested by current data based on direct observations of dispersal: indirect approaches will need to be applied. Distance–mass relationships should contribute to a resolution of neutral and niche‐based metacommunity theories by helping scale expectations for dispersal limitation. Also, distance–mass relationships should inform analyses of latitudinal species richness and conservation biology topics such as fragmentation, umbrella species and taxonomic homogenization.

Historical changes in the phenology of British Odonata are related to climate - CHRISTOPHER HASSALL; DAVID J. THOMPSON; GRAHAM C. FRENCH; IAN F. HARVEY (Global Change Biology, 2007)
Responses of biota to climate change take a number of forms including distributional shifts, behavioural changes and life history changes. This study examined an extensive set of biological records to investigate changes in the timing of life history transitions (specifically emergence) in British Odonata between 1960 and 2004. The results show that there has been a significant, consistent advance in phenology in the taxon as a whole over the period of warming that is mediated by life history traits. British odonates significantly advanced the leading edge (first quartile date) of the flight period by a mean of 1.51 ±0.060 (SEM, n =17) days per decade or 3.08±1.16 (SEM, n =17) days per degree rise in temperature when phylogeny is controlled for. This study represents the first review of changes in odonate phenology in relation to climate change. The results suggest that the damped temperature oscillations experienced by aquatic organisms compared with terrestrial organisms are sufficient to evoke phenological responses similar to those of purely terrestrial taxa.

Differential ability of D1 and D2 dopamine receptor agonists to induce and modulate expression and reinstatement of cocaine place preference in rats - Danielle L. Graham; Regis Hoppenot; April Hendryx; David W. Self (Psychopharmacology, 2007)

Historical changes in the phenology of British Odonata are related to climate - CHRISTOPHER HASSALL; DAVID J. THOMPSON; GRAHAM C. FRENCH; IAN F. HARVEY (Global Change Biology, 2007)

Manganese superoxide dismutase polymorphism and risk of skin cancer (United States) - Jiali Han; Graham A. Colditz; David J. Hunter (Cancer Causes & Control, 2007)

Abundance of six tetracycline resistance genes in wastewater lagoons at cattle feedlots with different antibiotic use strategies - Nicholas Peak; Charles W. Knapp; Richard K. Yang; Margery M. Hanfelt; Marilyn S. Smith; Diana S. Aga; David W. Graham (Environmental Microbiology, 2007)
Summary The abundance of six tetracycline resistance genes tet (O) , tet (Q) , tet (W) , tet (M), tet (B) and tet (L), were quantified over time in wastewater lagoons at concentrated animal feeding operations (CAFO) to assess how feedlot operation affects resistance genes in downstream surface waters. Eight lagoons at five cattle feedlots in the Midwestern United States were monitored for 6 months. Resistance and 16S‐rRNA gene abundances were quantified using real‐time PCR, and physicochemical lagoon conditions, tetracycline levels, and other factors (e.g. feedlot size and weather conditions) were monitored over time. Lagoons were sorted according to antibiotic use practice at each site, and designated as ‘no‐use’, ‘mixed‐use’ or ‘high‐use’ for comparison. High‐use lagoons had significantly higher detected resistance gene levels (tet R ; 2.8 × 10 6 copies ml −1 ) relative to no‐use lagoons (5.1 × 10 3 copies ml −1 ; P 5 copies ml −1 ; P = 0.076). Bivariate correlation analysis on pooled data ( n = 54) confirmed that tet R level strongly correlated with feedlot area ( r = 0.67, P r = 0.51, P tet (M) was the most commonly detected gene, both in absolute number and normalized to 16S‐rRNA gene level, although tet (O), tet (Q) and tet (W) levels were also high in the mixed and high‐use lagoons. Finally, resistance gene levels were highly seasonal with abundances being 10–100 times greater in the autumn versus the summer. Results show that antibiotic use strategy strongly affects both the abundance and seasonal distribution of resistance genes in associated lagoons, which has implications on water quality and feedlot management practices.

Multiple anthropogenic stressors cause ecological surprises in boreal lakes - MICHAEL R. CHRISTENSEN; MARK D. GRAHAM; ROLF D. VINEBROOKE; DAVID L. FINDLAY; MICHAEL J. PATERSON; MICHAEL A. TURNER (Global Change Biology, 2006)
The number of combinations of anthropogenic stressors affecting global change is increasing; however, few studies have empirically tested for their interactive effects on ecosystems. Most importantly, interactions among ecological stressors generate nonadditive effects that cannot be easily predicted based on single‐stressor studies. Here, we corroborate findings from an in situ mesocosm experiment with evidence from a whole‐ecosystem manipulation to demonstrate for the first time that interactions between climate and acidification determine their cumulative impact on the food‐web structure of coldwater lakes. Interactions among warming, drought, and acidification, rather than the sum of their individual effects, best explained significant changes in planktonic consumer and producer biomass over a 23‐year period. Further, these stressors interactively exerted significant synergistic and antagonistic effects on consumers and producers, respectively. The observed prevalence of long‐ and short‐term ecological surprises involving the cumulative impacts of multiple anthropogenic stressors highlights the high degree of uncertainty surrounding current forecasts of the consequences of global change.

Frequent Tanning Bed Use, Weight Concerns, and Other Health Risk Behaviors in Adolescent Females (United States) - David L. O’Riordan; Alison E. Field; Alan C. Geller; Daniel R. Brooks; Gideon Aweh; Graham A. Colditz; A. Lindsay Frazier (Cancer Causes & Control, 2006)

A Pooled Analysis of 12 Cohort Studies of Dietary Fat, Cholesterol and Egg Intake and Ovarian Cancer - Jeanine M. Genkinger; David J. Hunter; Donna Spiegelman; Kristin E. Anderson; W. Lawrence Beeson; Julie E. Buring; Graham A. Colditz; Gary E. Fraser; Jo L. Freudenheim; R. Alexandra Goldbohm; Susan E. Hankinson; Karen L. Koenig; et al. (Cancer Causes & Control, 2006)

An estimate of population sizes of burrowing seabirds at the Diego Ramirez archipelago, Chile, using distance sampling and burrow-scoping - Kieran Lawton; Graham Robertson; Roger Kirkwood; José Valencia; Roberto Schlatter; David Smith (Polar Biology, 2006)

Forest Roads as Partial Barriers to Terrestrial Salamander Movement - DAVID M. MARSH; GRAHAM S. MILAM; NICHOLAS P. GORHAM; NOELLE G. BECKMAN (Conservation Biology, 2005)
Roads can fragment animal populations by disrupting movement among formerly continuous habitats. Although models have demonstrated that disrupted movement can contribute to long‐term extinction, there are few empirical data on the effects of roads on animal movement. We used displacement and homing experiments to determine whether forest roads are barriers to the movement of terrestrial salamanders. We displaced 1471 red‐backed salamanders (Plethodon cinereus) across five forest roads and compared return rates to those of salamanders displaced equal distances toward the forest interior. Roads significantly reduced the return rate of salamanders, with a mean reduction of 51%. Steep roadside verges further reduced return rates, particularly for salamanders moving downhill across verges. The permeability of roads to salamander movement did not appear to be related to road surface type. Gravel roads had both the highest and lowest observed permeability with the two paved roads intermediate between these. We conclude that narrow forest roads are partial barriers to salamander movement and that steep roadside verges may exacerbate these effects.

SNPs in the neural cell adhesion molecule 1 gene (NCAM1) may be associated with human neural tube defects - Kristen L. Deak; Abee L. Boyles; Heather C. Etchevers; Elizabeth C. Melvin; Deborah G. Siegel; Felicia L. Graham; Susan H. Slifer; David S. Enterline; Timothy M. George; Michel Vekemans; David McClay; Alexander G. Bassuk; et al. (Human Genetics, 2005)

Locomotor activity detects subunit-selective effects of agonists and decahydroisoquinoline antagonists at AMPA/kainic acid ionotropic glutamate receptors in adult rats - Michael F. O’Neill; Graham Sanger; Paul L. Ornstein; David J. Osborne; Sandra M. Woodhouse (Psychopharmacology, 2005)

Acyl-CoA elongase activity and gene from the marine microalga Pavlova lutheri (Haptophyceae) - Thierry Tonon; David Harvey; Tony R. Larson; Yi Li; Ian A. Graham (Journal of Applied Phycology, 2005)

Zinc protects against arsenic-induced apoptosis in a neuronal cell line, measured by DEVD-caspase activity - Austin Graham Milton; Peter David Zalewski; Ranjit Nihal Ratnaike (BioMetals, 2004)

Estrogen Receptor β lpar;ESR2) Polymorphisms and Endometrial Cancer (United States) - Veronica Wendy Setiawan; Susan E. Hankinson; Graham A. Colditz; David J. Hunter; Immaculata De Vivo (Cancer Causes & Control, 2004)

The re-stocking of captive-bred ruffed lemurs (Varecia variegata variegata) into the Betampona Reserve, Madagascar: methodology and recommendations - Adam Britt; Charles Welch; Andrea Katz; Bernard Iambana; Ingrid Porton; Randall Junge; Graham Crawford; Cathy Williams; David Haring (Biodiversity and Conservation, 2004)

Grasping the meaning of words - Scott Glover; David A. Rosenbaum; Jeremy Graham; Peter Dixon (Experimental Brain Research, 2004)

Effects of oxygen and nitrogen conditions on the transformation kinetics of 1,2-dichloroethenes by Methylosinus trichosporium OB3b and its sMMO C mutant - Hyung J. Kim; David W. Graham (Biodegradation, 2003)

Identification of the 7,8-didemethyl-8-hydroxy-5-deazariboflavin synthase required for coenzyme F 420 biosynthesis - David E. Graham; Huimin Xu; Robert H. White (Archives of Microbiology, 2003)

Effects of elevated atmospheric CO 2 on net ecosystem CO 2 exchange of a scrub–oak ecosystem - Graham J. Hymus; David P. Johnson; Sabina Dore; Hans P. Anderson; C. Ross Hinkle; Bert G. Drake (Global Change Biology, 2003)
We report the results of a 2‐year study of effects of the elevated (current ambient plus 350 μmol CO 2 mol −1 ) atmospheric CO 2 concentration ( C a ) on net ecosystem CO 2 exchange ( NEE ) of a scrub–oak ecosystem. The measurements were made in open‐top chambers (OTCs) modified to function as open gas‐exchange systems. The OTCs enclosed samples of the ecosystem (ca. 10 m 2 surface area) that had regenerated after a fire, 5 years before, in either current ambient or elevated C a . Throughout the study, elevated C a increased maximum NEE ( NEE max ) and the apparent quantum yield of the NEE ( φ NEE ) during the photoperiod. The magnitude of the stimulation of NEE max , expressed per unit ground area, was seasonal, rising from 50% in the winter to 180% in the summer. The key to this stimulation was effects of elevated C a , and their interaction with the seasonal changes in the environment, on ecosystem leaf area index, photosynthesis and respiration. The separation of these factors was difficult. When expressed per unit leaf area the stimulation of the NEE max ranged from 7% to 60%, with the increase being dependent on increasing soil water content ( W soil ). At night, the CO 2 effluxes from the ecosystem ( NEE night ) were on an average 39% higher in elevated C a . However, the increase varied between 6% and 64%, and had no clear seasonality. The partitioning of NEE night into its belowground ( R below ) and aboveground ( R above ) components was carried out in the winter only. A 35% and 27% stimulation of NEE night in December 1999 and 2000, respectively, was largely due to a 26% and 28% stimulation of R below in the respective periods, because R below constituted ca. 87% of NEE night . The 37% and 42% stimulation of R above in December 1999 and 2000, respectively, was less than the 65% and 80% stimulation of the aboveground biomass by elevated C a at these times. An increase in the relative amount of the aboveground biomass in woody tissue, combined with a decrease in the specific rate of stem respiration of the dominant species Quercus myrtifolia in elevated C a , was responsible for this effect. Throughout this study, elevated C a had a greater effect on carbon uptake than on carbon loss, in terms of both the absolute flux and relative stimulation. Consequently, for this scrub–oak ecosystem carbon sequestration was greater in the elevated C a during this 2‐year study period.

Establishing the Canadian Community Monitoring Network - Graham Whitelaw; Hague Vaughan; Brian Craig; David Atkinson (Environmental Monitoring and Assessment, 2003)

Isolation of two cDNAs encoding E2 ubiquitin-conjugating enzymes from Pavlova lutheri (Haptophyceae) - Thierry Tonon; David Harvey; Yi Li; Ian A. Graham (Journal of Applied Phycology, 2003)

Effects of intense versus diffuse population bottlenecks on microsatellite genetic diversity and evolutionary potential - Phillip R. England; Graham H.R. Osler; Lynn M. Woodworth; Margaret E. Montgomery; David A. Briscoe; Richard Frankham (Conservation Genetics, 2003)

Cross validation of open‐top chamber and eddy covariance measurements of ecosystem CO 2 exchange in a Florida scrub‐oak ecosystem - Sabina Dore; Graham J. Hymus; David P. Johnson; C. R. Hinkle; Riccardo Valentini; Bert G. Drake (Global Change Biology, 2003)
Simultaneous measurements of net ecosystem CO 2 exchange (NEE) were made in a Florida scrub‐oak ecosystem in August 1997 and then every month between April 2000 to July 2001, using open top chambers (NEE O ) and eddy covariance (NEE E ). This study provided a cross validation of these two different techniques for measuring NEE. Unique characteristics of the comparison were that the measurements were made simultaneously, in the same stand, with large replicated chambers enclosing a representative portion of the ecosystem (75 m 2 , compared to approximately 1–2 ha measured by the eddy covariance system). The value of the comparison was greatest at night, when the microclimate was minimally affected by the chambers. For six of the 12 measurement periods, night NEE O was not significantly different to night NEE E , and for the other periods the maximum difference was 1.1 µ mol m − 2 s − 1 , with an average of 0.72 ± 0.09 µ mol m − 2 s − 1 . The comparison was more difficult during the photoperiod, because of differences between the microclimate inside and outside the chambers. During the photoperiod, air temperature (T air ) and air vapour pressure deficits (VPD) became progressively higher inside the chambers until mid‐afternoon. In the morning NEE O was higher than NEE E by about 26%, consistent with increased temperature inside the chambers. Over the mid‐day period and the afternoon, NEE O was 8% higher that NEE E , regardless of the large differences in microclimate. This study demonstrates both the uses and difficulties associated with attempting to cross validate NEE measurements made in chambers and using eddy covariance. The exercise was most useful at night when the chamber had a minimal effect on microclimate, and when the measurement of NEE is most difficult.

Caspase-9 Inhibition after Focal Cerebral Ischemia Improves Outcome following Reversible Focal Ischemia - Graham Mouw; Jennifer L. Zechel; Yifang Zhou; W. David Lust; Warren R. Selman; Robert A. Ratcheson (Metabolic Brain Disease, 2002)

Aspirin, other NSAIDs, and ovarian cancer risk (United States) - Kathleen M. Fairfield; David J. Hunter; Charles S. Fuchs; Graham A. Colditz; Susan E. Hankinson (Cancer Causes & Control, 2002)

Vitamins and carotenoids intake and the risk of basal cell carcinoma of the skin in women (United States) - Teresa T. Fung; David J. Hunter; Donna Spiegelman; Graham A. Colditz; Frank E. Speizer; Walter C. Willett (Cancer Causes & Control, 2002)

Acclimation of photosynthesis and respiration to elevated atmospheric CO 2 in two Scrub Oaks - Graham J. Hymus; Tom G. Snead; David P. Johnson; Bruce A. Hungate; Bert G. Drake (Global Change Biology, 2002)
For two species of oak, we determined whether increasing atmospheric CO 2 concentration ( C a ) would decrease leaf mitochondrial respiration (R) directly, or indirectly owing to their growth in elevated C a , or both. In particular, we tested whether acclimatory decreases in leaf‐Rubisco content in elevated C a would decrease R associated with its maintenance. This hypothesis was tested in summer 2000 on sun and shade leaves of Quercus myrtifolia Willd. and Quercus geminata Small. We also measured R on five occasions between summer 1999 and 2000 on leaves of Q. myrtifolia . The oaks were grown in the field for 4 years, in either current ambient or elevated (current ambient + 350 µmol mol −1 ) C a , in open‐top chambers (OTCs). For Q. myrtifolia , an increase in C a from 360 to 710 µmol mol −1 had no direct effect on R at any time during the year. In April 1999, R in young Q. myrtifolia leaves was significantly higher in elevated C a —the only evidence for an indirect effect of growth in elevated C a . Leaf R was significantly correlated with leaf nitrogen (N) concentration for the sun and shade leaves of both the species of oak. Acclimation of photosynthesis in elevated C a significantly reduced maximum RuBP‐saturated carboxylation capacity ( V c max ) for both the sun and shade leaves of only Q. geminata . However, we estimated that only 11–12% of total leaf N was invested in Rubisco; consequently, acclimation in this plant resulted in a small effect on N and an insignificant effect on R. In this study measurements of respiration and photosynthesis were made on material removed from the field; this procedure had no effect on gas exchange properties. The findings of this study were applicable to R expressed either per unit leaf area or unit dry weight, and did not support the hypothesis that elevated C a decreases R directly, or indirectly owing to acclimatory decreases in Rubisco content.

Prostate cancer screening practices and cancer control research (United States) - David Schottenfeld; Graham A. Colditz (Cancer Causes & Control, 2002)

Elevated atmospheric CO 2 stimulates aboveground biomass in a fire‐regenerated scrub‐oak ecosystem - Paul Dijkstra; Graham Hymus; Debra Colavito; David A. Vieglais; Christina M. Cundari; David P. Johnson; Bruce A. Hungate; C. ROSS Hinkle; Bert G. Drake (Global Change Biology, 2002)
The effect of elevated atmospheric CO 2 concentration ( C a ) on the aboveground biomass of three oak species, Quercus myrtifolia , Q. geminata , and Q. chapmanii , was estimated nondestructively using allometric relationships between stem diameter and aboveground biomass after four years of experimental treatment in a naturally fire‐regenerated scrub‐oak ecosystem. After burning a stand of scrub‐oak vegetation, re‐growing plants were exposed to either current ambient (379 µL L −1 CO 2 ) or elevated (704 µL L −1 CO 2 ) C a in 16 open‐top chambers over a four‐year period, and measurements of stem diameter were carried out annually on all oak shoots within each chamber. Elevated C a significantly increased aboveground biomass, expressed either per unit ground area or per shoot; elevated C a had no effect on shoot density. The relative effect of elevated C a on aboveground biomass increased each year of the study from 44% (May 96–Jan 97), to 55% (Jan 97–Jan 98), 66% (Jan 98–Jan 99), and 75% (Jan 99–Jan 00). The effect of elevated C a was species specific: elevated C a significantly increased aboveground biomass of the dominant species, Q. myrtifolia , and tended to increase aboveground biomass of Q. chapmanii , but had no effect on aboveground biomass of the subdominant, Q. geminata . These results show that rising atmospheric CO 2 has the potential to stimulate aboveground biomass production in ecosystems dominated by woody species, and that species‐specific growth responses could, in the long term, alter the composition of the scrub‐oak community.

Antibiotic resistance in bacteria from magpies ( Pica pica ) and rabbits ( Oryctolagus cuniculus ) from west Wales - David M. Livermore; Marina Warner; Lucinda M. C. Hall; Virve I. Enne; Stephen J. Projan; Paul M. Dunman; Sarah L. Wooster; Graham Harrison (Environmental Microbiology, 2001)
Summary The prevalence of antibiotic‐resistant bacteria in wild animal and bird populations is largely unknown, with little consistency among the few published reports. We therefore examined intestinal bacteria from magpies ( Pica pica ) and rabbits ( Oryctolagus cuniculus ) collected in rural west Wales. Escherichia coli isolates resistant to multiple antibiotics were grown from eight of 20 magpies trapped in spring, 1999 and one of 17 in spring, 2000; the most prevalent resistance trait among these isolates was to tetracycline, but resistances to ampicillin, chloramphenicol, kanamycin, sulphonamide, tetracycline and trimethoprim were also found. Tetracycline‐resistant Enterococcus spp. were found in one of 20 magpies in 1999 and three of 17 in 2000. Only one resistant E. coli isolate was detected among gut bacteria from 13 rabbits, and this strain was resistant only to tetracycline. Differences in the prevalence of resistance between bacteria from rabbits and magpies may reflect differences in diet: rabbits graze field edges, whereas magpies are omnivorous and opportunistic. The resistance genes found in E. coli isolates from magpies mostly corresponded to those common among human isolates, but those conferring tetracycline resistance were unique.

Central effects of urotensin-II following ICV administration in rats - Jane Gartlon; Frederick Parker; David Harrison; Stephen Douglas; Tracey Ashmeade; Graham Riley; Zoe Hughes; Stephen Taylor; Richard Munton; Jim Hagan; Jackie Hunter; Declan Jones (Psychopharmacology, 2001)

The Biodiversity and Conservation of Saproxylic Diptera In Scotland - Graham E. Rotheray; Geoff Hancock; Steve Hewitt; David Horsfield; Iain MacGowan; David Robertson; Kenneth Watt (Journal of Insect Conservation, 2001)

The Use of Inverse Phase Gas Chromatography to Measure the Surface Energy of Crystalline, Amorphous, and Recently Milled Lactose - Helen E. Newell; Graham Buckton; David A. Butler; Frank Thielmann; Daryl R. Williams (Pharmaceutical Research, 2001)

New Zealand mistletoes have equal or lower capacities for electron transport than their hosts - Graham L. Strong; Peter Bannister; David J. Burritt (New Zealand Journal of Botany, 2001)
previous work on the New Zealand mistletoes Ileostylus micranthus and Tupeia antarctica indicates that these mistletoes have lower maximum electron transport rates (ETR max ) than their hosts. We extend this research by testing Seven of the eight extant endemic New Zealand mistletoes using chlorophyll fluorescence measurements. In addition, we examined whether loranthaceous (Alepis flavida & Ileostylus micranthus, peraxilla Colensoi p. tetra‐petala Tupeia antarctica) and viscaceous mistletoes (Korthalsella Iindsayi, K. salicornioides) differed in their capacities for electron transport. Electron transport rates were significantly related to photosyn‐thetically active Photon flux densities (PPFD). Overall, mistletoes had significantly lower (110 ± 18 mol m ‐ s ‐1 ) ETR max than their hosts (219 ± 43 mol m ‐2 S ‐1 ) but Some specific host‐mistletoes Pairs showed no significant difference in ETR max There was no clear distinction in ETR max between mistletoe families. We conclude that New Zealand mistletoes generally have lower electron transport rates at the same PPFD and, usually, lower photosynthetic capacities than their hosts.

Gene structure, alternative splicing, and chromosomal localization of pro-apoptotic Bcl-2 relative Bim - Philippe Bouillet; Li Chen Zhang; David C.S. Huang; Graham C. Webb; Cynthia D.K. Bottema; Paul Shore; Helen J. Eyre; Grant R. Sutherland; Jerry M. Adams (Mammalian Genome, 2001)

New immunodiagnostic system - Euan R. Tovey; David J.M. Taylor; Anthony H. Graham; Timothy J. O'Meara; Uffe Lovborg; Allan Jones; Richard Sporik (Aerobiologia, 2000)

Citrus root responses to localized drying soil: A new approach to studying mycorrhizal effects on the roots of mature trees - Javier F. Espeleta; David M. Eissenstat; James H. Graham (Plant and Soil, 1999)

MIC-A allele profiles and HLA class I associations in Behçet's disease - Graham R. Wallace; David H. Verity; Lisa J. Delamaine; Shigeaki Ohno; Hidetoshi Inoko; Masao Ota; Nobuhisa Mizuki; Kazuro Yabuki; Elli Kondiatis; Henry A. F. Stephens; Wafa Madanat; Charles A. Kanawati; et al. (Immunogenetics, 1999)

Electron-energy-loss spectroscopic imaging of calcium and nitrogen in the cell walls of apple fruits - I. Max Huxham; Michael C. Jarvis; Lynette Shakespeare; Colin J. Dover; David Johnson; J. Paul Knox; Graham B. Seymour (Planta, 1999)

Exopolymer production by intertidal epipelic diatoms - David J. Smith; Graham J. C. Underwood (Limnology and Oceanography, 1998)
Epipelic diatoms are motile, the locomotive force being generated by the extrusion of carbohydrate‐rich exopolymers (EPS). Production rates of EPS, colloidal (water‐soluble) carbohydrates, and glucan (a photosynthetic storage product of diatoms) were investigated in axenic cultures, in sediments under laboratory conditions, and in the field. In stationary‐phase axenic monocultures of Cylindrotheca closterium , Navicula perminuta , and Nitzschia sigma , EPS concentrations significantly increased during darkness. EPS concentrations in darkness corresponded to decreases in glucan concentration. Glucan concentrations increased significantly in illuminated cultures, Identical patterns of concentration changes were observed in intact diatom‐dominated sediments. Inorganic 14 C incorporation was used to determine rates of production and flux of photoassimilates through the different carbohydrate fractions in intact sediments. Biofilms exhibited endogenous rhythms of primary and carbohydrate production under laboratory conditions in the absence of tidal influence and under constant illumination (200 µmol m −2 s −1 ). Maximum production (27.7 mg C m −2 h −1 ) occurred during periods when sediments would have been emersed had they remained in the field, with 8.0, 3.0, and 0.8% of photoassimilates being incorporated into colloidal‐S, glucan, and EPS, respectively. Higher rates of primary production were measured under natural illumination (617 µmol m −2 s −1 ) in the field (82.7 mg C m −2 h −1 ), but the maximum incorporation into colloidal‐S, glucan, and EPS was similar (10.9, 2.8, and 1.0%, respectively). Pulse experiments revealed that 14 C initially incorporated into glucan was subsequently reallocated into EPS. Increases in labeled EPS occurred up to 4 h after 14 C incorporation, coinciding with periods of migratory activity linked to impending tidal immersion. Production of EPS by epipelic diatoms therefore appears to be closely linked to migratory rhythms, During periods of photosynthesis, assimilated carbon is stored as intracellular glucan, as well as being utilized to produce EPS. A number of stimuli increase the production of EPS: dim light, darkness, and migration linked to tidal immersion. Such increases in EPS production can be met either by increasing the allocation of photoassimilated carbon from current photosynthesis or by reallocating an internal carbon source. This short‐term variability in EPS production has implications for our understanding of estuarine carbon budgets and biogenic stabilization of sediments.

Theoretical modelling of some spatial and temporal aspects of the mitochondrion/creatine kinase/ myofibril system in muscle - Graham J. Kemp; David N. Manners; Joseph F. Clark; Mark E. Bastin; George K. Radda (Molecular and Cellular Biochemistry, 1998)

Petrology and geochronology of basalt breccia from the 1996 earthquake swarm of Loihi seamount, Hawaii: magmatic history of its 1996 eruption - Michael O. Garcia; Kenna H. Rubin; Marc D. Norman; J. Michael Rhodes; David W. Graham; David W. Muenow; Khalil Spencer (Bulletin of Volcanology, 1998)

Inflammation-associated lysyl oxidase protein expression in vivo, and modulation by FGF-2 plus IGF-1 - P. C. Trackman; Rudolph J. Graham; Howard K. Bittner; David L. Carnes; James A. Gilles; Dana T. Graves (Histochemistry and Cell Biology, 1998)

Nitrate in drinking water and the incidence of gastric, esophageal, and brain cancer in Yorkshire, England - Jennifer H. Barrett; Roger C. Parslow; Patricia A. McKinney; Graham R. Law; David Forman (Cancer Causes & Control, 1998)

Increasing Himalayan tahr and decreasing chamois densities in the eastern Southern Alps, New Zealand: evidence for interspecific competition - David M. Forsyth; Graham J. Hickling (Oecologia, 1998)

A prospective study of oral contraceptive use and risk of breast cancer (Nurses' Health Study, United States) - Susan E. Hankinson; Graham A. Colditz; JoAnn E. Manson; Walter C. Willett; David J. Hunter; Meir J. Stampfer; Frank E. Speizer (Cancer Causes & Control, 1997)

Non-dietary factors as risk factors for breast cancer, and as effect modifiers of the association of fat intake and risk of breast cancer - David J. Hunter; Donna Spiegelman; Hans-Olov Adami; Piet A. van den Brandt; Aaron R. Folsom; R. Alexandra Goldbohm; Saxon Graham; Goeffrey R. Howe; Lawrence H. Kushi; James R. Marshall; Anthony B. Miller; Frank E. Speizer; et al. (Cancer Causes & Control, 1997)

Book reviews - David L. Hawksworth; Clem Tisdell; J. H. Graham (Biodiversity and Conservation, 1995)

Improving recall from an associative memory - Bruce Graham; David Willshaw (Biological Cybernetics, 1995)

Improving recall from an associative memory - Bruce Graham; David Willshaw (Biological Cybernetics, 1995)

The delayed neuropathic effects of nerve agents and some other organophosphorus compounds - James J. Gordon; Robert H. Inns; Martin K. Johnson; Levence Leadbeater; Michael P. Maidment; David G. Upshall; Graham H. Cooper; Robert L. Rickard (Archives of Toxicology, 1983)

Exchange of colicin receptor capacity between strains of Escherichia coli sensitive or resistant to colicin K-K235 - David P. Brunner; Gary S. Graham; Ronald W. Treick (Archives of Microbiology, 1982)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)